Lithium-ion rechargeable battery
Patent Information
- Application Number
- JP2025059697
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0018】 本発明の一態様により、リチウムイオン二次電池に用いることができ、リチウムイオンの挿入脱離が促進される正極活物質粒子を提供することができる。または、高レート放電時における放電容量の低下が抑制された正極活物質粒子または複合酸化物を提供することができる。または、低温環境における放電容量の低下が抑制された正極活物質粒子または複合酸化物を提供することができる。または、充放電サイクルにおける放電容量の低下が抑制された正極活物質粒子または複合酸化物を提供することができる。または、充放電を繰り返しても結晶構造が崩れにくい正極活物質粒子または複合酸化物を提供することができる。または、放電容量が大きい正極活物質粒子または複合酸化物を提供することができる。または、安全性又は信頼性の高い二次電池、当該二次電池を有する電子機器または当該二次電池を有する車両を提供することができる。
Smart Images

Figure 2026166633000001_ABST
Abstract
Description
[Technical Field]
[0001] One aspect of the present invention relates to a product, a method, or a method of manufacturing; or to a process, a machine, a manufacture, or a composition of matter. Another aspect of the present invention relates to an energy storage device including a secondary battery, a semiconductor device, a display device, a light-emitting device, a lighting device, an electronic device, or a method of manufacturing the same.
[0002] In this specification, "electronic equipment" refers to all devices that have an energy storage device, and all electro-optical devices with an energy storage device, information terminal devices with an energy storage device, etc., are considered electronic equipment. [Background technology]
[0003] In recent years, there has been a great deal of development on various energy storage devices, including lithium-ion secondary batteries, lithium-ion capacitors, air batteries, and all-solid-state batteries. In particular, the demand for lithium-ion secondary batteries, which offer high output and high capacity, has expanded rapidly in line with the development of the semiconductor industry, and they have become indispensable as a source of rechargeable energy in today's information society.
[0004] In particular, there is a high demand for secondary batteries with a large discharge capacity per unit weight and excellent cycle characteristics, especially for mobile electronic devices. To meet these demands, there is a great deal of research being done on improving the positive electrode active material of secondary batteries (for example, Patent Documents 1 and 2). Research is also being conducted on the crystal structure of positive electrode active material particles (Non-Patent Documents 1 to 3).
[0005] X-ray diffraction (XRD) is one of the methods used to analyze the crystal structure of positive electrode active material particles. By using the ICSD (Inorganic Crystal Structure Database) introduced in Non-Patent Document 4, XRD data can be analyzed. For example, the lattice constant of lithium cobalt oxide described in Non-Patent Document 5 can be referenced from the ICSD. For Rietveld method analysis, for example, the analysis program RIETAN-FP (Non-Patent Document 6) can be used. In addition, VESTA (Non-Patent Document 7) can be used as crystal structure plotting software.
[0006] Furthermore, ImageJ (Non-Patent Documents 8 to 10) is known as an image processing software. By using this software, it is possible to analyze, for example, the shape of positive electrode active material particles.
[0007] Micro-electron diffraction is also effective for identifying the crystal structure of positive electrode active material particles, particularly the crystal structure of the surface layer. For analyzing electron diffraction patterns, for example, the analysis program ReciPro (Non-Patent Literature 11) can be used. Furthermore, STEM (Scanning Transmission Electron Microscope)-EDX (Energy Dispersive X-ray Spectroscopy) can be used for elemental analysis of the positive electrode active material. Non-Patent Literature 12 is known as the detection limit (also called the lower detection limit) when using STEM-EDX.
[0008] As lithium cobalt oxide, in addition to LiCoO₂ having a layered rock-salt type crystal structure with space group R-3m, which is often used as a positive electrode active material for secondary batteries, LiCoO₂ having a LiTiO₂-type crystal structure with space group Fd-3m is known (Non-Patent Document 13, Non-Patent Document 14). LiCoO₂ having a LiTiO₂-type crystal structure with space group Fd-3m is also referred to as having a Li₂Ti₂O₄ structure, an LT-LiCoO₂ structure, or the like, and has a structure in which lithium is at the 16c position, cobalt is at the 16d position, and oxygen is at the 32e position in Wyckoff Positions (Non-Patent Document 15).
Prior Art Documents
Patent Documents
[0009]
Patent Document 1
Patent Document 2
Non-Patent Documents
[0010]
Non-Patent Document 1
Non-Patent Document 2
Non-Patent Document 3
[0011] Lithium-ion secondary batteries still have room for improvement in various aspects, including output characteristics, discharge capacity, cycle characteristics, reliability, safety, and cost. For example, in order to suppress changes in the crystal structure of the surface of the positive electrode active material particles, the surface of the positive electrode active material particles is sometimes coated with an inert oxide, but this coating may inhibit the insertion and removal of lithium ions. If the insertion and removal of lithium ions is inhibited, there is a concern that the characteristics of the secondary battery will deteriorate, such as a decrease in discharge capacity during high-rate discharge (also called a decrease in output characteristics or a decrease in rate characteristics) and a decrease in charge and discharge capacity in low-temperature environments.
[0012] Therefore, one aspect of the present invention aims to provide positive electrode active material particles that can be used in lithium-ion secondary batteries and promote the insertion and removal of lithium ions. Alternatively, one aspect aims to provide positive electrode active material particles or composite oxides in which the decrease in discharge capacity during high-rate discharge is suppressed. Alternatively, one aspect aims to provide positive electrode active material particles or composite oxides in which the decrease in discharge capacity in low-temperature environments is suppressed. Alternatively, one aspect aims to provide positive electrode active material particles or composite oxides in which the decrease in discharge capacity during charge-discharge cycles is suppressed. Alternatively, one aspect aims to provide positive electrode active material particles or composite oxides in which the crystal structure is not easily disrupted even after repeated charge-discharge. Alternatively, one aspect aims to provide positive electrode active material particles or composite oxides with a large discharge capacity. Alternatively, one aspect aims to provide a secondary battery with high safety or reliability, an electronic device having said secondary battery, or a vehicle having said secondary battery.
[0013] Furthermore, one aspect of the present invention aims to provide positive electrode active material particles, composite oxides, energy storage devices, or methods for producing the same.
[0014] Furthermore, the description of these problems does not preclude the existence of other problems. Moreover, one aspect of the present invention does not need to solve all of these problems. It is possible to extract other problems from the description, drawings, and claims. [Means for solving the problem]
[0015] One aspect of the present invention is a lithium-ion secondary battery having a positive electrode and a negative electrode, wherein the positive electrode has positive electrode active material particles, the positive electrode active material particles contain lithium, cobalt, oxygen, magnesium, fluorine, nickel, and aluminum, the interior of the positive electrode active material particles has a layered rock salt type crystal structure with space group R-3m, and the positive electrode active material particles have edge regions arranged in the following order from the interior to the exterior of the positive electrode active material particles: a region of layered rock salt type crystal structure, a region of LiTiO2 type crystal structure with space group Fd-3m, and a region having a rock salt type crystal structure, and in STEM-EELS analysis of the region having the rock salt type crystal structure, there is a region in which the valence of cobalt is 2.54 or more and 2.69 or less.
[0016] Furthermore, in the above, when the arrangement of bright spots on the surface of the positive electrode active material particles observed in the cross-sectional HAADF-STEM image of the edge region is defined as the first row, it is preferable that at least a portion of the fourth to ninth rows located in the interior direction of the positive electrode active material particles has a region of LiTiO2 type crystal structure, and that the region of LiTiO2 type crystal structure has lithium sites in which magnesium and nickel are detected in STEM-EELS analysis, cobalt sites in which magnesium and nickel are detected, and cobalt sites in which nickel is detected.
[0017] Furthermore, in any one of the above, it is preferable to use lithium metal as the negative electrode, and to use an electrolyte solution which is a mixture of lithium hexafluoride phosphate, ethylene carbonate, diethyl carbonate, and 2 wt% vinylene carbonate, and to charge with a constant current of 0.5C (provided that 1.0C = 200 mA / g) until the voltage reaches 4.60V at 25°C, and then to charge with a constant voltage until the current reaches 0.05C, and then to analyze the positive electrode by XRD with CuKα1 rays in an argon atmosphere, the XRD pattern preferably has diffraction peaks at least at 2θ = 19.25 ± 0.12° and 2θ = 45.47 ± 0.10°. [Effects of the Invention]
[0018] According to one aspect of the present invention, positive electrode active material particles can be used in lithium-ion secondary batteries and promote the insertion and removal of lithium ions. Alternatively, positive electrode active material particles or composite oxides can be provided in which the decrease in discharge capacity during high-rate discharge is suppressed. Alternatively, positive electrode active material particles or composite oxides can be provided in which the decrease in discharge capacity in low-temperature environments is suppressed. Alternatively, positive electrode active material particles or composite oxides can be provided in which the decrease in discharge capacity during charge-discharge cycles is suppressed. Alternatively, positive electrode active material particles or composite oxides can be provided in which the crystal structure is less likely to collapse even after repeated charge-discharge cycles. Alternatively, positive electrode active material particles or composite oxides can be provided in which the discharge capacity is large. Alternatively, a safe or highly reliable secondary battery, an electronic device having said secondary battery, or a vehicle having said secondary battery can be provided.
[0019] Furthermore, according to one aspect of the present invention, positive electrode active material particles, composite oxides, energy storage devices, or methods for producing the same can be provided.
[0020] Furthermore, the description of these effects does not preclude the existence of other effects. Moreover, one aspect of the present invention does not necessarily have to possess all of these effects. Other effects will naturally become apparent from the description in the specification, drawings, and claims, and it is possible to extract other effects from the description in the specification, drawings, and claims. [Brief explanation of the drawing]
[0021] [Figure 1] Figure 1(A) is a cross-sectional view illustrating the internal structure of a secondary battery, and Figure 1(B) is a cross-sectional view illustrating the positive electrode and electrolyte of the secondary battery. [Figure 2] Figures 2(A) and 2(B) are cross-sectional views illustrating the positive electrode active material particles. [Figure 3] Figures 3(A) to 3(F) are cross-sectional views illustrating the positive electrode active material particles. [Figure 4] Figure 4(A) is a HAADF-STEM image, and Figure 4(B) is an ABF-STEM image. [Figure 5] Figures 5(A) and 5(B) are schematic diagrams of the LiTiO2 type crystal structure. [Figure 6] Figures 6(A) to 6(F) are schematic diagrams of the LiTiO2 type crystal structure. [Figure 7] Figure 7 illustrates the crystal structure of the positive electrode active material particles. [Figure 8] Figure 8(A) illustrates the charging depth and lattice constant of the positive electrode active material, Figure 8(B) illustrates the H1-3 type crystal structure, and Figure 8(C) illustrates the O3' type crystal structure. [Figure 9] Figure 9 shows the XRD pattern calculated from the crystal structure. [Figure 10] Figures 10(A) through 10(G) illustrate the spatial relationships of the distributions in EDX line analysis. [Figure 11] Figures 11(A) and 11(B) illustrate the method for producing positive electrode active material particles. [Figure 12] Figures 12(A) to 12(C) illustrate the method for producing positive electrode active material particles. [Figure 13] Figure 13(A) is an exploded perspective view of a coin-type rechargeable battery, Figure 13(B) is a perspective view of a coin-type rechargeable battery, and Figure 13(C) is a cross-sectional perspective view thereof. [Figure 14] Figure 14(A) shows an example of a cylindrical secondary battery. Figure 14(B) shows an example of a cylindrical secondary battery. Figure 14(C) shows an example of multiple cylindrical secondary batteries. Figure 14(D) shows an example of an energy storage system with multiple cylindrical secondary batteries. [Figure 15] Figures 15(A) and 15(B) show the external appearance of a secondary battery. [Figure 16] Figures 16(A) to 16(C) illustrate the method for manufacturing a secondary battery. [Figure 17] Figure 17(A) shows an electric bicycle, Figure 17(B) shows a secondary battery for an electric bicycle, and Figure 17(C) is a diagram illustrating a scooter. [Figure 18]Figures 18(A) through 18(E) illustrate an example of an electronic device. [Figure 19] Figure 19(A) shows an example of a wearable device, Figure 19(B) shows a perspective view of a wristwatch-type device, and Figure 19(C) is a diagram illustrating the side view of a wristwatch-type device. [Figure 20] Figure 20 shows a cross-sectional HAADF-STEM image of the positive electrode active material particles. [Figure 21] Figures 21(A) and 21(B) illustrate the results of cross-sectional STEM-EDX analysis of positive electrode active material particles. [Figure 22] Figures 22(A) and 22(B) illustrate the results of cross-sectional STEM-EDX analysis of positive electrode active material particles. [Figure 23] Figures 23(A) and 23(B) are graphs illustrating the results of the XPS analysis. [Figure 24] Figures 24(A) and 24(B) are graphs illustrating the results of the discharge rate test. [Figure 25] Figures 25(A) and 25(B) are graphs illustrating the XRD analysis results of the positive electrode under high-voltage charging conditions. [Figure 26] Figure 26(A) is a cross-sectional HAADF-STEM image of the positive electrode active material particles, and Figure 26(B) is a black and white inverted version of the cross-sectional HAADF-STEM image. [Figure 27] Figures 27(A) and 27(B) illustrate the results of cross-sectional STEM-EELS analysis of positive electrode active material particles. [Figure 28] Figure 28 illustrates the results of cross-sectional STEM-EELS analysis of positive electrode active material particles. [Figure 29] Figure 29(A) is a cross-sectional HAADF-STEM image of the positive electrode active material particles, and Figure 29(B) is a valence mapping image of cobalt in the positive electrode active material particles. [Figure 30] Figure 30 is a graph showing the valence state of cobalt in the depth direction of the positive electrode active material particles. [Figure 31]Figure 31(A) is a diagram illustrating the method for calculating the valence of cobalt, and Figure 31(B) is a diagram illustrating the region where the proportion of rock salt-type crystal structures was calculated. [Modes for carrying out the invention]
[0022] The following describes embodiments for carrying out the present invention with reference to drawings and other illustrations. However, the present invention is not limited to the following embodiments. It is possible to modify the embodiments for carrying out the invention without departing from the spirit of the present invention.
[0023] In this specification, space groups are expressed using international notation (or Hermann-Mauguin notation) Short notation. Crystal planes and crystal directions are expressed using Miller indices. In crystallography, space groups, crystal planes, and crystal directions are expressed by superscripting numbers, but in this specification, due to formatting constraints, a minus sign (-) may be placed before the number instead of a superscript. Individual orientations indicating directions within a crystal are represented by [ ], collective orientations indicating all equivalent directions are represented by < >, individual crystal planes are represented by ( ), and collective planes with equivalent symmetry are represented by {}. Furthermore, for ease of understanding the structure, trigonal crystals represented by space group R-3m are generally represented as a composite hexagonal lattice, and in this specification, unless otherwise specified, space group R-3m will be represented as a composite hexagonal lattice. In addition to (hkl), (hkil) may also be used as Miller indices, where i is -(h+k).
[0024] In this specification, the term "particle" is not limited to spherical shapes (circular cross-sections), but may also refer to individual particles with elliptical, rectangular, trapezoidal, triangular, rounded quadrilateral, or asymmetrical cross-sections, and individual particles may also have irregular shapes.
[0025] Furthermore, the theoretical capacity of the positive electrode active material refers to the amount of electric charge when all the insertable and detachable lithium in the positive electrode active material has been detached. For example, the theoretical capacity of LiCoO2 is 274 mAh / g, the theoretical capacity of LiNiO2 is 275 mAh / g, and the theoretical capacity of LiMn2O4 is 148 mAh / g.
[0026] Furthermore, the amount of lithium remaining in the positive electrode active material can be determined by x in the composition formula, for example, Li x This is denoted by x in MO2. M represents a transition metal, and unless otherwise specified in this specification, M is cobalt and / or nickel. In the case of the positive electrode active material in a lithium-ion secondary battery, x can be expressed as x = (theoretical capacity - charging capacity) / theoretical capacity. For example, Li x When a lithium-ion secondary battery using CoO2 as the positive electrode active material is charged to a charge capacity of 219.2 mAh / g, Li 0.2 CoO2 or x = 0.2 can be expressed as Li x When x in MO2 is small, it means, for example, 0.1 <x≦0.24をいう。
[0027] When properly synthesized lithium cobalt oxide, before being used as the positive electrode, approximately satisfies the stoichiometric ratio, it is LiCoO2 and x=1. Similarly, lithium cobalt oxide contained in a lithium-ion secondary battery after discharge is also LiCoO2 and can be said to be x=1. The state after discharge (discharge state) referred to here is, for example, a state where the voltage is 3.0V or 2.5V or less with a current of 100mA / g or less.
[0028] When determining the value of current per unit weight of positive electrode active material, if the weight of positive electrode active material contained in the positive electrode is unknown, the weight of positive electrode active material can be determined by the analysis described below. Generally, a positive electrode has a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer has positive electrode active material, a binder, and a conductive material. If the positive electrode is a coated electrode in which the positive electrode active material layer is coated on the metal foil of the positive electrode current collector, the positive electrode current collector and the positive electrode active material layer can be easily separated. Therefore, the weight ratio of the positive electrode current collector and the positive electrode active material layer in the positive electrode can be calculated by separating the positive electrode current collector and the positive electrode active material layer and measuring their weights. In addition, the weight of positive electrode active material contained in the positive electrode active material layer can be calculated by determining the weight ratio of positive electrode active material, binder, and conductive material through analysis.
[0029] For analyzing the weight ratio of positive electrode active material in a positive electrode active material layer, thermogravimetric differential thermal analysis (TG-DTA) can be used, for example. Specifically, using the positive electrode active material layer as a sample, analysis is performed in an inert atmosphere using TG-DTA, followed by analysis in an oxygen-containing atmosphere. By measuring the weight change in each analysis, the weight ratio of positive electrode active material, binder, and conductive material in the positive electrode active material layer can be calculated. For example, in an inert atmosphere, the temperature is raised from 25°C to 600°C at a rate of 20°C / min, and then the temperature is lowered from 600°C to 300°C at a rate of 20°C / min, and the weight loss is measured. This weight loss in the analysis in an inert atmosphere can be considered to be due to the decomposition of organic compounds such as PVDF used as a binder. Furthermore, as an analysis in an oxygen-containing atmosphere, for example, after the analysis in the inert atmosphere described above, the weight loss is measured when the temperature is raised from 300°C to 800°C at a rate of 20°C / min in an 80% He and 20% O2 atmosphere. This weight loss in the analysis in an oxygen-containing atmosphere can be considered to be mainly due to the combustion of the conductive material composed of carbon. In this way, the weight ratio of the positive electrode active material in the positive electrode active material layer can be determined.
[0030] Li x The charging and / or discharging capacities used to calculate x in MO2 should preferably be measured under conditions with little or no influence from short circuits and / or decomposition of the electrolyte. For example, data from lithium-ion secondary batteries that have experienced a sudden change in capacity, which is thought to be due to a short circuit, should not be used to calculate x.
[0031] Furthermore, the space group of the positive electrode active material, etc., is identified by XRD, electron diffraction, neutron diffraction, etc. Therefore, in this specification, "belonging to a certain space group," "being part of a certain space group," or "being a certain space group" can be rephrased as "being identified to a certain space group."
[0032] Furthermore, if the anion has a structure in which three layers are stacked with a slight offset from each other, such as ABCABC, it will be called a cubic close-packed structure. Therefore, the anion does not have to be strictly a cubic lattice. At the same time, since real crystals always have defects, the analytical results do not necessarily conform to theory. For example, in FFT (Fast Fourier Transform) patterns such as electron diffraction patterns or TEM (Transmission Electron Microscope) images, spots may appear at positions slightly different from the theoretical positions.
[0033] In this specification and other documents, positive electrode active material particles may be referred to as positive electrode active material, composite oxide, positive electrode material, positive electrode material, positive electrode material for secondary batteries, positive electrode material for lithium-ion secondary batteries, etc.
[0034] Furthermore, when describing the characteristics of individual particles in the following embodiments, it is not necessary for all particles to possess those characteristics. For example, if 50% or more, preferably 66% or more, and more preferably 90% or more of three or more randomly selected positive electrode active material particles possess those characteristics, it can be said that this is sufficient to improve the properties of the positive electrode active material and the secondary battery having it.
[0035] Unless otherwise specified, the materials of a secondary battery (positive electrode active material particles, negative electrode active material, electrolyte, separator, etc.) will be described in their state before degradation. Note that a decrease in discharge capacity due to aging and burn-in treatments during the secondary battery manufacturing process is not considered degradation. For example, a secondary battery consisting of a single cell or a battery pack can be considered in its pre-degradation state if it has a discharge capacity of 97% or more of its rated capacity. The rated capacity for secondary batteries for portable devices conforms to JIS C 8711:2019. For secondary batteries other than those specified above, the rated capacity conforms to various JIS and IEC standards, including those for electric vehicle propulsion and industrial use, not limited to the above JIS standard.
[0036] In this specification, the state of a secondary battery before material degradation is referred to as the initial product or initial state, and the state after degradation (the state in which the discharge capacity is less than 97% of the rated capacity of the secondary battery) may be referred to as a used product or in use, or a used product or a used state.
[0037] In this specification, the (001) plane and the (003) plane, among others, may be collectively referred to as the (00l) plane. In this specification, the (00l) plane may also be referred to as the C plane, basal plane, etc. Furthermore, lithium in lithium cobalt oxide has a two-dimensional diffusion pathway. That is, the diffusion pathway of lithium can be said to exist along the plane. In this specification, the plane where the diffusion pathway of lithium is exposed, that is, the plane where lithium is inserted and removed (specifically, the plane other than the (00l) plane), may be referred to as the edge plane.
[0038] In this specification, secondary particles refer to particles formed by the aggregation of primary particles. Primary particles refer to particles that do not have visible grain boundaries. Single particles refer to particles that do not have visible grain boundaries. Single crystals refer to crystals in which grain boundaries do not exist within the particles, while polycrystalline crystals refer to crystals in which grain boundaries exist within the particles. Polycrystalline crystals can also be described as aggregates of multiple crystallites, and a grain boundary can be described as an interface between two or more crystallites. In polycrystalline crystals, it is preferable that the orientation of the crystallites is aligned.
[0039] In this specification, the phrase "A and / or B" may be used, but this is just one example of how it can refer to A alone, B alone, or A and B together.
[0040] A short circuit in a secondary battery can not only cause malfunctions in the charging and / or discharging operations of the secondary battery, but can also lead to overheating and ignition. To realize a safe secondary battery, it is desirable that short circuits be suppressed even at high charging voltages. The positive electrode of a battery according to one aspect of the present invention suppresses short circuits even at high charging voltages. Therefore, it is possible to create a battery that achieves both high discharge capacity and safety.
[0041] In this specification, ordinal numbers such as "first," "second," etc., are used to avoid confusion of constituent elements and do not indicate any order or rank, such as sequence or layering order. Even if an ordinal number is not used for a term in this specification, an ordinal number may be used in the claims to avoid confusion of constituent elements. Even if an ordinal number is used for a term in this specification, a different ordinal number may be used in the claims. Even if an ordinal number is used for a term in this specification, the ordinal number may be omitted in the claims.
[0042] (Embodiment 1) This embodiment describes a battery and positive electrode active material particles according to one aspect of the present invention.
[0043] [battery] A lithium-ion battery according to one aspect of the present invention comprises a positive electrode, a negative electrode, and an electrolyte. Furthermore, if the electrolyte includes an electrolyte solution, a separator is provided between the positive electrode and the negative electrode. In addition, a lithium-ion battery according to one aspect of the present invention may have an outer casing that covers at least a portion of the positive electrode, negative electrode, and electrolyte.
[0044] This embodiment will primarily describe the positive electrode and positive electrode active material particles of a battery according to one aspect of the present invention. The method for producing the positive electrode active material particles will be described in Embodiment 2. The details of the remaining components of the lithium-ion battery according to one aspect of the present invention will be described in Embodiment 3.
[0045] Figure 1(A) is a schematic cross-sectional diagram illustrating the internal structure of a lithium-ion battery 10. The lithium-ion battery 10 has a positive electrode 11, a negative electrode 12, and a separator 13. The positive electrode 11 has a positive electrode current collector 21 and a positive electrode active material layer 22 on the positive electrode current collector 21, and the negative electrode 12 has a negative electrode current collector 31 and a negative electrode active material layer 32. As shown in the figure, the positive electrode active material layer 22 and the negative electrode active material layer 32 face each other with the separator 13 in between. Although not shown in Figure 1(A), the electrolyte is contained in the voids of the positive electrode active material layer 22, the voids of the separator 13, and the voids of the negative electrode active material layer 32.
[0046] Although Figure 1(A) shows one positive electrode 11, one negative electrode 12, and one separator 13, the lithium-ion battery according to one embodiment of the present invention is not limited to this structure. The lithium-ion battery according to one embodiment of the present invention may have a structure having two positive electrodes 11, two negative electrodes 12, and two separators 13, and may have even more electrodes stacked. Furthermore, the lithium-ion battery according to one embodiment of the present invention may have a wound structure instead of the stacked structure shown in Figure 1(A).
[0047] Figure 1(B) is an enlarged view of area A, which is enclosed by a dashed line in Figure 1(A).
[0048] The positive electrode active material layer 22 comprises positive electrode active material particles 100 (also called first positive electrode active material particles), second positive electrode active material particles 200, and a conductive material 41. Although not shown in the figures, the positive electrode active material layer 22 may also have a binder in addition to the positive electrode active material particles 100, second positive electrode active material particles 200, and conductive material 41.
[0049] Furthermore, the voids in the positive electrode active material layer 22 are preferably filled with the electrolyte 51, as shown in the figure. For example, it is preferable that 60% or more of the voids in the positive electrode active material layer 22 are filled with the electrolyte 51, more preferably 70% or more, more preferably 80% or more, more preferably 90% or more, more preferably 95% or more, and most preferably 99% or more. Note that the voids in the positive electrode active material layer 22 refer to the areas in the positive electrode active material layer 22 other than the solid components (positive electrode active material particles, conductive material, etc.).
[0050] [Positive electrode] The positive electrode 11 has a positive electrode current collector 21 and a positive electrode active material layer 22. The positive electrode active material layer 22 has positive electrode active material particles 100.
[0051] <Cathode active material particles 100> The positive electrode active material particles 100 have the function of taking in and releasing lithium ions during charging and discharging. The positive electrode active material particles used in one embodiment of the present invention can be made of a material that does not degrade much during charging and discharging (hereinafter also referred to as "charging and discharging"), even at high charging voltages (hereinafter also referred to as "high charging voltage"). Specifically, positive electrode active material particles (composite oxides) with a particle size (median diameter (D50)) of 10 μm or more and 50 μm or less, preferably 10 μm or more and 25 μm or less, obtained by the method for producing positive electrode active material particles described in Embodiment 2 can be used. The positive electrode active material particles 100 contain one or more of the additive elements X, Y, and Z. The additive elements X, Y, and Z will be described in detail in <Contained Elements>. Note that additive elements X, Y, and Z may be collectively referred to as additive element A.
[0052] The positive electrode active material particles 100 are the main constituent material of the positive electrode active material layer 22. The weight of the positive electrode active material particles 100 is preferably 50% or more, more preferably 60% or more, and even more preferably 70% or more, of the total weight of the solid components of the positive electrode active material layer 22. If the particle size of the positive electrode active material particles 100 is too small, the surface area becomes too large, which may lead to excessive reaction between the surface of the positive electrode active material particles and the electrolyte. Therefore, the particle size (median diameter (D50)) of the positive electrode active material particles is preferably 10 μm or larger. Furthermore, if the particle size of the positive electrode active material particles is larger than the thickness of the positive electrode active material layer 22 (described later), the particle density of the positive electrode active material layer 22 cannot be increased. Therefore, it is preferable that the largest particle size be 50 μm or less.
[0053] Particle size can be measured using a particle size analyzer (laser diffraction particle size distribution analyzer) that employs laser diffraction and scattering methods. D50 is the particle size at which the cumulative amount of the particle size distribution measurement results reaches 50%. Particle size measurement is not limited to laser diffraction particle size distribution measurement; the major axis of the particle cross-section may also be measured by analysis such as SEM (Scanning Electron Microscope) or TEM. As a method for measuring D50 from analysis such as SEM or TEM, for example, the particle sizes of 20 or more particles can be measured, a cumulative curve can be created, and the particle size at which the cumulative amount reaches 50% can be defined as D50.
[0054] Furthermore, it is preferable that all active material particles in the positive electrode active material layer 22 (i.e., positive electrode active material particles 100 and second positive electrode active material particles 200) have a small difference in charging depth during charging and discharging. This is because a large difference in charging depth can cause particles with a higher charging depth to degrade more easily. To mitigate the difference in charging depth, the conductive material 41 and / or binder in the positive electrode active material layer 22 do not necessarily have to be uniformly distributed. For example, particles near the current collector may have a higher charging depth, while particles further away from the current collector may have a lower charging depth. Therefore, it is preferable that the conductive material 41 in the region further away from the current collector is greater than in the region near the current collector.
[0055] Unless otherwise specified in this specification, "charging voltage" shall be expressed with reference to the potential of lithium metal. Furthermore, in this specification, "high charging voltage" refers to a charging voltage of, for example, 4.5V or higher, preferably 4.55V or higher, more preferably 4.6V or higher, 4.65V or higher, or 4.7V or higher.
[0056] Furthermore, as stated above, in this specification, "high charging voltage" is defined as 4.6V or higher based on the potential when the negative electrode is lithium metal. However, when the negative electrode is a carbon material (e.g., graphite), 4.5V or higher will be referred to as "high charging voltage." In short, in the case of a half-cell using lithium metal as the negative electrode, a charging voltage of 4.6V or higher will be called a high charging voltage, and in the case of a full-cell using a carbon material (e.g., graphite) as the negative electrode, a charging voltage of 4.5V or higher will be called a high charging voltage.
[0057] The positive electrode active material particles 100, which exhibit minimal degradation due to repeated charging and discharging at high charging voltages, will be explained using Figures 2(A) to 3(F).
[0058] Figures 2(A) and 2(B) are cross-sectional views of positive electrode active material particles 100 according to one embodiment of the present invention.
[0059] The positive electrode active material particles 100 have a layered rock salt type crystal structure belonging to space group R-3m, and a rock salt type crystal structure located on the surface side of the said layered rock salt type crystal structure. Furthermore, if a carbon-containing coating or the like exists outside the positive electrode active material particles 100, it can be said that the positive electrode active material particles 100 have a layered rock salt type crystal structure and a rock salt type crystal structure between the layered rock salt type crystal structure and the carbon-containing coating. Note that lithium cobalt oxide (LiCoO2) with a layered rock salt type crystal structure belonging to space group R-3m has a layered structure in which lithium layers and layers consisting of octahedrons of cobalt and oxygen (also called CoO2 layers) are alternately stacked.
[0060] As shown in Figure 2(A), the positive electrode active material particle 100 has a surface layer 100a and an interior layer 100b. The boundary between the surface layer 100a and the interior layer 100b is indicated by a dashed line in Figure 2(A).
[0061] The surface layer 100a of the positive electrode active material particles 100 refers to a region within 50 nm, more preferably within 35 nm, even more preferably within 20 nm, and most preferably within 10 nm, perpendicular or approximately perpendicular from the surface inward. Perpendicular or approximately perpendicular means an angle of 80° to 100°. Surfaces formed by cracks and / or fissures may also be considered the surface. The surface layer 100a is synonymous with the vicinity of the surface, the vicinity of the surface region, or the shell.
[0062] Furthermore, the region deeper than the surface layer 100a of the positive electrode active material particles is called the interior 100b. Interior 100b is synonymous with the interior region or core.
[0063] Furthermore, when the positive electrode active material particles 100 have a layered rock salt type crystalline structure of space group R-3m, the surface layer 100a has an edge region 100a1 and a basal region 100a2, as shown in Figure 2(B). In Figures 2(A) and 2(B), the line labeled (00l) represents the (00l) plane. Here, the edge region 100a1 has a surface exposed in a direction intersecting the (00l) plane, and the region extending inward perpendicularly or approximately perpendicularly from this surface within 50 nm, more preferably within 35 nm, even more preferably within 20 nm, and most preferably within 10 nm is called the edge region 100a1. Here, "intersecting" means that the angle formed by the perpendicular of the first plane ((00l) plane) and the normal of the second plane (the surface of the positive electrode active material particles 100) is 10 degrees or more and 90 degrees or less, more preferably 30 degrees or more and 90 degrees or less.
[0064] Furthermore, the basal region 100a2 has a surface parallel to the (00l) plane, and the region extending perpendicularly or substantially perpendicularly inward from this surface within 50 nm, more preferably within 35 nm, even more preferably within 20 nm, and most preferably within 10 nm is called the basal region 100a2. Here, "parallel" means that the angle between the perpendicular of the first plane ((00l) plane) and the normal of the second plane (the surface of the positive electrode active material particles 100) is between 0 degrees and 5 degrees, more preferably between 0 degrees and 2.5 degrees.
[0065] The surface of the positive electrode active material particles 100 refers to the surface of the composite oxide, including the surface layer 100a and the interior 100b. The positive electrode active material particles 100 need to contain a redox-capable transition metal M in order to maintain charge neutrality even when lithium ions are inserted and removed. In the positive electrode active material particles 100, the transition metal M is responsible for the redox reaction, and is redox-transformed as lithium ions are inserted and removed. When the positive electrode active material particles are subjected to analysis, a protective film may be applied to the surface, but this protective film is not included in the positive electrode active material particles. As a protective film, single-layer or multi-layer films of carbon, metal, oxide, resin, etc., may be used.
[0066] The position of the surface of the positive electrode active material particles 100 can be determined, for example, using a High-Angle Annular Dark Field (HAADF) STEM image. In HAADF-STEM images, contrast proportional to the square of the atomic number is obtained. Specifically, elements with larger atomic numbers have higher brightness (brighter) and elements with smaller atomic numbers have lower brightness (darker). Since lithium has a small atomic number of 3, lithium is observed with very low brightness in HAADF-STEM images, or it becomes difficult to observe lithium at all. The same applies to oxygen, which also has a small atomic number. On the other hand, transition metals M (e.g., cobalt) have large atomic numbers and are therefore observed with high brightness. Thus, in the HAADF-STEM image of the cross-section of the positive electrode active material particles 100, high-brightness spots are thought to correspond to transition metals M, and the position of the high-brightness spot closest to the outside can be considered the surface of the positive electrode active material particles 100. Note that the added element A is observed with brightness corresponding to its concentration and atomic number. For example, if a cobalt site is substituted with additive element A, which has a low atomic number, the brightness at that cobalt site will decrease as the concentration of additive element A increases. Similarly, if a lithium site is substituted with additive element A, which has a high atomic number, the brightness at that cobalt site will increase as the concentration of additive element A increases.
[0067] Furthermore, metal oxides (e.g., aluminum oxide) adhering to the surface of the positive electrode active material particles 100 that do not have lithium sites that can contribute to charging and discharging are not included in the positive electrode active material particles 100. Examples of such metal oxides include metal oxides whose crystal orientation does not match that of the interior 100b.
[0068] The agreement or approximate agreement of crystal orientations in two regions can be determined from TEM images, STEM images, HAADF-STEM images, ABF (Annular Bright Field)-STEM images, electron diffraction patterns, etc. It can also be determined from the FFT patterns of TEM images and STEM images. Furthermore, XRD and neutron diffraction can also be used as indicators.
[0069] In this specification, electrolytes, electrolyte decomposition products, organic solvents, binders, conductive materials, or compounds derived therefrom that are attached to the positive electrode active material particles 100 are not treated as part of the positive electrode active material particles 100, but are considered separate from the positive electrode active material particles 100.
[0070] <Contained elements> The positive electrode active material particles 100 contain lithium, cobalt, oxygen, and additive element A. Alternatively, the positive electrode active material particles 100 may contain lithium cobalt oxide (LiCoO2) with additive element A added. Therefore, the composition of lithium cobalt oxide is not strictly limited to Li:Co:O=1:1:2. Furthermore, it is preferable that the positive electrode active material particles 100 in one embodiment of the present invention have the crystalline structure described later.
[0071] The positive electrode active material particles of a lithium-ion secondary battery need to contain a redox-capable transition metal in order to maintain charge neutrality even when lithium ions are inserted and removed. In one embodiment of the present invention, it is preferable that the positive electrode active material particles 100 mainly use cobalt as the transition metal responsible for the redox reaction. In addition to cobalt, at least one or more selected from nickel and manganese may be used. It is preferable that the cobalt content of the transition metals in the positive electrode active material particles 100 is 75 atomic% or more, preferably 90 atomic% or more, and more preferably 95 atomic% or more, as this offers many advantages, such as being relatively easy to synthesize, easy to handle, and having excellent cycle characteristics.
[0072] Furthermore, if the cobalt content among the transition metals of the positive electrode active material particles 100 is 75 atomic percent or more, preferably 90 atomic percent or more, then compared to composite oxides such as lithium nickelate (LiNiO2) where nickel accounts for the majority of the transition metals, Li xThe stability of CoO2 is better when x is small. This is thought to be because cobalt is less affected by strain due to the Jahn-Teller effect than nickel. In transition metal compounds, the strength of the Jahn-Teller effect varies depending on the number of electrons in the d orbitals of the transition metal. In layered rock salt type composite oxides in which octahedral low-spin nickel(III) constitutes the majority of the transition metal, such as lithium nickelate, the Jahn-Teller effect is significant, and strain is likely to occur in the layers consisting of octahedra of nickel and oxygen. Therefore, there is a growing concern that the crystal structure may collapse during charge-discharge cycles. Also, nickel ions are larger than cobalt ions and are close in size to lithium ions. Therefore, in layered rock salt type composite oxides in which nickel constitutes the majority of the transition metal, such as lithium nickelate, there is a problem that cation mixing of nickel and lithium is likely to occur.
[0073] It is preferable to use one or more elements selected from magnesium, fluorine, nickel, aluminum, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, boron, barium, bromine, and beryllium as the additive element A in the positive electrode active material particles 100. Furthermore, when the total amount of additive element A in the positive electrode active material particles 100 is set to 100 atomic%, if the sum of transition metals among the additive element A is too high, the chargeable and dischargeable capacity of the positive electrode active material particles 100 may decrease. Therefore, it is preferable that the sum be less than 25 atomic%, more preferably less than 10 atomic%, and even more preferably less than 5 atomic%.
[0074] In other words, the positive electrode active material particles 100 can be one or more of the following: lithium cobalt oxide having magnesium, lithium cobalt oxide having magnesium and aluminum, lithium cobalt oxide having magnesium and nickel, lithium cobalt oxide having magnesium, aluminum and nickel, lithium cobalt oxide having magnesium and fluorine, lithium cobalt oxide having magnesium, fluorine and nickel, lithium cobalt oxide having magnesium, fluorine, nickel and aluminum, etc.
[0075] Furthermore, it can be said that one or more of the following can be used as positive electrode active material particles 100: positive electrode active material particles having cobalt, oxygen, and magnesium; positive electrode active material particles having cobalt, oxygen, magnesium, and aluminum; positive electrode active material particles having cobalt, oxygen, magnesium, aluminum, and nickel; positive electrode active material particles having cobalt, oxygen, magnesium, and fluorine; positive electrode active material particles having cobalt, oxygen, magnesium, fluorine, and aluminum; positive electrode active material particles having cobalt, oxygen, magnesium, fluorine, and nickel; and positive electrode active material particles having cobalt, oxygen, magnesium, fluorine, nickel, and aluminum.
[0076] It is preferable that the additive element A is solid-dissolved in the positive electrode active material particles 100. For example, when performing STEM-EDX line analysis, it is preferable that the position where additive element A begins to be detected in the depth direction is deeper than the position where transition metal M begins to be detected, i.e., located inside the positive electrode active material particles 100. In STEM-EDX line analysis in the depth direction, the position where an element begins to be detected is the position where the amount of characteristic X-rays detected (count) due to that element begins to increase continuously.
[0077] These added elements A make the crystal structure of the positive electrode active material particles 100 more stable, as will be described later.
[0078] Furthermore, the additive element A does not necessarily have to include magnesium, fluorine, nickel, aluminum, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, boron, barium, bromine, or beryllium.
[0079] Furthermore, by using positive electrode active material particles 100 that are substantially free of titanium, it becomes possible to enhance the effect of suppressing capacity degradation when repeatedly charging and discharging at high voltage. For example, the weight of titanium contained in the positive electrode active material particles 100 is preferably 600 ppm or less, and more preferably 100 ppm or less. Also, when the positive electrode active material particles 100 are analyzed by STEM-EDX, it is preferable that characteristic X-rays caused by titanium are not detected, that is, they are below the detection limit (for example, less than 0.3 atomic percent).
[0080] The surface layer 100a is the region where lithium ions first desorb during charging, and it is a region where the lithium concentration tends to be lower than in the interior 100b. Furthermore, the atoms on the surface of the positive electrode active material particles 100 in the surface layer 100a can be described as having some of their bonds broken. Therefore, the surface layer 100a is prone to instability, and it is a region where degradation of the crystal structure is likely to begin. On the other hand, if the surface layer 100a can be made sufficiently stable, Li x Even when x in CoO2 is small, for example, when x is 0.24 or less, the layered structure consisting of octahedrons of cobalt and oxygen in the interior 100b can be made less prone to breaking. Furthermore, the displacement of the layers consisting of octahedrons of cobalt and oxygen in the interior 100b can be suppressed.
[0081] To ensure a stable composition and crystal structure for the surface layer 100a, it is preferable that the surface layer 100a contains additive element A, and more preferably that it contains multiple additive element A. Furthermore, it is preferable that the surface layer 100a has a higher concentration of one or more selected additive element A than the interior layer 100b. It is also preferable that the one or more selected additive element A present in the positive electrode active material particles 100 have a concentration gradient. Moreover, it is more preferable that the distribution of the positive electrode active material particles 100 differs depending on the additive element A. For example, it is more preferable that the depth of the concentration peak from the surface differs depending on the additive element A. Here, "concentration peak" refers to the maximum concentration in the surface layer 100a or within 50 nm from the surface.
[0082] [distribution] The distribution of additive element A will now be explained. Figures 3(A) to 3(C) are enlarged views of the area around AB in Figure 2(B), illustrating the edge region 100a1 of the positive electrode active material particle 100. Figures 3(D) to 3(F) are enlarged views of the area around CD in Figure 2(B), illustrating the basal region 100a2 of the positive electrode active material particle 100.
[0083] For example, some of the additive elements A, such as magnesium, fluorine, silicon, phosphorus, and boron, preferably have a concentration gradient that increases from the interior 100b towards the surface, as shown by the density of the hatches in Figures 3(A) and 3(D). Additive elements having such a concentration gradient will be called additive elements X.
[0084] Another additive element A, such as aluminum or manganese, preferably has a concentration gradient as shown by the density of the hatches in Figures 3(B) and 3(E), and has a concentration peak in a region deeper than that of additive element X shown in Figures 3(A) and 3(D). The concentration peak may be located in the surface layer 100a or deeper than the surface layer 100a. For example, it is preferable to have a peak in a region of 5 nm to 30 nm from the surface inward. Additive elements having such a concentration gradient will be called additive element Y.
[0085] Another additive element A, such as nickel or barium, may be clearly present in the edge region 100a1, but substantially absent in the basal region 100a2, as shown by the presence or absence and density of hatches in Figures 3(C) and 3(F). Here, "clearly present" means that the characteristic X-ray energy spectrum of the additive element is detected in the cross-sectional STEM-EDX analysis of the positive electrode active material particle 100. "Substantially absent" means that the characteristic X-ray energy spectrum of the additive element is not detected in the cross-sectional STEM-EDX analysis of the positive electrode active material particle 100. This can also be said to mean that the additive element is below the detection limit in the STEM-EDX analysis. Additive elements with such a distribution will be called additive element Z.
[0086] For example, magnesium ions, which are one of the additive elements X, are divalent, and since magnesium ions are more stable when present at lithium sites than at cobalt sites in a layered rock-salt type crystal structure, they tend to enter lithium sites. Note that magnesium present at cobalt sites or lithium sites in the layered rock-salt type crystal structure is 6-coordinated with oxygen, and six oxygen atoms are present around each magnesium. The same applies to rock-salt type magnesium oxide (MgO). Therefore, magnesium oxide is, for example, Mg·n(O 1 / n ) (n=6). When magnesium is present at an appropriate concentration in the lithium sites of the surface layer portion 100a, the layered rock-salt type crystal structure can be easily maintained. This is presumed to be because the magnesium present at the lithium sites functions as a pillar that supports the CoO₂ layers with each other. In addition, the presence of magnesium allows Li x When x in CoO₂ is, for example, 0.24 or less, desorption of oxygen around magnesium can be suppressed. In addition, the presence of magnesium can be expected to increase the density of the positive electrode active material particles 100. Further, when the magnesium concentration in the surface layer portion 100a is high, it can also be expected that the corrosion resistance to hydrofluoric acid generated by the reaction of the electrolytic solution with water is improved. On the other hand, when the magnesium concentration is not sufficient, the surface layer portion 100a may be eroded by hydrofluoric acid and eluted into the electrolytic solution, making it impossible to sufficiently suppress the phase change of the inner portion 100b.
[0087] At appropriate concentrations, magnesium does not adversely affect lithium insertion and removal during charging and discharging, and the above benefits can be enjoyed. However, excessive magnesium may inhibit lithium insertion and removal. Furthermore, its effect on stabilizing the crystal structure may be reduced. This is thought to be because magnesium enters not only lithium sites but also cobalt sites. In addition, excess magnesium compounds (oxides or fluorides, etc.) that do not substitute for lithium or cobalt sites may segregate on the surface of the positive electrode active material particles, potentially becoming a resistive component of the secondary battery. Moreover, as the magnesium concentration of the positive electrode active material particles increases, the discharge capacity of the positive electrode active material particles may decrease. This is thought to be because too much magnesium enters the lithium sites, reducing the amount of lithium that contributes to charging and discharging.
[0088] Therefore, it is preferable that the total amount of magnesium contained in the positive electrode active material particles 100 is appropriate. For example, the number of magnesium atoms is preferably 0.001 times or more and 0.1 times or less the number of cobalt atoms, more preferably greater than 0.01 times and less than 0.04 times, and even more preferably about 0.02 times. The amount of magnesium contained in the total positive electrode active material particles 100 referred to here may be the value obtained by performing an elemental analysis of the entire positive electrode active material particles 100 using, for example, GD-MS (Glow Discharge Mass Spectrometry) or ICP-MS (Inductively Coupled Plasma-Mass Spectrometry), or it may be based on the value of the raw material composition during the manufacturing process of the positive electrode active material particles 100.
[0089] Furthermore, the thermal stability of the positive electrode active material particles 100 is improved due to the effect of aluminum, one of the additive elements Y. Therefore, the presence of aluminum as additive element Y improves the safety when the positive electrode active material particles 100 are used in secondary batteries. In addition, the positive electrode active material particles 100 can be made less susceptible to structural collapse even after repeated charging and discharging.
[0090] On the other hand, an excess of aluminum may negatively affect the insertion and removal of lithium.
[0091] Therefore, it is preferable that the total amount of aluminum in the positive electrode active material particles 100 is appropriate. For example, the total number of aluminum atoms in the positive electrode active material particles 100 is preferably 0.05% to 4%, preferably 0.1% to 2%, and more preferably 0.3% to 1.5% of the total number of cobalt atoms. Alternatively, 0.05% to 2% is preferred, or 0.1% to 4% is preferred. The total amount of aluminum in the positive electrode active material particles 100 referred to here may be, for example, the value obtained by elemental analysis of the entire positive electrode active material particles 100 using GD-MS, ICP-MS, etc., or it may be based on the value of the raw material composition during the manufacturing process of the positive electrode active material particles 100.
[0092] Furthermore, nickel can be present in both the cobalt site and the lithium site in lithium cobalt oxide. When nickel is present in the cobalt site of lithium cobalt oxide, the reaction potential for lithium ion insertion and deinsertion is lower compared to when cobalt is present in the cobalt site, which leads to an increase in discharge capacity and is therefore preferable.
[0093] Furthermore, the presence of nickel at the lithium sites can suppress the displacement of the layered structure consisting of octahedrons of cobalt and oxygen. Volume changes associated with charging and discharging are also suppressed. Additionally, the elastic modulus increases, meaning the positive electrode active material particles 100 become harder. This is presumed to be because the nickel present at the lithium sites also functions as pillars supporting the CoO2 layers. Therefore, it is desirable that the crystal structure becomes more stable, especially in charging conditions at high temperatures, such as 45°C or higher.
[0094] On the other hand, an excess of nickel is undesirable because it intensifies the distortion caused by the Jahn-Teller effect. Furthermore, an excess of nickel may adversely affect lithium insertion and removal.
[0095] Therefore, it is preferable that the total amount of nickel in the positive electrode active material particles 100 is appropriate. For example, the number of nickel atoms in the positive electrode active material particles 100 is preferably more than 0% and 7.5% or less of the number of cobalt atoms, preferably 0.05% to 4%, preferably 0.1% to 2%, and more preferably 0.2% to 1%. Alternatively, it is preferable that it is more than 0% and 4% or less. Alternatively, it is preferable that it is more than 0% and 2% or less. Alternatively, it is preferable that it is more than 0% and 7.5% or less. Alternatively, it is preferable that it is more than 0% and 2% or less. Alternatively, it is preferable that it is more than 0% and 7.5% or less. Alternatively, it is preferable that it is more than 0% and 4% or less. The amount of nickel shown here may be, for example, a value obtained by elemental analysis of the entire positive electrode active material particles using GD-MS, ICP-MS, etc., or it may be based on the value of the raw material blend during the process of manufacturing the positive electrode active material particles.
[0096] Furthermore, as shown in Figures 3(A) and 3(C), when the surface layer 100a contains both magnesium and nickel, divalent nickel may be able to exist more stably near divalent magnesium. Therefore, Li x Even when x in CoO2 is small, the elution of magnesium can be suppressed. Therefore, this can contribute to the stabilization of the surface layer 100a.
[0097] Furthermore, it is preferable to have multiple types of additive elements A with different distributions, such as additive elements X, Y, and Z, as this can stabilize the crystal structure over a wider area. For example, if the positive electrode active material particles 100 contain magnesium (one of additive elements X), aluminum (one of additive elements Y), and nickel (one of additive elements Z), it can stabilize the crystal structure over a wider area than when it contains only one or two of additive elements X, Y, and Z. Thus, when the positive electrode active material particles 100 contain three types of additive elements X, Y, and Z, surface stabilization can be sufficiently achieved by additive elements X such as magnesium and additive elements Z such as nickel, so additive element Y such as aluminum is not essential for the surface. Rather, it is preferable for aluminum to be widely distributed slightly inward from the surface. For example, it is preferable for aluminum to be continuously detected in the region from 1 nm to 25 nm in depth from the surface. It is preferable for aluminum to be widely distributed in this way as it can stabilize the crystal structure over a wider area.
[0098] Furthermore, when the additive element Z is abundantly present in the edge region 100a1 (also referred to as preferentially present or selectively present) as shown in Figures 3(C) and 3(F), it is preferable because it improves the stability of the crystal structure of the edge region 100a1 where lithium ions enter and exit the positive electrode active material particles 100 during charging and discharging of the lithium-ion battery. In addition, when the additive element Z has the distribution described above, it is preferable because it can minimize the effects of adding the additive element Z, such as a decrease in discharge voltage or a decrease in discharge capacity.
[0099] When the positive electrode active material particles 100 have multiple additive elements A as described above, the effects of each additive element A synergistically contribute to further stabilization of the surface layer 100a. In particular, the presence of magnesium, nickel, and aluminum is highly preferable as it is more effective in achieving a stable composition and crystal structure. Among these, it is preferable that the surface layer 100a of the positive electrode active material particles 100 has a region where magnesium is distributed closer to the surface than aluminum. Furthermore, in addition to the regions where magnesium and aluminum are distributed as described above, it is most preferable that the edge region 100a1 of the surface layer 100a of the positive electrode active material particles 100 has a region where the distribution of nickel and magnesium overlap.
[0100] <Crystal structure> <Li x When x in CoO2 is 1 > In one aspect of the present invention, the positive electrode active material particles 100 are in a discharge state, i.e., Li x In the case of x=1 in CoO2, it has a layered rock salt type crystal structure belonging to space group R-3m. Layered rock salt type composite oxides have high discharge capacity, possess a two-dimensional lithium ion diffusion pathway, and are suitable for lithium ion insertion / desorption reactions, making them excellent as positive electrode active material particles for secondary batteries. For this reason, it is particularly preferable that the interior 100b, which accounts for most of the volume of the positive electrode active material particle 100, has a layered rock salt type crystal structure.
[0101] On the other hand, in one aspect of the present invention, it is preferable that the surface layer 100a of the positive electrode active material particles 100 has a function to reinforce the layered structure of the interior 100b, which consists of an octahedron of transition metal M and oxygen, so that it does not break down even if lithium is removed from the positive electrode active material particles 100 due to charging. Alternatively, it is preferable that the surface layer 100a functions as a barrier film for the positive electrode active material particles 100. Alternatively, it is preferable that the surface layer 100a, which is the outer periphery of the positive electrode active material particles 100, reinforces the positive electrode active material particles 100. Reinforcement as used here means suppressing structural changes in the surface layer 100a and the interior 100b of the positive electrode active material particles 100, including the desorption of oxygen.
[0102] Therefore, it is preferable that the surface layer 100a has a different crystal structure from the interior 100b. Furthermore, it is preferable that the surface layer 100a has a more stable composition and crystal structure than the interior 100b. Specifically, it is preferable that at least a portion of the surface layer 100a of the positive electrode active material particles 100 in one embodiment of the present invention has a rock salt type crystal structure. Furthermore, it is preferable that at least a portion of the surface layer 100a has the characteristics of a spinel type crystal structure. Specifically, it is preferable that the positive electrode active material particles 100 have a crystal structure with a spinel type skeleton on the interior 100b side of the region having a rock salt type crystal structure. More specifically, it is preferable that it has the characteristics of a LiTiO2 type crystal structure with space group Fd-3m (ICSD Collection code 48128), which is a crystal structure similar to a spinel type crystal structure. It is even more preferable that the surface layer 100a has the characteristics of three crystal structures: layered rock salt type, LiTiO2 type with space group Fd-3m, and rock salt type. While crystal structures with a spinel-type skeleton are sometimes collectively referred to as spinel-type crystal structures, strictly speaking, a spinel-type crystal structure refers to a crystal structure such as Co3O4, which has metal atoms at the 8a and 16d sites in the Wyckoff position. Therefore, even if a crystal structure is described as having the characteristics of a spinel-type crystal structure in this specification, it does not necessarily mean that it is a structure that matches a spinel-type crystal structure like Co3O4. In addition, in this specification, a LiTiO2-type crystal structure with space group Fd-3m may be referred to as a spinel'-type crystal structure. The description of a LiTiO2-type crystal structure with space group Fd-3m in this specification is used to indicate that the symmetry of the atomic positions of the crystal structure is that of a LiTiO2-type crystal structure, and is not a description to specify the constituent elements, such as "consisting of lithium, titanium, and oxygen."
[0103] Furthermore, while it is preferable that some of the additive elements A, particularly magnesium, nickel, and aluminum, are present at higher concentrations in the surface layer 100a than in the interior 100b, it is also preferable that they be present randomly and dilutely in the interior 100b. When magnesium and aluminum are present at appropriate concentrations in the lithium sites of the interior 100b, it has the effect of making it easier to maintain a layered rock salt type crystal structure. Also, when nickel is present at an appropriate concentration in the interior 100b, the displacement of the layered structure consisting of octahedra of transition metal M and oxygen can be suppressed. In the case where both magnesium and nickel are present, divalent magnesium may be able to exist more stably near divalent nickel, so a synergistic effect of suppressing magnesium leaching can be expected. In addition, aluminum can be present in the cobalt sites in the layered rock salt type crystal structure. Since aluminum is a trivalent typical element and its valency does not change, lithium around aluminum does not easily move during charging and discharging. Therefore, aluminum and the lithium around it can function as pillars supporting the CoO2 layers, suppressing changes in the crystal structure. Furthermore, aluminum suppresses the leaching of surrounding cobalt, improving continuous charging resistance and / or storage resistance in a fully charged state. Also, because the Al-O bond is stronger than the Co-O bond, it can suppress the desorption of oxygen around the aluminum.
[0104] Furthermore, it is preferable that the crystal structure changes continuously from the interior 100b toward the surface, as shown in the concentration gradient of additive element A in Figures 3(A) to 3(E). Alternatively, it is preferable that the crystal orientation of the surface layer 100a and the interior 100b are roughly the same.
[0105] For example, it is preferable that the crystal structure changes sequentially from the interior 100b of the layered rock salt type toward the surface, from the characteristics of the layered rock salt type crystal structure to the characteristics of the spinel type crystal structure, and from the characteristics of the spinel type crystal structure to the characteristics of the rock salt type crystal structure. More specifically, it is preferable that the edge region 100a1 has a structure arranged in the following order from the interior 100b toward the outside of the positive electrode active material particle 100: a region of the layered rock salt type crystal structure, a region of the LiTiO2 type crystal structure, and a region having a rock salt type crystal structure. In other words, it is preferable that the edge region 100a1 has a structure arranged in the following order from the interior 100b toward the outside of the positive electrode active material particle 100: a region of the layered rock salt type crystal structure, a region of the spinel' type crystal structure, and a region having a rock salt type crystal structure. It is also preferable that this change in crystal structure is continuous. Furthermore, it is preferable that the crystal orientations of the three crystal structures—layered rock salt type, spinel' type, and rock salt type—are roughly the same.
[0106] In this specification, the layered rock salt crystal structure belonging to space group R-3m of a composite oxide containing lithium and a transition metal M refers to a crystal structure having a rock salt-type ionic arrangement in which cations and anions are arranged alternately, and in which the transition metal M and lithium are regularly arranged to form a two-dimensional plane. Therefore, two-dimensional diffusion of lithium is possible in this crystal structure. Defects such as vacancies in cations or anions may be present. Furthermore, strictly speaking, the layered rock salt crystal structure may have a distorted lattice structure of the rock salt crystal.
[0107] Furthermore, a rock salt-type crystal structure refers to a crystal structure that is cubic or can be considered cubic, in which cations and anions are arranged alternately. It is acceptable for there to be vacancies in either the cations or anions.
[0108] Furthermore, the characteristics of layered rock salt crystal structures, spinel crystal structures, and rock salt crystal structures can be determined by electron diffraction, TEM images, cross-sectional STEM images, etc.
[0109] Figure 4(A) is a cross-sectional HAADF-STEM image of the vicinity of the surface of the positive electrode active material particle 100, and Figure 4(B) is a cross-sectional ABF-STEM image of the vicinity of the surface of the positive electrode active material particle 100.
[0110] In cross-sectional HAADF-STEM images, when a layered rock salt crystal structure (e.g., LiCoO2) is observed from a direction perpendicular to the c-axis, layers with high-luminosity spots and layers with low-luminosity spots are observed alternately along the c-axis, as shown in the region labeled "layered rock salt type" in Figure 4(A). In Figures 4(A) and 4(B), the spots aligned in the direction indicated by the block arrows are called layers, and the spots aligned in the direction indicated by the dashed arrows are called rows. Similarly, in this specification, for the spots in a HAADF-STEM image of the edge region 100a1 of the positive electrode active material particle 100 observed from a direction perpendicular to the c-axis, the spots aligned in the direction perpendicular to the c-axis of the region having a layered rock salt structure are called layers. The spots aligned in the direction intersecting the layers are called rows, and the rows are selected as the arrangement of spots that is closest to parallel to the edge surface of the edge region 100a1.
[0111] Rock salt crystal structures (e.g., CoO) do not exhibit these features because there is no distinction between cation sites. Instead, only layers with rows of highly luminous spots are observed, as shown in the region labeled "rock salt type" in Figure 4(A).
[0112] In the row of lithium sites in Figure 4(A), a pattern is observed in which bright spots 110 with high brightness and regions 111 where no distinct bright spots are visible are arranged alternately. Furthermore, in the region labeled LiTiO2 type in Figure 4(A), layers consisting only of bright spots with high brightness and layers in which bright spots 110 and regions 111 where no distinct bright spots are visible alternately (block arrows in the figure) appear alternately in the row direction. When such characteristics are present, the region is said to have the characteristics of a spinel-type crystal structure. In addition, if the region with the characteristics of a spinel-type crystal structure is a LiTiO2-type crystal structure with space group Fd-3m, then in the region 111 where no distinct bright spots are visible in the HAADF-STEM image of Figure 4(A), atoms are present at Wyckoff position 16c, not Wyckoff position 8a.
[0113] When the region 111 in the HAADF-STEM image of Figure 4(A), where no clear bright spots are observed, is examined using the ABF-STEM image shown in Figure 4(B), no atomic-derived contrast was observed at the Wyckoff position 8a (solid circle in Figure 4(B)). In other words, in the positive electrode active material particles 100 of one embodiment of the present invention shown in Figures 4(A) and 4(B), the region labeled as LiTiO2 type can be determined to have a LiTiO2 type crystal structure with space group Fd-3m.
[0114] As shown in Figure 4(B), the ABF-STEM image exhibits similar characteristics to the HAADF-STEM image, although the brightness and contrast are reversed. The reason for this reversal is that in the HAADF-STEM image, strong bright spots appear at the locations of elements with high atomic numbers (e.g., cobalt), while in the ABF-STEM image, strong bright spots appear at the locations of elements with low atomic numbers (e.g., lithium).
[0115] The characteristics of a spinel-type crystal structure can also be determined by electron diffraction or TEM-FFT patterns.
[0116] In this specification, the row of metallic elements with atomic numbers greater than lithium (also called a row of bright spots or arrangement of bright spots) observed in a cross-sectional HAADF-STEM image of the positive electrode active material particle 100, that is closest to the surface, i.e., the outside, is referred to as the first row. The next row of metallic elements with atomic numbers greater than lithium, observed closer to the outside, is referred to as the second row. The same applies to the third row and subsequent rows. In other words, the rows proceed inward from the first row, second row, third row, fourth row, and so on.
[0117] For example, the first to third columns in the edge region 100a1 preferably have a rock salt type crystal structure. The fourth to ninth columns preferably have a LiTiO2 type crystal structure with space group Fd-3m. The tenth column and beyond preferably have a layered rock salt type crystal structure.
[0118] In the cross-sectional HAADF-STEM image of edge region 100a1, the region exhibiting characteristics of a spinel-type crystal structure is <110> Let's describe an example of observation from a specific direction. In this observation, in the region in question, the characteristics of the crystal structure change sequentially from those of a layered rock salt type to those of a spinel type, and then from those of a spinel type to those of a rock salt type, in the direction from the inside to the outside of the particle (depth direction). At this time, in the region with the characteristics of a layered rock salt type crystal structure, a first layer (lithium layer) without clear bright spots and a second layer (cobalt layer) adjacent to the first layer with a row of clear bright spots can be observed. If the viewpoint is shifted along the extension of the first layer in the direction from the inside to the outside of the particle (direction of the block arrow in Figure 4(A)), a characteristic can be observed in the region with the characteristics of a spinel type crystal structure, where bright spots 110 with high brightness and regions 111 without clear bright spots are arranged alternately.
[0119] Furthermore, in regions exhibiting spinel-type crystal structure characteristics in cross-sectional HAADF-STEM images, there are cases where a LiTiO2-type crystal structure with space group Fd-3m is present. The existence of a LiTiO2-type crystal structure with space group Fd-3m can be confirmed in ABF-STEM images, as mentioned above. In LiCoO2 with a LiTiO2-type crystal structure with space group Fd-3m, lithium (Li) is located at the 16c position, cobalt (Co) at the 16d position, and oxygen (O) at the 32e position, with the lithium at the 16c position being... <110> Because they are aligned linearly in the direction, this arrangement is preferable as it allows for smooth movement of lithium during charging and discharging. Furthermore, since the 16c and 16d positions are equivalent in terms of site symmetry, it is also possible to have cobalt at the 16c position, lithium at the 16d position, and oxygen at the 32e position.
[0120] Figure 5(A) shows a schematic diagram of the LiTiO2 type crystal structure. In Figure 5(A), for example, in region A, only the Wyckoff position 16c of space group Fd-3m exists. <110> These are positions that overlap in the direction, and in region A, lithium sites at position 16c are aligned. Also, for example, in regions B and C, the Wyckoff positions 16c and 16d of space group Fd-3m are <110> These are positions that overlap in the direction, and in regions B and C, the lithium site at position 16c and the cobalt site at position 16d are aligned. Also, for example, in region D, only the Wyckoff position 16d of space group Fd-3m is present. <110> These are positions that overlap in direction, and in region D, the cobaltites at position 16d are aligned.
[0121] Region A shown in Figure 5(A) is <110> This is a region where lithium sites are aligned in a particular direction, and lithium diffusion is possible in this direction. In a LiTiO2-type crystal structure, the lithium diffusion pathway exemplified in region A above exists in three dimensions. The three-dimensional lithium diffusion pathway of a LiTiO2-type crystal structure will be explained using Figure 5(B).
[0122] The diffusion pathway of lithium <110> Specifically, there are six directions:
[0110] , [0-11],
[0101] ,
[0011] , [10-1], and [1-10]. Figure 5(B) shows three of the six directions of lithium diffusion pathways in the three-dimensional direction of the LiTiO2 type crystal structure (direction 1, direction 2, and direction 3) as representative examples. Direction 1 is
[0110] , direction 2 is
[0011] , and direction 3 is [0-11]. In all of these directions, lithium sites are lined up in the thick lines labeled "Li" in the figure, indicating that there are lithium diffusion pathways in the three-dimensional direction.
[0123] Figures 6(A) to 6(F) show the six diffusion paths of lithium in more detail. Figures 6(A) to 6(F) show schematic diagrams of LiCoO2 with a LiTiO2-type crystal structure of space group Fd-3m, and the different lithium diffusion paths are indicated by dashed arrows. The arrow in Figure 6(A) indicates the
[0110] direction, the arrow in Figure 6(B) indicates the [0-11] direction, the arrow in Figure 6(C) indicates the
[0101] direction, the arrow in Figure 6(D) indicates the
[0011] direction, the arrow in Figure 6(E) indicates the [10-1] direction, and the arrow in Figure 6(F) indicates the [1-10] direction.
[0124] To determine whether a region exhibiting the characteristics of a spinel-type crystal structure is LiCoO2 with a space group Fd-3m and a LiTiO2-type crystal structure, for example, it can be determined by checking for the presence of an atom at position 8a in an ABF-STEM or HAADF-STEM image. If there is no atom at position 8a and an atom is present at position 16c, then it can be said to be a LiTiO2-type crystal structure with a space group Fd-3m. Alternatively, in a region where the characteristics of a spinel-type crystal structure are confirmed by a HAADF-STEM image, STEM-EELS (Electron Energy-Loss Spectroscopy) analysis can be performed. <110> If atomic columns of lithium aligned in a particular direction, atomic columns of lithium and cobalt aligned, and atomic columns of cobalt aligned are observed, then it can be said that the material is LiCoO2 with a LiTiO2-type crystal structure of space group Fd-3m. In other words, in regions where the characteristics of a spinel-type crystal structure are observed by HAADF-STEM imaging, there are two methods for determining whether a LiTiO2-type crystal structure of space group Fd-3m is present: the ABF-STEM method and the STEM-EELS method. Either of the above methods can be used to determine whether a LiTiO2-type crystal structure of space group Fd-3m is present.
[0125] In the region having the above-described LiTiO2-type crystal structure, it is preferable to have magnesium and nickel of additive element A at the lithium site (Wyckoff position 16c). It is also preferable to have nickel of additive element A at the transition metal M site (cobalt site, Wyckoff position 16d). By having magnesium and nickel of additive element A at these positions, the LiTiO2-type crystal structure can be stabilized and the elimination of oxygen can be suppressed.
[0126] Here, we compare the layered rock-salt structure with R-3m and the LiTiO2-type crystal structure with space group Fd-3m, and explain the simulation results focusing on cobalt, nickel, and titanium to determine which structure is more stable.
[0127] In LiCoO2, comparing the layered rock salt structure with R-3m and the LiTiO2-type crystal structure with space group Fd-3m, the layered rock salt structure with R-3m exhibits higher structural stability. Similarly, in LiNiO2, comparing the layered rock salt structure with R-3m and the LiTiO2-type crystal structure with space group Fd-3m, the LiTiO2-type crystal structure exhibits higher structural stability. Furthermore, in LiTiO2, comparing the layered rock salt structure with R-3m and the LiTiO2-type crystal structure with space group Fd-3m, the layered rock salt structure with R-3m exhibits higher structural stability. Note that all of the above calculations assume a charged state where all Li has been desorbed.
[0128] As described above, in the case of a LiTiO2 type crystal structure with space group Fd-3m, having nickel at the transition metal M site (Wyckoff position 16d) can stabilize the structure more than when cobalt or titanium is present at the same position.
[0129] Crystals with the characteristics of layered rock salt crystals, spinel crystals (e.g., LiTiO2 type), and rock salt crystals have anions that form a cubic close-packed structure (face-centered cubic lattice structure). It is also presumed that the O3' type crystals, which will be described later, have anions that form a cubic close-packed structure. Therefore, when the layered rock salt crystal structure, the LiTiO2 type crystal structure with space group Fd-3m, and the rock salt crystal structure are in contact with each other, there are crystal planes in which the orientation of the cubic close-packed structure composed of anions is aligned. For example, as shown in the schematic diagram of the crystal structure in Figure 7, it is possible to have structures in which the rock salt crystal structure, the LiTiO2 type crystal structure with space group Fd-3m, and the layered rock salt crystal structure are in contact with each other in such a way that the orientation of the cubic close-packed structure is aligned. Figure 7 shows the crystal structure of the edge region 100a1 of positive electrode active material particles 100 of one embodiment of the present invention, which will be considered from the examples described later. In the LiTiO2 type crystal structure of space group Fd-3m, as shown in Figure 7, Co 2+ And, Co 3+ and are arranged alternately.
[0130] The fact that the rock salt crystal structure, the LiTiO2 crystal structure with space group Fd-3m, and the layered rock salt crystal structure are aligned and in contact can also be explained as follows. The rock salt crystal structure and the LiTiO2 crystal structure with space group Fd-3m are cubic, and the anions in the {111} plane of the cubic crystal structure have a triangular lattice. The layered rock salt crystal structure has space group R-3m and is a rhombohedral structure, but to facilitate understanding of the structure, it can be represented by a composite hexagonal lattice, and the (0001) plane of the layered rock salt structure has a hexagonal lattice. The triangular lattice of the cubic {111} plane has a similar atomic arrangement to the hexagonal lattice of the (0001) plane of the layered rock salt structure. The consistency between the two lattices can be described as the orientation of the cubic close-packed structure being aligned.
[0131] In this LiTiO2-type crystal structure with space group Fd-3m, lithium can diffuse in three dimensions. Therefore, positive electrode active material particles 100 having a surface structure as shown in Figure 7, which mainly consists of a rock salt-type crystal structure region and a layered rock salt-type crystal structure region, are preferable because they have low lithium ion diffusion resistance and promote lithium ion insertion and deinsertion. Furthermore, using these positive electrode active material particles in a secondary battery is preferable because it suppresses the decrease in discharge capacity even during high-rate discharge and allows for the acquisition of a large discharge capacity.
[0132] However, the space group of the layered rock salt type is R-3m, which is different from the space group of the cubic crystal systems of the rock salt type and LiTiO2 type. Therefore, the Miller indices of the crystal planes that satisfy the condition for the orientation of the cubic close-packed structure to be aligned are different for the layered rock salt type crystal and for the rock salt type and LiTiO2 type with space group Fd-3m. In this specification, etc., it is said that in the layered rock salt type crystal structure, the LiTiO2 type crystal structure with space group Fd-3m, and the rock salt type crystal structure, when the orientation of the cubic close-packed structure composed of anions is aligned within 5 degrees, preferably within 2.5 degrees, the crystal orientation is said to be approximately the same. In other words, in the layered rock salt type crystal structure, the LiTiO2 type crystal structure with space group Fd-3m, and the rock salt type crystal structure, when the orientation of the cubic close-packed structure composed of anions is aligned within 5 degrees, preferably within 2.5 degrees, the crystal orientation is said to be approximately the same. Alternatively, in layered rock salt type, LiTiO2 type with space group Fd-3m, and rock salt type, when the orientation of the cubic close-packed structure composed of anions is aligned within 5 degrees, preferably within 2.5 degrees, these crystal structures are said to be aligned. The orientation of the cubic close-packed structure composed of anions is, for example, the direction indicated by the block arrows in Figures 4(A) and 4(B), and can also be called the layer direction.
[0133] [Ratio of rock salt structure in the surface layer] In one embodiment of the present invention, the positive electrode active material particles 100 have a region having a rock salt-type crystalline structure on the surface side of the particle in the surface layer 100a, as shown in Figure 7. This region having a rock salt-type crystalline structure can be considered to be a state in which a rock salt-type crystalline structure and a layered rock salt-type crystalline structure are mixed. Furthermore, this region having a rock salt-type crystalline structure can be said to be the region that comes into contact with the electrolyte when the positive electrode active material particles 100 are incorporated into a secondary battery.
[0134] When rock salt-type crystal structures and layered rock salt-type crystal structures are present together, the rock salt-type crystal structure portion is highly stable, thus suppressing the detachment of constituent elements of the positive electrode active material particles 100 into the electrolyte. Furthermore, the layered rock salt-type crystal structure portion can contribute to the inflow and outflow of lithium ions to and from the positive electrode active material particles 100.
[0135] When repeatedly charging and discharging at high voltage, a higher proportion of rock salt-type crystal structures in the region in contact with the electrolyte is preferable for greater stability. However, if the proportion is too high, it may hinder the movement of lithium ions to and from the positive electrode active material particles 100. For example, when analyzing regions with rock salt-type crystal structures using STEM-EELS analysis, the closer the valence of cobalt is to divalent, the higher the proportion of rock salt-type crystal structures.
[0136] In a positive electrode active material particle 100 according to one aspect of the present invention, when analyzing the region having a rock salt structure in the edge region 100a1, the valency of cobalt is preferably 2.40 to 2.75, and more preferably 2.54 to 2.69, within the range indicating a state in which salt-type crystalline structure and layered rock salt-type crystalline structure are mixed. When the cobalt in the region having a rock salt-type crystalline structure has the above valency, the stability during high-voltage charging can be enhanced, and lithium ions can enter and exit the positive electrode active material particle 100 sufficiently. It is preferable to use the average of the values calculated at multiple measurement points in the analysis region for the valency of cobalt. Therefore, when the valency of cobalt in STEM-EELS analysis is indicated in this specification, unless otherwise specified, it refers to the average valency of cobalt at multiple measurement points in the analysis region.
[0137] The valency of cobalt can be calculated as follows: First, obtain the energy spectrum from STEM-EELS analysis. Next, calibrate the obtained energy spectrum using the zeroloss peak (peak with zero energy loss). Next, remove the background from the energy spectrum by using the counts in the energy region lower than the Co L3 edge as the background region. Next, remove the effects of multiple scattering. Next, perform peak fitting using the standard spectra of divalent cobalt and trivalent cobalt. Finally, convert the ratio of the fit coefficients of divalent cobalt and trivalent cobalt obtained by peak fitting into the valency. Note that the standard spectrum of divalent cobalt can be obtained using, for example, cobalt(II) oxide (product code: 035-05651) manufactured by Fujifilm Wako Pure Chemical Corporation, and the standard spectrum of trivalent cobalt can be obtained using lithium cobalt(III) oxide (product code: 442704) manufactured by Sigma-Aldrich. However, the reagents used to obtain standard spectra are not limited to those listed above, and it is advisable to obtain them from reliable reagent manufacturers.
[0138] Furthermore, in one embodiment of the present invention, the positive electrode active material particle 100 has a structure in which, from the interior 100b toward the exterior of the positive electrode active material particle 100, a region of layered rock salt type crystal structure, a region of LiTiO2 type crystal structure with space group Fd-3m, and a region having a rock salt type crystal structure are arranged in that order. As described above, in the region of LiTiO2 type crystal structure with space group Fd-3m, lithium pathways exist in a three-dimensional direction. Therefore, even if the proportion of rock salt type crystal structure is increased in the region having a rock salt type crystal structure that is in contact with the electrolyte, it is possible to smoothly diffuse lithium ions into the interior 00b of the positive electrode active material particle 100.
[0139] <Li x The state where x is small during CoO2 > In one aspect of the present invention, the positive electrode active material particles 100 have the above-described distribution and / or crystal structure of the additive element A in the discharge state, resulting in Li x The crystal structure of CoO2 when x is small differs from that of conventional cathode active material particles. Here, x is small when it is 0.1 <x≦0.24をいうこととする。
[0140] Using lithium cobalt oxide (LiCoO2) without additive element A as an example, we will explain the changes in the crystal structure of conventional positive electrode active material particles.
[0141] Figure 8(A) shows Li x This shows the relationship between the x-value and the c-axis length of CoO2. In conventional lithium cobalt oxide, the crystal structure when the x-value is small is the H1-3 type crystal structure shown by the rhombic shape in the figure. The c-axis length decreases significantly during the phase transition to the H1-3 structure.
[0142] On the other hand, the positive electrode active material particles 100 in one aspect of the present invention are Li x In the CoO2, when x is small, the crystal structure is an O3' type crystal structure with small changes in c-axis length, as shown by the gray circle in Figure 8(A) and labeled as the O3' structure. Note that when x=1, the positive electrode active material particle 100 has the same R-3m O3 crystal structure as conventional lithium cobalt oxide.
[0143] The O3'-type crystal structure and the H1-3-type crystal structure exhibit a large change in the interplanar distance between CoO2 layers. Figure 8(B) shows the H1-3-type crystal structure, and Figure 8(C) shows the O3'-type crystal structure, showing the distance between the plane formed by oxygen in the CoO2 layer and the plane formed by oxygen in the next CoO2 layer in each structure. In the H1-3-type crystal structure, this interplanar distance is 2.77 Å and 3.06 Å, while in the O3'-type crystal structure, which will be discussed later, this interplanar distance is 3.13 Å. When this interplanar distance changes significantly, as in the H1-3-type crystal structure, there is a risk of degradation such as cracking occurring, especially in the surface layer where lithium diffusion pathways exist.
[0144] Therefore, repeated charging and discharging cycles that result in x being 0.24 or less cause the conventional lithium cobalt oxide crystal structure to break down. This breakdown of the crystal structure leads to a deterioration of the cycle characteristics. This is because the breakdown of the crystal structure reduces the number of sites where lithium can exist stably, and also makes it more difficult for lithium to be inserted and removed.
[0145] Conventional lithium cobalt oxide with a high x value of 0.24 or less, where many Li atoms have been removed, also readily releases oxygen. Along with the release of oxygen, cobalt is released into the cobalt. 3+ From Co 2+ This can lead to a phase change from a layered rock salt type crystal structure to a degraded spinel type crystal structure (e.g., LiCo2O4 or Co3O4). In one embodiment of the present invention, the LiTiO2 type crystal structure of space group Fd-3m, which has the characteristics of a spinel type crystal structure and exists between the region of layered rock salt type crystal structure and the region having a rock salt type crystal structure in the positive electrode active material particle 100, is a different crystal structure from the degraded spinel type crystal structure described above.
[0146] Furthermore, when oxygen is removed, cations such as cobalt that were bonded to the oxygen may dissolve into the electrolyte. If this progresses, it can lead to degradation in which holes are formed in the positive electrode active material particles, also known as pitting corrosion or pitting. At this time, strain and / or stress may occur in the positive electrode active material particles 100.
[0147] On the other hand, in the positive electrode active material particle 100, Li x The change in crystal structure between the discharge state where x is 1 and the state where x is 0.24 or less in CoO2 is less than that of conventional positive electrode active material particles. More specifically, the displacement of the CoO2 layer between the state where x is 1 and the state where x is 0.24 or less can be reduced. In one embodiment of the present invention, the positive electrode active material particle 100 has magnesium, one of the additive elements A, at a sufficient concentration in the surface layer 100a, even if lithium is desorbed from the positive electrode active material particle 100 and x becomes 0.24 or less, the phase change to the H1-3 type crystal structure can be suppressed due to the phase change suppression effect of magnesium. This can also be expressed, for example, as the rock salt type crystal structure containing MgO functioning as a wall that suppresses the displacement of the CoO2 layer in the interior 100b.
[0148] The terminology for the O3' type crystal structure is explained below. In one embodiment of the present invention, the positive electrode active material particle 100 at x=0.24 has a crystal structure belonging to the trigonal space group R-3m. This is because the symmetry of the CoO2 layer is the same as that of O3. Therefore, this crystal structure is referred to as the O3' type crystal structure.
[0149] In the O3' type crystal structure, the coordinates of cobalt and oxygen in the unit cell can be expressed as Co(0,0,0.5), O(0,0,x), within the range of 0.20≦x≦0.25. Furthermore, the lattice constant of the unit cell is given by the a-axis as 2.797≦a≦2.837(×10⁻¹⁰). -1 (nm) is preferred, and 2.807≦a≦2.827(×10 -1 nm) is more preferable. The c-axis is 13.681 ≤ c ≤ 13.881 (×10 -1 A value of n) is preferred, and 13.751 ≤ c ≤ 13.811 is more preferred.
[0150] There is almost no displacement of the CoO2 layer between the discharged state R-3m(O3) and the O3' type crystal structure. On the other hand, there is a large displacement of the CoO2 layer between the discharged state R-3m(O3) and the H1-3 type crystal structure, and as a result, the c-axis length is significantly reduced as shown in Figures 8(A) and 8(B).
[0151] Furthermore, the difference in volume per unit number of cobalt atoms between R-3m(O3) in the discharged state and the O3' type crystal structure is 2.5% or less, more specifically 2.2% or less, and typically 1.8%. On the other hand, when comparing per unit number of cobalt atoms, the difference in volume between the H1-3 type crystal structure and the O3 type crystal structure of R-3m in the discharged state exceeds 3.5%, and typically 3.9% or more.
[0152] The positive electrode active material particles 100 are Li x It has been confirmed that when x in CoO2 is between 0.15 and 0.24, it may have an O3' type crystal structure, and it is estimated that it also has an O3' type crystal structure when x is greater than 0.24 and less than or equal to 0.27. However, the crystal structure is Li x Since x in CoO2 is affected not only by the number of charge / discharge cycles, charge / discharge current, temperature, electrolyte, etc., x in the case of an O3' type crystal structure is not necessarily limited to the range of x mentioned above.
[0153] Therefore, the positive electrode active material particle 100 is Li x When x in CoO2 is greater than 0.1 and less than or equal to 0.24, the entire interior 100b of the positive electrode active material particle 100 does not necessarily have to have an O3' type crystal structure. It may contain other crystal structures, or a portion may be amorphous.
[0154] Also Li x To make x in CoO2 small, it is generally necessary to charge with a high charging voltage. x A state where x in CoO2 is small can be described as a state where it has been charged at a high charging voltage. For example, when CC / CV charging is performed at a voltage of 4.6V or higher relative to the potential of lithium metal in an environment of 25°C, the H1-3 type crystal structure appears in conventional positive electrode active material particles. Therefore, a charging voltage of 4.6V or higher relative to the potential of lithium metal can be said to be a high charging voltage.
[0155] Therefore, the positive electrode active material particles 100 of one aspect of the present invention are preferable because they can maintain a crystal structure with R-3m O3 symmetry even when charged at a high charging voltage, for example, a voltage of 4.6V or higher at 25°C. Furthermore, they are preferable because they can adopt an O3' type crystal structure when charged at a higher charging voltage, for example, a voltage of 4.65V or higher and 4.7V or lower at 25°C.
[0156] Even with the positive electrode active material particles 100, an H1-3 type crystal structure may only be observed when the charging voltage is further increased. Furthermore, as mentioned above, the crystal structure is affected by the number of charge / discharge cycles, charge / discharge current, temperature, electrolyte, etc., so even at lower charging voltages, for example, when the charging voltage is 4.5V or higher but less than 4.6V at 25°C, the positive electrode active material particles 100 of one embodiment of the present invention may take on an O3' type crystal structure.
[0157] Furthermore, when graphite is used as the negative electrode active material in a secondary battery, for example, the voltage of the secondary battery will decrease by the amount of the graphite's potential compared to the above. The potential of graphite is approximately 0.05V to 0.2V relative to the potential of lithium metal. Therefore, in the case of a secondary battery using graphite as the negative electrode active material, the potential of the positive electrode will be the secondary battery voltage minus the potential of graphite.
[0158] Note that the additive element A does not necessarily have to have a similar concentration gradient across the entire surface layer 100a of the positive electrode active material particles 100. An example of the distribution of additive element X near CD in Figure 2(B) is shown in Figure 3(D), and an example of the distribution of additive element Y near CD is shown in Figure 3(E).
[0159] Here, the region near CD has a layered rock salt crystal structure of R-3m, and the surface is (001) oriented. The distribution of additive element A in the surface layer 100a of a (001) oriented surface may differ from that of the surface layer 100a of other surfaces. For example, in the surface layer 100a of a (001) oriented surface, the distribution of one or more concentration peaks selected from additive element X and additive element Y may be limited to a shallower portion from the surface compared to the surface layer 100a of a surface other than a (001) oriented surface. Alternatively, the concentration of one or more elements selected from additive element X and additive element Y may be lower in the surface layer 100a of a (001) oriented surface compared to the surface layer 100a of other oriented surfaces. Alternatively, in the surface layer 100a of a (001) oriented surface, one or more elements selected from additive element X and additive element Y may be below the detection limit.
[0160] In the layered rock salt crystal structure of R-3m, cations are arranged parallel to the (001) plane. This indicates a structure in which CoO2 layers and lithium layers are alternately stacked parallel to the (001) plane. Therefore, the diffusion pathways for lithium ions also exist parallel to the (001) plane.
[0161] Since the CoO2 layer is relatively stable, the surface of the positive electrode active material particles 100 is more stable when it is oriented in the (001) direction. The main diffusion pathway of lithium ions during charging and discharging is not exposed on the (001) plane.
[0162] On the other hand, the lithium ion diffusion pathways are exposed on surfaces other than those oriented in (001). Therefore, the surfaces and surface layer 100a other than those oriented in (001) are important regions for maintaining the lithium ion diffusion pathways, but at the same time, they are prone to instability because they are the regions where lithium ions first desorb. For this reason, reinforcing the surfaces and surface layer 100a other than those oriented in (001) is extremely important for maintaining the overall crystal structure of the positive electrode active material particles 100.
[0163] Therefore, in another embodiment of the positive electrode active material particles 100 of the present invention, it is important that the distribution of the added element A in the surface layer 100a (edge region 100a1) on surfaces other than (001) is as shown in Figures 3(A) to 3(C). On the other hand, in the (001) surface and its surface layer 100a (basal region 100a2), the concentration of the added element A may be low or absent, as described above.
[0164] As described in Embodiment 2 below, in the manufacturing method in which high-purity LiCoO2 is produced and then the additive element A is mixed in and heated afterward, the additive element A spreads mainly through the diffusion pathway of lithium ions. Therefore, it is easy to set the distribution of the additive element A in the surface layer 100a (edge region 100a1) on surfaces other than (001) to a desirable range.
[0165] <Analysis method> A certain positive electrode active material particle, Li x Whether or not the positive electrode active material particle 100 of one embodiment of the present invention has an O3' type crystal structure when x in CoO2 is small depends on Li x The presence of positive electrode active material particles with a small x value in CoO2 can be determined by analyzing them using XRD, electron diffraction, neutron diffraction, electron spin resonance (ESR), nuclear magnetic resonance (NMR), etc.
[0166] XRD is particularly favored because it can analyze the symmetry of transition metals such as cobalt in the positive electrode active material particles with high resolution, compare the crystallinity and crystal orientation, analyze the periodic distortion of the lattice and crystallite size, and obtain sufficient accuracy even when measuring the positive electrode obtained by disassembling a secondary battery. The XRD measurement method is not particularly limited, and for example, a method can be used in which the incident angle of the X-rays is changed and the angle of the X-ray detector is set to be the same as the incident angle to measure the X-ray diffraction intensity (hereinafter also referred to as 2θ / θ continuous scan or θ-2θ method). In XRD by 2θ / θ continuous scan, diffraction peaks are obtained that reflect the crystal structure of the interior 100b of the positive electrode active material particles 100, which occupy most of the volume of the positive electrode active material particles 100.
[0167] When analyzing crystallite size using XRD, it is preferable to measure while excluding the influence of the orientation of positive electrode active material particles due to pressure, etc. For example, positive electrode active material particles can be extracted from the positive electrode obtained by disassembling a secondary battery, and measured after being prepared as a powder sample. Alternatively, as part of the analysis of the XRD diffraction pattern, waveform separation may be performed using a reference diffraction pattern of the O3' structure, a reference diffraction pattern of the H1-3 structure, etc., and the proportion of the O3' structure may be calculated.
[0168] Furthermore, while it is preferable to obtain the XRD diffraction pattern for calculating the crystallite size using only the positive electrode active material particles, it may also be obtained in the positive electrode state, which includes a current collector, binder, and conductive material in addition to the positive electrode active material particles. However, in the positive electrode state, the positive electrode active material particles may be oriented due to the effects of pressurization during the manufacturing process. If the orientation is strong, it may not be possible to accurately calculate the crystallite size of the positive electrode active material particles. Therefore, the XRD diffraction pattern can be obtained by methods such as removing the positive electrode active material layer from the positive electrode, removing some of the binder and other components from the positive electrode active material layer using a solvent, and then filling it into a sample holder.
[0169] For calculating crystallite size, for example, a Bruker D8 ADVANCE detector can be used, with the diffraction pattern obtained using CuKα1 as the X-ray source, 2θ between 15° and 90°, increment 0.005°, and a LYNXEYE XE-T detector, along with the literature value for lithium cobalt oxide, ICSD coll.code.172909. Crystal structure analysis can be performed using the Rietveld method with the DIFFRAC.TOPAS ver.6 crystal structure analysis software.
[0170] It is preferable to use the value of LVol-IB, which is the crystallite size corrected by the integral width criterion calculated using the above method, as the crystallite size.
[0171] Since lithium cobalt oxide is prone to (001) orientation, setting the Preferred orientation to (001) may yield a better GOF (goodness of fit). The March-Dollase function or Spherical Harmonics can be used as the Preferred orientation. Furthermore, in XRD analysis to determine crystallite size, the Rietveld method may not be suitable for determining crystallite size if the Preferred Orientation is less than 0.8 or greater than 1.2, as the sample orientation is too strong. In such cases where the Rietveld method is unsuitable, it is preferable to use other refinement techniques that yield a better GOF to determine the crystallite size. For example, the Whole-Powder Pattern Decomposition (WPPD) method can be employed.
[0172] Furthermore, with the full pattern resolution method, not only the crystallite size but also the lattice constant can be calculated without being affected by the orientation of the sample.
[0173] It is also important to note that simply adding element A may not result in the formation of an O3' type crystal structure. For example, even if lithium cobalt oxide has magnesium and fluorine, or lithium cobalt oxide has magnesium and aluminum, the structure may differ depending on the concentration and distribution of element A. x There are two cases in CoO2: one where x is 0.24 or less and the O3' type crystal structure accounts for more than 60%, and another where the H1-3 type crystal structure accounts for more than 50%.
[0174] Furthermore, even with the positive electrode active material particles 100 according to one aspect of the present invention, if x is too small, such as 0.1 or less, or under conditions where the charging voltage exceeds 4.9V, an H1-3 type or trigonal O1 type crystal structure may occur. Therefore, in order to determine whether or not the positive electrode active material particles 100 are according to one aspect of the present invention, analysis of the crystal structure, including XRD, and information such as charging capacity or charging voltage are necessary.
[0175] However, positive electrode active material particles with a small x value may undergo a change in crystal structure when exposed to air. For example, they may change from an O3' type crystal structure to an H1-3 type crystal structure. Therefore, it is preferable to handle all samples used for crystal structure analysis in an inert atmosphere such as an argon atmosphere.
[0176] On the other hand, even when handled in an argon atmosphere, the crystal structure of the positive electrode after disassembling a secondary battery may change over time. Therefore, it is preferable to employ a method that allows for rapid measurement as needed. It is also preferable to pre-dry a sealable sample holder for measurement in an argon atmosphere and to thoroughly remove any water adsorbed inside the sealed container. As a drying method, for example, it is preferable to use a vacuum drying oven and perform the process at a reduced pressure environment and 35°C for 12 hours.
[0177] In the case of XRD, the detector and / or measurement start angle can be appropriately changed to quickly observe the main peaks. If the crystal structure changes significantly over time, it is preferable to measure the main peak within 13 minutes of starting the measurement, for example.
[0178] Furthermore, whether the distribution of additive element A in the positive electrode active material particles is as described above can be determined by analyzing it using methods such as XPS, EDX, or EPMA (Electron Probe Microanalysis).
[0179] <Charging method> To determine whether the composite oxide is the positive electrode active material particle 100 according to one aspect of the present invention, charging can be performed, for example, by manufacturing a coin cell (CR2032 type, 20 mm in diameter and 3.2 mm in height) using the composite oxide as the positive electrode and lithium metal as the counter electrode. The coin cell comprises an electrolyte, a separator, a positive electrode can, and a negative electrode can.
[0180] More specifically, the positive electrode can be made by coating an aluminum foil positive electrode current collector with a slurry containing positive electrode active material particles, a conductive material, and a binder.
[0181] When a material other than lithium metal is used for the counter electrode, the voltage value of the secondary battery and the potential value of the positive electrode will differ. Unless otherwise specified, the voltage and potential in this specification refer to the potential of the positive electrode relative to the lithium metal counter electrode.
[0182] As the electrolyte, a mixed solvent containing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of EC:DEC = 3:7, with 1 mol / L lithium hexafluoride phosphate (LiPF6) added, and 2 wt% vinylene carbonate (VC) added as an additive can be used.
[0183] A 25 μm thick porous polypropylene film can be used as the separator.
[0184] The positive electrode and negative electrode cans can be made of stainless steel (SUS).
[0185] The coin cell manufactured under the above conditions is charged with an arbitrary voltage (e.g., 4.50V, 4.55V, 4.58V, 4.60V, 4.62V, 4.65V, 4.70V, 4.75V, or 4.80V). The charging method is not particularly limited as long as it can be charged at any voltage for a sufficient amount of time. In this specification, when approximately 4.6V is mentioned, it refers to a voltage between 4.58V and 4.62V. For example, when charging with CCCV, the current in CC charging can be between 20mA / g and 100mA / g. CV charging can be completed at a current between 2mA / g and 10mA / g. Because the diffusion of lithium ions is slow inside the positive electrode active material particles, it is desirable to charge with such small current values in order to observe the phase change of the positive electrode active material particles. The temperature should be 25°C or 45°C. After charging in this manner, the coin cell can be disassembled in a glove box under an argon atmosphere and the positive electrode can be removed to obtain positive electrode active material particles with any charging capacity. When performing various analyses afterward, it is preferable to seal the removed positive electrode in an argon atmosphere to suppress reactions with external components. For example, XRD can be performed by sealing the removed positive electrode in a sealable sample holder in an argon atmosphere. It is also preferable to remove the positive electrode as soon as possible after charging is complete and use it for analysis. To avoid the effects of self-discharge, it is preferable that the dismantling of the coin cell be completed within one hour after charging is complete, and more preferably within 30 minutes.
[0186] <xrd> The equipment and conditions for XRD measurement are not particularly limited. For example, XRD patterns can be measured with the following equipment and conditions: XRD device: Bruker D8 ADVANCE, X-ray: CuKα1, output: 40kV, 40mA, divergence slit: 0.6mm, detector: LYNXEYE XE-T, scanning method: 2θ / θ continuous scan, measurement range (2θ): 15° to 90°, step width (2θ): 0.01° setting, counting time: 1 second / step, sample stage rotation: 15rpm.
[0187] If the sample to be measured is a powder, it can be set up by placing it in a glass sample holder or by sprinkling the sample onto a grease-coated silicon anti-reflective plate. If the sample to be measured is a positive electrode, the positive electrode can be attached to a substrate with double-sided tape, and the positive electrode active material layer can be set up to match the measurement surface required by the instrument. If the positive electrode active material layer is higher than the measurement surface required by the instrument, the diffraction pattern will shift overall to the higher angle side, and if it is lower, it will shift overall to the lower angle side. In this case, the shift in the diffraction pattern can be corrected using crystal structure analysis software or the like.
[0188] As shown in Figure 9, the O3' type crystal structure has diffraction peaks at 2θ = 19.25 ± 0.12° (19.13° to 19.37°) and 2θ = 45.47 ± 0.10° (45.37° to 45.57°). However, these peaks do not appear in the H1-3 type crystal structure. Therefore, Li x The fact that the positive electrode active material particles 100 of one embodiment of the present invention have diffraction peaks at 2θ = 19.25 ± 0.12° (19.13° to 19.37°) and 2θ = 45.47 ± 0.10° (45.37° to 45.57°) when x in CoO2 is small is a characteristic feature of the positive electrode active material particles 100 of the present invention.
[0189] Furthermore, when charging is performed with a voltage slightly lower than 4.60V (4.56V, 4.57V, 4.58V, or 4.59V) as the upper limit of the charging voltage, the above diffraction peaks appear shifted to the lower angle side. For example, when charging is performed with a charging voltage of 4.58V as the upper limit, the positive electrode active material particles 100 have diffraction peaks at 2θ = 18.85 ± 0.20° and 2θ = 45.15 ± 0.10°.
[0190] In one aspect of the present invention, the positive electrode active material particles 100 are Li x When x in CoO2 is small, it has an O3' type crystal structure, but not all of it has to be an O3' type crystal structure. It may contain other crystal structures, and part of it may be amorphous. However, when Rietveld analysis is performed on the XRD pattern, it is preferable that the O3' type crystal structure is 50 wt% or more, more preferably 60 wt% or more, and even more preferably 66 wt% or more. If the O3' type crystal structure is 50% or more, more preferably 60 wt% or more, and even more preferably 66 wt% or more, it is possible to obtain cathode active material particles with sufficiently excellent cycle characteristics.
[0191] <xps> In XPS (X-ray Photoelectron Spectroscopy), for inorganic oxides, using monochromatic aluminum Kα X-rays allows for analysis of regions from the surface to a depth of approximately 2 nm to 8 nm (usually less than 5 nm). Furthermore, narrow-scan analysis can be used to analyze the bonding state of elements. The quantitative accuracy of XPS is generally around ±1 atomic percent, and the detection limit is approximately 1 atomic percent, although this varies depending on the element.
[0192] In one embodiment of the present invention, it is preferable that the concentration of one or more selected additive elements A in the positive electrode active material particles 100 is higher in the surface layer 100a than in the interior 100b. This is equivalent to saying that it is preferable that the concentration of one or more selected additive elements A in the surface layer 100a is higher than the average concentration of the positive electrode active material particles 100 as a whole. For example, it can be said that it is preferable that the concentration of one or more selected additive elements A in the surface layer 100a, as measured by XPS, is higher than the average concentration of additive elements A in the positive electrode active material particles 100 as a whole, as measured by ICP-MS (inductively coupled plasma mass spectrometry) or GD-MS (glow discharge mass spectrometry). For example, it is preferable that the concentration of magnesium in at least a portion of the surface layer 100a, as measured by XPS, is higher than the average magnesium concentration of the positive electrode active material particles 100 as a whole. It is also preferable that the concentration of nickel in at least a portion of the surface layer 100a is higher than the average nickel concentration of the positive electrode active material particles 100 as a whole. Furthermore, it is preferable that the concentration of aluminum in at least a portion of the surface layer 100a is higher than the average concentration of aluminum in the entire positive electrode active material particle 100. It is also preferable that the concentration of fluorine in at least a portion of the surface layer 100a is higher than the average concentration of fluorine in the entire positive electrode active material particle 100.
[0193] In one embodiment of the present invention, the surface and surface layer 100a of the positive electrode active material particles 100 do not contain carbonates, hydroxyl groups, etc., that have been chemically adsorbed after the production of the positive electrode active material particles 100. Furthermore, electrolyte, binder, conductive material, or compounds derived therefrom that are attached to the surface of the positive electrode active material particles 100 are also excluded. Therefore, when quantifying the elements contained in the positive electrode active material particles, corrections may be made to exclude carbon, hydrogen, excess oxygen, excess fluorine, etc., which can be detected by surface analysis such as XPS. For example, XPS can separate the types of bonds through analysis, and corrections may be made to exclude CF bonds derived from the binder.
[0194] Before subjecting the samples to various analyses, the positive electrode active material particles 100 and the positive electrode active material layer 22 may be washed to remove electrolyte, binder, conductive material, and compounds derived therefrom that adhere to the surface of the positive electrode active material particles 100. In this case, lithium may leach into the cleaning agent (e.g., solvent) used for washing. On the other hand, since additive element A does not easily leach, the effect of washing on the concentration and atomic ratio of additive element A is very small. For washing, it is preferable to use a method that causes little damage to the samples such as the positive electrode active material particles 100 and the positive electrode active material layer 22. As a cleaning agent, for example, a solvent that can be used in an electrolyte can be used. For solvents that can be used in an electrolyte, refer to the description of organic solvents listed in <Electrolyte> below. Dimethyl carbonate (DMC) or acetonitrile can be suitably used as a cleaning agent. Alternatively, a solvent that can be used during wet mixing or grinding (e.g., N-methyl-2-pyrrolidone (NMP)) can also be used as a cleaning agent. Additionally, cleaning agents can be combined with ultrasonic cleaning or filtration.
[0195] Furthermore, the concentration of additive element A may be compared in ratio to cobalt. Using the ratio to cobalt is preferable because it reduces the influence of carbonates and the like that chemically adsorbed after the production of the positive electrode active material particles. For example, the ratio of the number of magnesium atoms to the number of cobalt atoms, Mg / Co, as determined by XPS analysis, is preferably 0.400 or more and 1.20 or less, more preferably 0.500 or more and 1.00 or less, more preferably 0.500 or more and 0.900 or less, and more preferably 0.500 or more and 0.700 or less.
[0196] Furthermore, for example, the ratio of nickel atoms to cobalt atoms (Ni / Co) determined by XPS analysis is preferably 0.050 or more and 0.200 or less, more preferably 0.050 or more and 0.150 or less, more preferably 0.050 or more and 0.100 or less, and more preferably 0.050 or more and 0.070 or less.
[0197] Furthermore, for example, the ratio of aluminum atoms to cobalt atoms (Al / Co) determined by XPS analysis is preferably 0.010 or more and 0.100 or less, more preferably 0.010 or more and 0.050 or less, and even more preferably 0.010 or more and 0.040 or less.
[0198] Furthermore, for example, the ratio of fluorine atoms to magnesium atoms, F / Mg, determined by XPS analysis, is preferably 0.100 or more and 1.00 or less, more preferably 0.100 or more and 0.800 or less, more preferably 0.100 or more and 0.500 or less, more preferably 0.100 or more and 0.300 or less, and more preferably 0.100 or more and 0.200 or less.
[0199] The fact that the concentrations are within the range described above indicates that these additive elements A are not adhering to a narrow area on the surface of the positive electrode active material particles 100, but are widely distributed at a favorable concentration in the surface layer 100a of the positive electrode active material particles 100. In other words, the fact that the XPS analysis results of the positive electrode active material particles 100 are within the range described above means that the crystal structure is less likely to collapse even when repeated charging and discharging cycles occur where x is 0.24 or less, enabling excellent cycle characteristics. Furthermore, good lithium insertion and deinsertion are possible in the positive electrode active material particles 100, enabling excellent rate characteristics.
[0200] For XPS analysis, for example, monochromatic aluminum Kα rays can be used as the X-ray source. Furthermore, for energy resolution, it is preferable to use an XPS instrument with an energy resolution such that the full width at half maximum of the Ag3d5 / 2 peak (112 eV) in the XPS spectrum of an Ag sample is 1.0 eV ± 0.1 eV. The extraction angle can be, for example, 45°. Measurements can be performed using, for example, the following XPS instrument and measurement conditions. Measurement device: QuanteraII manufactured by ULVAC-PHI X-ray: Monochromatic Al Kα (1486.6 eV) Energy resolution: Full width at half maximum of the Ag3d5 / 2 peak is 1.0 eV ± 0.1 eV. Detection area: 100 μmφ Detection depth: Approximately 4nm to 5nm from the surface (extraction angle 45°) Measurement spectrum: Wide scan, narrow scan of each detected element
[0201] When XPS analysis is performed on positive electrode active material particles 100 according to one embodiment of the present invention, the peak indicating the bond energy between magnesium and other elements (Mg1s peak) is preferably 1303.0 eV or more and less than 1305.0 eV, and more preferably around 1304.0 eV. This value is different from the bond energy of magnesium fluoride, which is 1306.0 eV, and is close to the bond energy of magnesium oxide.
[0202] In XPS analysis of positive electrode active material particles 100 according to one aspect of the present invention, the measured XPS spectrum should be corrected so that the C1s peak matches a reference value (284.8 eV), that is, the entire spectrum should be shifted. This reduces the influence of differences in XPS instruments, measurement conditions, etc., on the XPS measurement.
[0203] Furthermore, in XPS analysis of positive electrode active material particles 100 according to one embodiment of the present invention, when analyzing the Mg1s peak and determining the ratio of peak components derived from O-Mg-O bonds, peak components derived from O-Mg-F bonds, and peak components derived from F-Mg-F bonds, it is preferable to have a peak component derived from O-Mg-O bonds. While peak components derived from O-Mg-F bonds may be present, it is preferable that they constitute 30% or less of the total three peak components, more preferably 20% or less, more preferably 10% or less, and even more preferably below the detection limit. Similarly, while peak components derived from F-Mg-F bonds may be present, it is preferable that they constitute 10% or less of the total, and even more preferably below the detection limit.
[0204] In other words, in XPS analysis of positive electrode active material particles 100 according to one aspect of the present invention, when the ratio of peak components derived from O-Mg-O bonds, peak components derived from O-Mg-F bonds, and peak components derived from F-Mg-F bonds is analyzed, it is preferable that the peak component derived from O-Mg-O bonds is 70% or more, more preferably 80% or more, even more preferably 90% or more, and particularly preferably 100%. However, when performing a similar analysis on the positive electrode after incorporating the positive electrode active material particles 100 according to one aspect of the present invention into a secondary battery, the peak component derived from O-Mg-O bonds may be detected due to the influence of fluorine contained in the binder or electrolyte.
[0205] This section describes a method for analyzing the Mg1s peak in XPS spectra obtained through XPS analysis. In analyzing the Mg1s peak, the peak component derived from the O-Mg-O bond is designated as Fit Peak 1, the peak component derived from the O-Mg-F bond as Fit Peak 2, and the peak component derived from the F-Mg-F bond as Fit Peak 3. By synthesizing these three fit peaks, the ratio of peak synthesis that minimizes the difference between the resulting peak and the Mg1s peak in the XPS spectrum obtained through XPS analysis can be calculated. The area ratio of Fit Peak 1, Fit Peak 2, and Fit Peak 3 at this time can be assumed to represent the relative abundance of the O-Mg-O bond, O-Mg-F bond, and F-Mg-F bond, and the analysis results can be output accordingly.
[0206] In the XPS spectrum analysis method described above, the energy value at the maximum value (also called the peak top) of Fit Peak 1 (Ep1) can be referenced from the energy value at the maximum value of the Mg1s peak when MgO-coated LiCoO2 was measured separately as a standard sample. Similarly, the energy value at the maximum value of Fit Peak 3 (Ep3) can be referenced from the energy value at the maximum value of the Mg1s peak when magnesium fluoride (MgF2, for example, MGH18XB, purity 99.9% (3N) up) was measured separately as a standard sample. Furthermore, the energy value at the maximum value of Fit Peak 2 (Ep2) can be an intermediate value between Ep1 and Ep3. Also, Ep1 is located on the lower energy side compared to Ep3. The energy value at the maximum value of a peak is also called the peak position.
[0207] In XPS analysis of positive electrode active material particles 100 according to one embodiment of the present invention, the analysis result of the Mg1s peak being within the above preferred range can be determined from the peak position and the full width at half maximum of the peak. For example, the full width at half maximum of the Mg1s peak is preferably 1.0 eV or more and 3.0 eV or less, more preferably 1.0 eV or more and 2.8 eV or less, and particularly preferably 1.0 eV or more and 2.6 eV or less. In the above, the peak position of the Mg1s peak is on the lower energy side than the energy value at the maximum value of the Mg1s peak when magnesium fluoride is measured separately as a standard sample.
[0208] <edx> It is preferable that one or more elements selected from the additive elements A present in the positive electrode active material particles 100 have a concentration gradient. More preferably, the depth of the concentration peaks from the surface differs depending on the additive elements A of the positive electrode active material particles 100. The concentration gradient of the additive elements A can be evaluated, for example, by exposing the cross-section of the positive electrode active material particles 100 using a FIB (Focused Ion Beam) and analyzing the cross-section using EDX, EPMA (Electron Probe Microanalysis), etc.
[0209] Among EDX analyses, EDX surface analysis refers to measuring while scanning within a region and evaluating that region in two dimensions. Line analysis refers to measuring while scanning linearly and evaluating the distribution of atomic concentration within positive electrode active material particles. Furthermore, sometimes line analysis refers to extracting data from a linear region from surface analysis. Finally, point analysis refers to measuring a region without scanning.
[0210] EDX surface analysis (e.g., elemental mapping) allows for the quantitative analysis of the concentration of additive element A in the surface layer 100a, interior 100b, and near grain boundaries of the positive electrode active material particles 100. The region near grain boundaries refers to the area within 10 nm of the grain boundary. Furthermore, EDX radiation analysis allows for the analysis of the concentration distribution and maximum value of additive element A. Analysis using thinned samples, such as STEM-EDX, is preferable because it allows for the analysis of the depth-direction concentration distribution from the surface towards the center of the positive electrode active material particles in a specific region, without being affected by the depth-direction distribution. Note that depth-direction analysis methods that remove the sample surface by sputtering, such as depth-direction SIMS (Secondary Ion Mass Spectrometry) analysis and depth-direction XPS analysis, do not yield the same results as STEM-EDX due to the influence of elemental indentation caused by the sputtering.
[0211] In STEM-EDX radiation analysis, due to the principle or measurement errors, the graph of the detected characteristic X-rays of an element may not show a steep change, making it difficult to precisely determine the surface. Therefore, when referring to the depth direction in STEM-EDX radiation analysis, the detected amount of characteristic X-rays of the transition metal M is considered to be equal to the average value M of the detected characteristic X-rays of the transition metal M inside the surface. AVE And the average value M of the detected characteristic X-rays of the above transition metal M in the background. BG The point where the sum of the two is 50%, or where the amount of oxygen characteristic X-rays detected is equal to the average value of the amount of oxygen characteristic X-rays detected inside O AVE And the average value of the detected characteristic X-rays of background oxygen O BG The reference point is the point at which the sum of the two values is 50%. Note that if the point at which the detected amount of characteristic X-rays of the transition metal M is 50% of the sum of the average detected amount of characteristic X-rays of the internal transition metal M and the average detected amount of characteristic X-rays of the background transition metal M is different from the point at which the detected amount of characteristic X-rays of oxygen is 50% of the sum of the average detected amount of characteristic X-rays of internal oxygen and the average detected amount of characteristic X-rays of background oxygen, it is thought to be due to the influence of oxygen-containing metal oxides, carbonates, etc. adhering to the surface, and therefore the point at which the detected amount of characteristic X-rays of the transition metal M is 50% of the average detected amount of characteristic X-rays of internal transition metal M AVE And the average value M of the detected characteristic X-rays of the above transition metal M in the background. BG The point at 50% of the sum of these can be adopted as the reference point. Also, in the case of positive electrode active material particles containing multiple transition metals M, the transition metal element M that has the highest amount of characteristic X-ray detection inside is selected. AVE and M BG The above reference points can be determined using this method.
[0212] The average value M of the detected characteristic X-rays of the above transition metal M in the background. BG For example, the average value M of the detected characteristic X-rays of the transition metal M can be determined by averaging the range of 2 nm or more, preferably 3 nm or more, outside the positive electrode active material particles, while avoiding the vicinity where the detection amount of characteristic X-rays of the transition metal M begins to increase. AVE The average value of the background characteristic X-ray O is obtained by averaging a range of 2 nm or more, preferably 3 nm or more, from a depth of 30 nm or more, preferably beyond 50 nm, in the region where the detection amount of characteristic X-rays of transition metal M and oxygen saturates and stabilizes, for example, from the region where the detection amount of characteristic X-rays of transition metal M begins to increase. BG and the average value of the amount of characteristic X-rays detected from the internal oxygen O AVE This can be calculated in a similar manner.
[0213] Furthermore, the surface of the positive electrode active material particles 100 in cross-sectional STEM images, etc., is defined as the boundary between the region where an image originating from the crystal structure of the positive electrode active material particles is observed and the region where it is not observed, and is the outermost region where atomic columns originating from the nuclei of metal elements with atomic numbers greater than lithium among the metal elements constituting the positive electrode active material particles are confirmed.
[0214] In STEM-EDX analysis, a peak refers to a convex shape that appears on the graph of characteristic X-ray intensity or concentration for each element. Peak intensity refers to the maximum value of characteristic X-ray intensity or concentration for each element. Peak position refers to the position of the maximum value of characteristic X-ray intensity or concentration for each element. Noise in STEM-EDX analysis can include measurements with a full width at half maximum (FWHM) below the spatial resolution (R), for example, R / 2 or less.
[0215] Scanning the same location multiple times under the same conditions can reduce the impact of noise. For example, the cumulative value obtained from two scans can be used as the detected value for each element. The number of scans is not limited to two; more scans can be performed, and the cumulative value of those scans can be used as the detected value for each element.
[0216] For elemental quantification in EDX analysis, a standardless quantification method can be employed, using the k-factor built into the analytical instrument and / or analytical software. When determining elemental concentrations from the quantification results, it is preferable that the elements included include those used in the target material, raw materials, and pre-analysis treatment, such as carbon, oxygen, fluorine, magnesium, aluminum, silicon, phosphorus, sulfur, calcium, titanium, iron, cobalt, nickel, and gallium—a total of 14 elements. Since the quantification calculation is performed so that the sum of the quantification concentrations of these elements equals 100%, these elements are also called the denominators.
[0217] STEM-EDX radiation analysis can be performed, for example, as follows: First, a protective film is deposited on the surface of the positive electrode active material particles. For example, carbon can be deposited using an ion sputtering system (Hitachi High-Tech MC1000).
[0218] Next, the positive electrode active material is thinned to prepare a STEM cross-sectional sample. For example, thinning can be performed using a FIB-SEM device (Hitachi High-Tech XVision200TBS). In this case, pickup is performed using an MPS (microprobing system), and it is preferable to finish the processing by gradually decreasing the acceleration voltage from high to low in the order of 30kV, 15kV, 5kV, and 2kV.
[0219] STEM-EDX radiation analysis can be performed using, for example, a STEM instrument (Hitachi High-Tech HF5000) and an OXFORD Ultim MAX TLE EDX detector (equipped with two detectors). During EDX radiation analysis, the emission current of the STEM instrument should be set to 7 μA to 10 μA, and the thinned sample should be measured in areas with little depth and unevenness. STEM-EDX radiation analysis involves performing EDX surface analysis to evaluate the measurement area in two dimensions, and then using analysis software to extract any desired area as EDX radiation analysis. The measurement magnification for EDX surface analysis should be set to a magnification where the measurement pitch of the line analysis is approximately 0.3 nm, for example, around 160,000x (320,000x on the screen display due to drift correction). The conditions for EDX surface analysis can be 256 x 256 pixels, 50 μsec dwell time, and approximately 400 frames (with a target of approximately 150,000 Co counts in the qualitative spectrum). Furthermore, the extraction conditions for EDX line analysis can be set to a line width of 256 pixels in order to detect more characteristic X-rays. In addition, EDX analysis allows for the arbitrary selection of either Netcount(Counts), which indicates the number of detected element counts, or atomic%, which is obtained by multiplying Netcount by the element-specific coefficient, the k factor.
[0220] STEM-EDX radiation analysis is not limited to the above-mentioned STEM instrument, but can also use other STEM instruments (JEOL JEM-ARM200F NEOARM) and EDX detectors (JEOL Dual SDD detector JED-2300T).
[0221] To achieve high spatial resolution in STEM-EDX analysis, a small beam diameter is preferable. The beam diameter in STEM-EDX analysis is preferably 0.3 nm or less, more preferably 0.2 nm or less, and even more preferably 0.1 nm or less. Furthermore, to increase the analytical sensitivity in STEM-EDX analysis, a high beam current is preferable. Therefore, it is preferable that the apparatus used for STEM-EDX analysis be equipped with a spherical aberration correction device (Cs collector) that can reduce the beam diameter and increase the beam current.
[0222] Furthermore, in positive electrode active material particles 100 having magnesium and fluorine as additive element A, it is preferable that the distribution of fluorine has a region that overlaps with the distribution of magnesium. For example, it is preferable that the difference in depth direction between the peak of fluorine concentration or detected amount and the peak of magnesium concentration or detected amount is within 10 nm, more preferably within 3 nm, even more preferably within 1 nm, and still more preferably within 0.5 nm.
[0223] Furthermore, in positive electrode active material particles 100 having nickel as additive element A, the peak of nickel concentration or detected amount in the surface layer 100a is preferably located on the surface of the positive electrode active material particle 100, or within a depth of 3 nm from the reference point toward the center, and more preferably within a depth of 1 nm. Furthermore, in positive electrode active material particles 100 having magnesium and nickel, the distribution of nickel is preferably in a region that overlaps with the distribution of magnesium. For example, the difference in depth between the peak of nickel concentration or detected amount and the peak of magnesium concentration or detected amount is preferably within 3 nm, and more preferably within 1 nm.
[0224] Furthermore, when the positive electrode active material particles 100 contain aluminum as additive element A, when EDX radiation analysis is performed, it is preferable that the peaks of concentration or detection amount of magnesium, nickel, or fluorine are closer to the surface than the peaks of concentration or detection amount of aluminum in the surface layer 100a. In other words, it is preferable that the peak of concentration or detection amount of aluminum in the surface layer 100a is located further inland than the peaks of concentration or detection amount of magnesium, nickel, or fluorine. For example, it is preferable that the peak of concentration or detection amount of aluminum is located on the surface of the positive electrode active material particles 100, or at a depth of 0.5 nm to 50 nm from a reference point toward the center, and more preferably at a depth of 5 nm to 50 nm.
[0225] Here, we will explain how to represent the positional relationships of elemental distributions when performing EDX radiation analysis, using Figures 10(A) to 10(G). Figures 10(A) to 10(F) are schematic diagrams showing the concentration distribution or detection amount distribution of the first element e1 and the second element e2. Figure 10(G) is a schematic diagram showing the concentration distribution or detection amount distribution of the first element e1, the second element e2, and the third element e3.
[0226] For example, if the concentration distribution or detection amount distribution of the first element e1 and the second element e2 is as shown in Figure 10(A), the position where the concentration or detection amount of the second element e2 is maximum is located further inside than the position where the concentration or detection amount of the first element e1 is maximum. Also, for example, if the concentration distribution or detection amount distribution of the first element e1 and the second element e2 is as shown in Figure 10(B), the position where the concentration or detection amount of the second element e2 is maximum is located further inside than the position where the concentration or detection amount of the first element e1 is maximum. Also, for example, if the concentration distribution or detection amount distribution of the first element e1 and the second element e2 is as shown in Figure 10(C), the position where the concentration or detection amount of the first element e1 is maximum is located further inside than the position where the concentration or detection amount of the second element e2 is maximum. Furthermore, for example, if the concentration distribution or detection amount distribution of the first element e1 and the second element e2 is as shown in Figure 10(D), the position where the concentration or detection amount of the second element e2 is maximum is located further inside than the position where the concentration or detection amount of the first element e1 is maximum. Furthermore, for example, if the concentration distribution or detection amount distribution of the first element e1 and the second element e2 is as shown in Figure 10(E), the position where the concentration or detection amount of the first element e1 is maximum is located further inside than the position where the concentration or detection amount of the second element e2 is maximum. Furthermore, for example, if the concentration distribution or detection amount distribution of the first element e1 and the second element e2 is as shown in Figure 10(F), the position where the concentration or detection amount of the second element e2 is maximum is located further inside than the position where the concentration or detection amount of the first element e1 is maximum.
[0227] The expression "having a region where the distributions overlap" will be explained using the example of the positional relationship shown in Figure 10(G) for the concentration distributions or detection amount distributions of the first element e1, the second element e2, and the third element e3. In this specification, "having a region where the distributions of two elements overlap" means, for example, that the position where the maximum value occurs in the concentration distribution or detection amount distribution of at least one element is located within the range where the concentration or detection amount in the concentration distribution or detection amount distribution of the other element is 1 / 5 or more of the maximum value. Note that if the detection intensity of the background in EDX radiation analysis is 1 / 5 or more of the above "maximum value", then "1 / 5 of the maximum value" in the above text shall be referred to as the "detection intensity of the background (also called the detection limit)".
[0228] For example, in the positional relationship shown in Figure 10(G), the position (p2) where the concentration distribution or detection amount distribution of the second element e2 is at its maximum value is located within the range (hatched area in the figure) where the concentration or detection amount of the first element e1 is at or above 1 / 5 of the maximum value (or the lower detection limit). Therefore, the first element e1 and the second element e2 have an overlapping distribution. On the other hand, the position (p3) where the concentration distribution or detection amount distribution of the third element e3 is at its maximum value is not located within the range (hatched area in the figure) where the concentration or detection amount of the first element e1 is at or above 1 / 5 of the maximum value (or the lower detection limit). Therefore, the first element e1 and the third element e3 cannot be said to have an overlapping distribution.
[0229] Furthermore, in the case of the positional relationship shown in Figure 10(G), it can be said that the distribution of the second element e2 and the distribution of the third element e3 are located more inward than the distribution of the first element e1. Alternatively, it can be said that the distribution of the second element e2 and the distribution of the third element e3 are biased more towards the inward side than the distribution of the first element e1.
[0230] <Second positive electrode active material particles> The positive electrode of one embodiment of the present invention can include, in addition to the positive electrode active material particle 100, a second positive electrode active material particle different from the positive electrode active material particle 100. Like the positive electrode active material particle 100, the second positive electrode active material particle 200 has a function of taking in and a function of releasing lithium ions along with charge and discharge. As the second positive electrode active material particle 200 used in one embodiment of the present invention, a material can be used which is similar to the positive electrode active material particle 100 except for the difference in particle size, and which causes little deterioration associated with charge and discharge even at a high charging voltage. Specifically, in the method for manufacturing a positive electrode active material particle described in Embodiment 2, a positive electrode active material particle (composite oxide) having a particle size (median diameter (D50)) of 0.1 μm or more and less than 9 μm, preferably 1 μm or more and 5 μm or less, which is obtained by reducing the particle size of a starting material and lowering the temperature or shortening the time of the heat treatment, can be used. Like the positive electrode active material particle 100 described above, the second positive electrode active material particle 200 preferably contains any one or more of the additive element X, the additive element Y, and the additive element Z.
[0231] The content of this embodiment can be freely combined with the content of other embodiments.
[0232] (Embodiment 2) In this embodiment, an example of a method for manufacturing the positive electrode active material particle 100, which is the positive electrode active material of the battery of one embodiment of the present invention, will be described. FIGS. 11(A) to 12(C) are diagrams illustrating a method for manufacturing the positive electrode active material particle 100.
[0233] In order to manufacture the positive electrode active material particle 100, the method of adding the additive element A is important. At the same time, it is also important that the crystallinity inside the positive electrode active material particle is favorable.
[0234] Therefore, in the manufacturing process of the positive electrode active material particle 100, it is preferable that first, a first lithium source and a cobalt source are mixed and subjected to heat treatment to synthesize lithium cobaltate, then the lithium cobaltate and a second lithium source are mixed and subjected to heat treatment, and thereafter, an additive element source is mixed and subjected to heat treatment.
[0235] In a method of synthesizing lithium cobalt oxide containing additive element A by mixing a first lithium source, a cobalt source, and an additive element source, it is difficult to increase the concentration of additive element A in the surface layer portion of the positive electrode active material particles. Further, after synthesizing lithium cobalt oxide, if only the additive element source is mixed without performing heating, additive element A will merely adhere to the lithium cobalt oxide without forming a solid solution. Without sufficient heating, it is difficult to distribute additive element A in a favorable manner. Therefore, it is preferable to synthesize lithium cobalt oxide, then mix the additive element source, and perform a heat treatment.
[0236] However, if the temperature of the heat treatment is excessively high, cation mixing occurs, increasing the possibility that additive element A, for example magnesium, enters the cobalt site. Magnesium present at the cobalt site, Li x when x in CoO2 is small, has no effect of maintaining the R-3m layered rock salt type crystal structure. Furthermore, if the temperature of the heat treatment is excessively high, there are concerns about adverse effects such as cobalt being reduced to a divalent state and lithium evaporating.
[0237] [Initial Heating] Accordingly, before mixing with the additive element source and heating, it is preferable to mix with a second lithium source and perform heating (also referred to as initial heating). Here, as the second lithium source, it is preferable to use a material that functions as a flux, and lithium fluoride, for example, is suitable.
[0238] Further, it is preferable to sufficiently mix lithium cobalt oxide and the second lithium source. As the mixing method, mixing can be performed by, for example, a ball mill.
[0239] In the step of sufficiently mixing lithium cobalt oxide and the second lithium source, there is an effect that the adhesion between lithium cobalt oxide particles is eliminated.
[0240] Furthermore, by adding a material that functions as a flux as a second lithium source, it is possible to suppress the re-adhesion of lithium cobalt oxide particles when the lithium cobalt oxide after initial heating is mixed with the added element source and heated in subsequent steps.
[0241] If lithium cobalt oxide particles are stuck together and then additive element A is added and heated, there is a risk that additive element A will not be sufficiently distributed to the stuck areas. Therefore, when the sticking is released in a later process, such as a pressurizing process after coating the positive electrode current collector, surfaces with insufficient additive element A will be exposed, and degradation may progress from those surfaces when used in a secondary battery. For this reason, it is preferable to suppress the sticking of lithium cobalt oxide particles using the method described above before mixing in the additive element source and heating.
[0242] Furthermore, by adding a flux during the initial heating process, a melting point depression occurs near the surface of the lithium cobalt oxide when the lithium cobalt oxide after initial heating is mixed with the additive element source and heated in subsequent steps. This melting point depression makes it easier to distribute additive element A well at a temperature where cation mixing is less likely to occur.
[0243] Therefore, the heating temperature in the initial heating is preferably above the melting point of the second lithium source. For example, when lithium fluoride is used as the second lithium source, the temperature is preferably higher than the melting point of lithium fluoride, which is 848°C (e.g., 850°C or higher), and more preferably 900°C or higher. Furthermore, the heating temperature in the initial heating is preferably below the temperature used when synthesizing lithium cobalt oxide (e.g., 950°C or lower). In other words, for the initial heating, it is preferable to mix lithium cobalt oxide and lithium fluoride and heat them at a temperature of 900°C to 950°C.
[0244] Furthermore, by using lithium cobalt oxide that has undergone the initial heating described above, it is possible to suppress lithium deficiency that occurs due to the evaporation of lithium during the subsequent process of mixing and heating with additive element A.
[0245] Lithium cobalt oxide that has undergone the initial heating described above preferably has a higher proportion of layered rock salt-type crystal structures in the surface layer compared to lithium cobalt oxide before the initial heating. For example, in lithium cobalt oxide that has undergone the initial heating described above, it is preferable that the layered rock salt-type crystal structure accounts for 35% or more, and more preferably 45% or more, in the portion within 2 nm from the surface. Furthermore, when EELS analysis is performed, the valence of cobalt is preferably 2.35 or higher, and more preferably 2.45 or higher. A high proportion of layered rock salt-type crystal structures is one factor indicating that lithium deficiency is suppressed.
[0246] On the other hand, it is preferable that not the entire surface layer of lithium cobalt oxide has a layered rock salt crystal structure. For example, the solid solubility limit of magnesium is extremely low in pure lithium cobalt oxide. In order to solid dissolve magnesium and other additive elements A at a sufficient concentration, it is preferable that the surface layer of lithium cobalt oxide has a rock salt crystal structure. Therefore, it is preferable that the lithium cobalt oxide that has undergone the above initial heating has a layered rock salt crystal structure of less than 100% within 2 nm from the surface, and more preferably 90% or less. Furthermore, when EELS analysis is performed, it is preferable that the valence of cobalt is less than 3.00, and more preferably 2.90 or less.
[0247] In other words, the lithium cobalt oxide that has undergone the initial heating described above preferably has a layered rock salt-type crystalline structure of 35% or more and less than 100% in the portion within 2 nm from the surface, more preferably 35% or more and 90%, and even more preferably 45% or more and 90%. Furthermore, when EELS analysis is performed, the valence of cobalt is preferably 2.35 or more and less than 3.00, more preferably 2.35 or more and 2.90, and even more preferably 2.45 or more and 2.90.
[0248] Method for producing positive electrode active material particles 100 Method 1 for producing positive electrode active material particles 100, which undergo heat treatment and initial heating, will be explained using Figures 11(A) to 12(C).
[0249] <Step S11> In step S11 shown in Figure 11(B), a first lithium source (Li source 1) and a first cobalt source (Co source) are prepared as the starting materials, which are the first lithium and transition metal materials, respectively.
[0250] As the first lithium source, it is preferable to use a lithium-containing compound, such as lithium carbonate, lithium hydroxide, lithium nitrate, or lithium fluoride. The lithium source should preferably have high purity; for example, a material with a purity of 99.99% or higher is preferable.
[0251] As a cobalt source, it is preferable to use a compound containing cobalt, such as tricobalt tetroxide or cobalt hydroxide.
[0252] The cobalt source should preferably have high purity; for example, a material with a purity of 3N (99.9%) or higher, preferably 4N (99.99%) or higher, more preferably 4N5 (99.995%) or higher, and even more preferably 5N (99.999%) or higher should be used. By using a high-purity material, impurities in the positive electrode active material particles can be controlled. As a result, the capacity of the secondary battery is increased and / or the reliability of the secondary battery is improved.
[0253] In addition, it is preferable that the cobalt source has high crystallinity, for example, that it has single crystal grains. The crystallinity of the cobalt source can be evaluated by TEM images, STEM images, HAADF-STEM (High-angle Annular Dark Field Scanning TEM), ABF-STEM (Annular Bright-Field Scanning Transmission Electron Microscope), or by X-ray diffraction, electron diffraction, neutron diffraction, etc. The above methods for evaluating crystallinity can be applied not only to cobalt sources but also to the evaluation of other materials.
[0254] <Step S12> Next, as step S12 shown in FIG. 11(B), the first lithium source and the cobalt source are pulverized and mixed to prepare a mixed material. Pulverization and mixing can be performed in a dry or wet manner. The wet method allows finer pulverization and mixing of particles. When performing the process by the wet method, a solvent is prepared. As the solvent, ketones such as acetone, alcohols such as ethanol and isopropanol, ether, dioxane, acetonitrile, N-methyl-2-pyrrolidone (NMP) and the like can be used. It is more preferable to use an aprotic solvent that hardly reacts with lithium. In the present embodiment, dehydrated acetone with a purity of 99.5% or higher is used. It is preferable to mix the first lithium source and the cobalt source in dehydrated acetone with a purity of 99.5% or higher whose water content is suppressed to 10 ppm or less, and then perform pulverization and mixing. By using the dehydrated acetone with the purity as described above, impurities that may be mixed in can be reduced.
[0255] A ball mill, a bead mill or the like can be used as the means for pulverization and mixing. When a ball mill is used, it is preferable to use aluminum oxide balls or zirconium oxide balls as the pulverization media. Zirconium oxide balls are preferable because they cause less discharge of impurities. Further, when a ball mill, a bead mill or the like is used, the peripheral speed is preferably set to 100 mm / s or more and 2000 mm / s or less in order to suppress contamination from the media. In the present embodiment, the process is carried out at a peripheral speed of 838 mm / s (a rotation speed of 400 rpm, and a ball mill diameter of 40 mm).
[0256] <Step S13> Next, as step S13 shown in Figure 11(B), the mixed material is heated. The heating is preferably carried out at a temperature of 800°C to 1100°C, more preferably at 900°C to 1050°C, and even more preferably at 950°C to 1000°C. If the temperature is too low, the decomposition and melting of the first lithium source and cobalt source may be insufficient. On the other hand, if the temperature is too high, defects may occur due to the evaporation of lithium from the first lithium source and / or the excessive reduction of cobalt. For example, cobalt may change from trivalent to divalent, inducing oxygen defects, etc.
[0257] If the heating time is too short, lithium cobalt oxide will not be synthesized, but if it is too long, productivity will decrease. For example, the heating time is preferably between 1 hour and 100 hours, and more preferably between 2 hours and 20 hours.
[0258] The heating rate depends on the target temperature, but a rate between 80°C / h and 250°C / h is preferable. For example, when heating to 1000°C for 10 hours, the heating rate can be 200°C / h.
[0259] Heating is preferably carried out in an atmosphere with little water, such as dry air, for example, an atmosphere with a dew point of -50°C or lower, more preferably an atmosphere with a dew point of -80°C or lower. In this embodiment, heating is carried out in an atmosphere with a dew point of -93°C. Furthermore, in order to suppress impurities that may be mixed into the material, it is preferable that the concentrations of impurities such as CH4, CO, CO2, and H2 in the heating atmosphere be 5 ppb (parts per billion) or less.
[0260] An oxygen-containing atmosphere (oxygen atmosphere) is preferred as the heating atmosphere. For example, one method is to continuously introduce dry air into the reaction chamber. In this case, the flow rate of the dry air is preferably 10 L / min. The method of continuously introducing oxygen into the reaction chamber and having oxygen flow through the reaction chamber is called flow.
[0261] When the heating atmosphere is to be an oxygen-containing atmosphere, a method that does not involve flowing oxygen may be used. For example, the reaction chamber may be depressurized and then filled with oxygen (which can also be called purging), and the oxygen may be prevented from entering or leaving the reaction chamber to create an oxygen-containing atmosphere. For example, the reaction chamber may be depressurized to -970 hPa (differential pressure gauge) and then filled with oxygen to 50 hPa (differential pressure gauge).
[0262] After heating, natural cooling is acceptable, but it is preferable that the cooling time from the specified temperature to room temperature is between 10 and 50 hours. However, cooling to room temperature is not always necessary; it is sufficient if it cools to a temperature acceptable for the next step.
[0263] Heating in this process may be carried out using a rotary kiln or a roller hearth kiln. When using a rotary kiln, heating can be performed while stirring, whether in a continuous or batch system.
[0264] When heating, the container holding the material to be heated is preferably an aluminum oxide crucible or an aluminum oxide setter (also called a sheath). An aluminum oxide crucible is a material that hardly allows impurities to mix with the material to be heated. In this embodiment, an aluminum oxide setter with a purity of 99.9% is used. When heating a mixture containing lithium fluoride (LiF), the LiF may volatilize due to heating, reducing the amount of LiF in the mixture. Therefore, when heating a mixture containing lithium fluoride, it is preferable to control the partial pressure of fluorine or fluoride in the atmosphere to an appropriate range. For example, it is preferable to cover the crucible or setter before heating because this can prevent the volatilization of the material to be heated. Mullite-cordierite may also be used as the material for the crucible and setter.
[0265] Furthermore, it is preferable to use a used crucible rather than a new one. In this specification, a new crucible is defined as one that has undergone the heating process of a material containing lithium, transition metal M, and / or additive element A two times or less. A used crucible is defined as one that has undergone the heating process of a material containing lithium, transition metal M, and / or additive element A three or more times. This is because, when a new crucible is used, there is a risk that some of the heated material, including lithium fluoride, may be absorbed, diffused, migrated, and / or adhered to the casing during heating. If some of the material is lost as a result, there is a growing concern that the distribution of elements on the surface of the positive electrode active material particles will not be within a desirable range. On the other hand, this risk is less with a used crucible.
[0266] After heating is complete, the material may be crushed and sieved as needed. When collecting the heated material, it may be transferred from the crucible to a mortar before collection. A zirconium oxide mortar is preferable for this purpose. Zirconium oxide mortars are less likely to release impurities. Specifically, a zirconium oxide mortar with a purity of 90% or higher, preferably 99% or higher, should be used. The conditions described in step S13 can also be referenced in the heating steps described later, other than step S13.
[0267] <Step S14> Through the above process, lithium cobalt oxide (LiCoO2) shown in step S14 of Figure 11(B) can be synthesized. The lithium cobalt oxide (LiCoO2) thus produced can be used as the starting material LiCoO2 in step S10 of Figure 11(A).
[0268] <Step S10> The lithium cobalt oxide produced in this way can be used as the starting material LiCoO2 in step S10 of Figure 11(A).
[0269] Although examples of producing lithium cobalt oxide by a solid-phase method have been shown as in steps S11 to S14, lithium cobalt oxide may also be produced by a coprecipitation method. Alternatively, lithium cobalt oxide may be produced by a hydrothermal method.
[0270] <Step S15> In step S15 shown in Figure 11(A), a second lithium source (Li source 2) is prepared. It is preferable to use lithium fluoride, for example, as the second lithium source.
[0271] <Step S16> Next, in step S16 shown in Figure 11(A), lithium cobalt oxide and the second lithium source are mixed. The mixing in step S16 is preferably carried out under milder conditions than in step S12, in order to avoid damaging the shape of the lithium cobalt oxide particles. For example, it is preferable to use conditions with a lower rotation speed or shorter mixing time than in step S12. Furthermore, dry mixing is generally considered milder than wet mixing. For mixing, a ball mill, bead mill, etc., can be used. When using a ball mill, it is preferable to use zirconium oxide balls as the media, for example.
[0272] <Step S17> Next, as step S17 shown in Figure 11(A), the lithium cobalt oxide and the second lithium source are heated. The heating is preferably carried out at 800°C to 1000°C, more preferably at 850°C to 950°C, and even more preferably at 900°C to 950°C. The heating time is preferably 1 hour to 60 hours, more preferably 2 hours to 20 hours, even more preferably 2 hours to 10 hours, and even more preferably 2 hours to 6 hours. Because this is the first heating of the lithium cobalt oxide, the heating in step S17 is sometimes called initial heating. Alternatively, because it is heated before step S33 shown below, it may be called preheating or pretreatment. By carrying out steps S16 and S17, lithium cobalt oxide with a smooth surface can be obtained.
[0273] In step S10, lithium cobalt oxide synthesized in step S14 may be used. In this case, steps S11 to S13 can be omitted. Even when using lithium cobalt oxide synthesized in advance, steps S16 and S17 can be performed to obtain lithium cobalt oxide with a smooth surface.
[0274] <Step S20a> Next, as shown in steps S20a to S33, it is preferable to add element A1 to the lithium cobalt oxide that has undergone initial heating. Adding element A1 to lithium cobalt oxide that has undergone initial heating allows for even addition of element A1. Therefore, it is preferable to add element A1 after initial heating. In step S20a, a first source of additive element (A1 source) is prepared.
[0275] <Step S21> The details of step S20a are shown in Figure 12(A). Steps S21 to S23 shown in Figure 12(A) are used to prepare a first additive element source (A1 source). As the first additive element A1, one or more of magnesium and fluorine can be suitably used. Figure 12(A) illustrates the case where a magnesium source (Mg source) and a fluorine source (F source) are used as the first additive element source.
[0276] Step S21 shown in Figure 12(A) will now be explained. When magnesium is selected as the additive element A, the additive element source can be called a magnesium source (Mg source). Magnesium fluoride, magnesium oxide, magnesium hydroxide, or magnesium carbonate can be used as the magnesium source. Multiple magnesium sources may also be used.
[0277] When fluorine is selected as additive element A, the additive element source can be called a fluorine source (F source). Examples of such fluorine sources include lithium fluoride (LiF), magnesium fluoride (MgF2), aluminum fluoride (AlF3), cobalt fluoride (CoF2, CoF3), nickel fluoride (NiF2), zirconium fluoride (ZrF4), vanadium fluoride (VF5), manganese fluoride, iron fluoride, chromium fluoride, niobium fluoride, zinc fluoride (ZnF2), calcium fluoride (CaF2), sodium fluoride (NaF), potassium fluoride (KF), barium fluoride (BaF2), cerium fluoride (CeF3, CeF4), lanthanum fluoride (LaF3), or sodium aluminum hexafluoride (Na3AlF6). Among these, lithium fluoride is preferred because it has a relatively low melting point of 848°C and is easily melted in the heating process described later. When lithium fluoride is used as the fluorine source, it can also be called the third lithium source.
[0278] Magnesium fluoride can be used as both a fluorine source and a magnesium source. Lithium fluoride can also be used as a lithium source. Another lithium source used in step S21 is lithium carbonate.
[0279] Alternatively, the fluorine source may be a gas such as fluorine (F2), carbon fluoride, sulfur fluoride, or oxygen fluoride (OF2, O2F2, O3F2, O4F2, O5F2, O6F2, O2F), which may be mixed into the atmosphere during the heating process described later. Multiple fluorine sources may also be used.
[0280] In this embodiment, lithium fluoride (LiF) is prepared as the fluorine source, and magnesium fluoride (MgF2) is prepared as both the fluorine source and the magnesium source. The effect of lowering the melting point is greatest when lithium fluoride and magnesium fluoride are mixed in a molar ratio of approximately LiF:MgF2 = 65:35. On the other hand, if the amount of lithium fluoride is too high, there is a concern that the lithium will be in excess and the cycle characteristics will deteriorate. Therefore, the molar ratio of lithium fluoride to magnesium fluoride is preferably LiF:MgF2 = x:1 (0 ≤ x ≤ 1.9), more preferably LiF:MgF2 = x:1 (0.1 ≤ x ≤ 0.5), and even more preferably LiF:MgF2 = x:1 (x = 0.33 or nearby). In this specification, nearby means a value greater than 0.9 times and less than 1.1 times the value.
[0281] <Step S22> Next, in step S22 shown in Figure 12(A), the magnesium source and the fluorine source are crushed and mixed. This step can be performed by selecting from the crushing and mixing conditions described in step S12.
[0282] <Step S23> Next, in step S23 shown in Figure 12(A), the materials crushed and mixed above are recovered to obtain the additive element A1 source (A1 source). The additive element A1 source shown in step S23 has multiple starting materials and can be called a mixture.
[0283] The particle size of the above mixture is preferably such that the D50 (median diameter) is 600 nm or more and 10 μm or less, and more preferably 1 μm or more and 5 μm or less. Even when one material is used as the source of added elements, the D50 (median diameter) is preferably such that it is 600 nm or more and 10 μm or less, and more preferably 1 μm or more and 5 μm or less.
[0284] When the mixture is finely powdered in this way (including cases where only one element A is added), it is easier to uniformly adhere the mixture to the surface of the lithium cobalt oxide particles when it is mixed with lithium cobalt oxide in a later process. When the mixture is uniformly adhered to the surface of the lithium cobalt oxide particles, it is preferable because it is easier to evenly distribute or diffuse the element A onto the surface layer of the positive electrode active material particles 100 after heating.
[0285] <Step S31> Next, in step S31 shown in Figure 11(A), the lithium cobalt oxide that has undergone initial heating is mixed with the additive element A1 source (A1 source).
[0286] In this embodiment, the number of magnesium atoms contained in the additive element A1 source is preferably 0.50% to 3.0%, more preferably 0.75% to 2.0%, and even more preferably 0.75% to 1.0%, relative to the number of cobalt atoms in the lithium cobalt oxide after initial heating.
[0287] The mixing in step S31 is preferably carried out under milder conditions than the mixing in step S12 in order to avoid destroying the shape of the lithium cobalt oxide particles. For example, it is preferable to use conditions with a lower rotation speed or shorter time than the mixing in step S12. Also, dry mixing is generally milder than wet mixing. For mixing, for example, a ball mill or a bead mill can be used. When using a ball mill, it is preferable to use zirconium oxide balls as the media.
[0288] In this embodiment, the mixing is performed dry using a ball mill with zirconium oxide balls with a diameter of 1 mm at 150 rpm for 1 hour. The mixing is carried out in a dry room with a dew point of -100°C or higher and -10°C or lower.
[0289] <Step S32> Next, in step S32 of Figure 11(A), the materials mixed above are recovered to obtain mixture 903. Sieving may be performed during recovery if necessary.
[0290] Although Figures 11(A) to 12(A) illustrate a manufacturing method in which additive element A is added only after initial heating, the present invention is not limited to the above method. Additive element A may be added at other times, or added multiple times. The timing may also be varied depending on the element.
[0291] <Step S33> Next, in step S33 shown in Figure 11(A), the mixture 903 is heated.
[0292] For example, if the additive element source A contains MgF2, the eutectic point of LiF and MgF2 is around 742°C, so it is preferable that the heating temperature in step S33 be above the eutectic point (for example, 742°C or higher).
[0293] Furthermore, a mixture obtained by mixing LiCoO2:LiF:MgF2 in a molar ratio of 100:0.33:1 shows an endothermic peak around 830°C in differential scanning calorimetry (DSC). Since this endothermic peak is thought to be due to the melting of the mixture, a heating temperature of 830°C or higher is more preferable. Therefore, the heating in step S33 is preferably carried out at 800°C to 1000°C, more preferably at 830°C to 950°C, and even more preferably at 850°C to 950°C. In addition, the heating time is preferably 1 hour to 60 hours, and more preferably 2 hours to 20 hours.
[0294] In the manufacturing method described in this embodiment, the second lithium source, LiF, added in steps S16 and S17 of Figure 11(A), may function as a flux.
[0295] A note regarding heating time: The heating time varies depending on conditions such as the heating temperature, the size of the lithium cobalt oxide in step S14, and its composition. When the lithium cobalt oxide is small, a lower heating temperature or shorter heating time may be preferable than when it is large.
[0296] <Step S34a> Next, the material heated in step S33 is recovered to produce lithium cobalt oxide containing additive element A1. This is called a composite oxide to distinguish it from the lithium cobalt oxide produced in step S14.
[0297] <Step S40> In step S40 shown in Figure 11(A), a second source of added elements (source A2) is prepared.
[0298] <Step S41> In steps S41 to S43 shown in Figure 12(B), a second additive element source (A2 source) is prepared. The additive element A2 in the second additive element source can preferably be one or more selected from nickel, boron, zirconium, and aluminum. Figure 12(B) illustrates the case where a nickel source (Ni source) and an aluminum source (Al source) are used as the second additive element source. For example, nickel hydroxide, nickel fluoride, etc., can be used as the nickel source. Similarly, for example, aluminum hydroxide, aluminum fluoride, etc., can be used as the aluminum source.
[0299] The number of nickel atoms in the second additive element source (A2 source) is preferably 0.05% to 4.0%, more preferably 0.20% to 2.0%, and even more preferably 0.20% to 1.0%, relative to the number of cobalt atoms in the lithium cobalt oxide (composite oxide) having additive element A1. For example, when nickel hydroxide is used as the nickel source, when the number of moles of lithium cobalt oxide in step S10 is set to 100, the number of moles of nickel hydroxide contained in the second additive element source is preferably 0.05 to 4.0 (0.05 mol% to 4.0 mol%), more preferably 0.20 to 2.0 (0.20 mol% to 2.0 mol%), and even more preferably 0.20 to 1.0 (0.20 mol% to 1.0 mol%).
[0300] The number of aluminum atoms in the second additive element source (A2 source) is preferably 0.05% to 4.0%, more preferably 0.20% to 2.0%, and even more preferably 0.20% to 1.0%, relative to the number of cobalt atoms in the lithium cobalt oxide (composite oxide) having additive element A1. For example, when aluminum hydroxide is used as the aluminum source, when the number of moles of lithium cobalt oxide in step S10 is set to 100, the number of moles of aluminum hydroxide contained in the second additive element source is preferably 0.05 to 4.0 (0.05 mol% to 4.0 mol%), more preferably 0.20 to 2.0 (0.20 mol% to 2.0 mol%), and even more preferably 0.20 to 1.0 (0.20 mol% to 1.0 mol%).
[0301] Steps S41 to S43 shown in Figure 12(B) can be carried out under the same conditions as steps S21 to S23 shown in Figure 12(A). As a result, the additive element source (A2 source) can be obtained in step S43.
[0302] Furthermore, Figure 12(C) shows a modified example of the steps described using Figure 12(B). In step S41 shown in Figure 12(C), a nickel source (Ni source) and an aluminum source (Al source) are prepared, and in step S42a, each is crushed. In other words, in step S43 shown in Figure 12(C), multiple second additive element sources (A2 sources) are prepared.
[0303] <Steps S51 to S53> Next, steps S51 to S53 shown in Figure 11(A) can be carried out under the same conditions as steps S31 to S34. The heating in step S53 is preferably carried out at 800°C to 1000°C, more preferably at 800°C to 950°C, and even more preferably at 800°C to 900°C. The heating time is preferably 1 hour to 60 hours, more preferably 2 hours to 20 hours, and even more preferably 2 hours to 10 hours. It is preferable that the heating in step S53 is carried out at a lower heating temperature and for a shorter heating time than in step S33. Through the above steps, in step S54, positive electrode active material particles 100 according to one embodiment of the present invention can be produced. The positive electrode active material particles according to one embodiment of the present invention have a smooth surface.
[0304] As shown in Figures 11(A) to 12(C), in the method for producing the positive electrode active material particles 100 described in this embodiment, the addition of additive element A to lithium cobalt oxide is carried out separately as additive element A1 and additive element A2. By adding additive element A1 and additive element A2 separately, the depth distribution of each additive element A can be changed. For example, it is possible to distribute additive element A1 at a higher concentration in the surface layer of the positive electrode active material particles compared to the interior, and to distribute additive element A2 at a higher concentration in the interior compared to the surface.
[0305] Furthermore, by performing steps S10 to S17 of the initial heating process shown in the method for producing positive electrode active material particles 100, the positive electrode active material particles 100 obtained in the final step S54 can have a LiTiO2-type crystal structure as explained in Figures 5(A) to 6(F).
[0306] The contents of this embodiment can be freely combined with the contents of other embodiments.
[0307] (Embodiment 3) In this embodiment, each element constituting the battery will be described.
[0308] [Positive electrode] The positive electrode comprises a positive electrode active material layer and a positive electrode current collector. The positive electrode active material layer has positive electrode active material particles and may further have at least one of a conductive material and a binder. The positive electrode active material particles can be the positive electrode active material particles 100 described in Embodiments 1 and 2.
[0309] The positive electrode current collector can be made of, for example, metal foil. The positive electrode can be formed by applying a slurry to the metal foil and drying it. Pressing may also be applied after drying. The positive electrode is formed by creating an active material layer on the positive electrode current collector.
[0310] A slurry is a liquid material used to form an active material layer on a positive electrode current collector. It contains an active material, a binder, and a solvent, and preferably also contains a conductive material. The slurry is sometimes called an electrode slurry or an active material slurry. When forming a positive electrode active material layer, a positive electrode slurry is used, and when forming a negative electrode active material layer, a negative electrode slurry is used.
[0311] The positive electrode active material particles have the function of taking in and releasing lithium ions during charging and discharging. The positive electrode active material particles 100 used in one embodiment of the present invention described above can be made of a material that does not degrade much during charging and discharging, even at high charging voltages.
[0312] <Binder> As a binder, it is preferable to use rubber materials such as styrene-butadiene rubber (SBR), styrene-isoprene-styrene rubber, acrylonitrile-butadiene rubber, butadiene rubber, or ethylene-propylene-diene copolymer. Fluororubber can also be used as a binder.
[0313] Furthermore, a water-soluble polymer may be used as the binder. Examples of water-soluble polymers include polysaccharides. Examples of polysaccharides include cellulose derivatives such as carboxymethylcellulose (CMC), methylcellulose, ethylcellulose, hydroxypropylcellulose, diacetylcellulose, and regenerated cellulose, or starch. It is even more preferable to use these water-soluble polymers in combination with the aforementioned rubber material.
[0314] Alternatively, it is preferable to use materials such as polystyrene, methyl polyacrylate, polymethyl methacrylate (PMMA), sodium polyacrylate, polyvinyl alcohol (PVA), polyethylene oxide (PEO), polypropylene oxide, polyimide, polyvinyl chloride, polytetrafluoroethylene, polyethylene, polypropylene, polyisobutylene, polyethylene terephthalate, nylon, polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), ethylene propylene diene polymer, polyvinyl acetate, or nitrocellulose as the binder.
[0315] You may use a combination of several of the binders mentioned above.
[0316] <Conductive material> Conductive materials, also called conductivity imparters or conductivity enhancers, are typically made of carbon. By attaching the conductive material between multiple active materials, the active materials are electrically connected to each other, increasing conductivity. Note that "attachment" does not only refer to physical contact between the active materials and the conductive material, but also includes cases where covalent bonds are formed, bonds are formed by van der Waals forces, the conductive material covers part of the surface of the active material, the conductive material fits into surface irregularities of the active material, or where they are electrically connected even without physical contact.
[0317] The active material layers, such as the positive electrode active material layer and the negative electrode active material layer, preferably contain a conductive material.
[0318] As conductive materials, one or more of the following can be used: carbon black such as acetylene black and furnace black; graphite such as artificial graphite and natural graphite; carbon fibers such as carbon nanofibers and carbon nanotubes; and graphene compounds.
[0319] As carbon fibers, for example, mesophase pitch carbon fibers and isotropic pitch carbon fibers can be used. Alternatively, carbon nanofibers or carbon nanotubes can be used. Carbon nanotubes can be fabricated, for example, by vapor deposition.
[0320] In this specification, graphene compounds include graphene, multilayer graphene, multigraphene, graphene oxide, multilayer graphene oxide, multigraphene oxide, reduced graphene oxide, reduced multilayer graphene oxide, reduced multigraphene oxide, graphene quantum dots, etc. A graphene compound is a material having carbon, having a plate-like or sheet-like shape, and having a two-dimensional structure formed by a six-membered carbon ring. The two-dimensional structure formed by the six-membered carbon ring may also be called a carbon sheet. Graphene compounds may have functional groups. Furthermore, graphene compounds preferably have a bent shape. Furthermore, graphene compounds may be rolled up to resemble carbon nanofibers.
[0321] The content of conductive material relative to the total amount of active material layer is preferably 1 wt% to 10 wt%, and more preferably 1 wt% to 5 wt%.
[0322] <Positive electrode current collector> As the current collector, highly conductive materials such as stainless steel, gold, platinum, aluminum, titanium, and alloys thereof can be used. Furthermore, it is preferable that the material used for the positive electrode current collector does not dissolve at the positive electrode potential. Aluminum alloys with added elements that improve heat resistance, such as silicon, titanium, neodymium, scandium, and molybdenum, can also be used. Alternatively, it may be formed from a metallic element that reacts with silicon to form a silicide. Examples of metallic elements that react with silicon to form a silicide include zirconium, titanium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, cobalt, and nickel. The current collector can be in various shapes, such as foil, plate, sheet, mesh, perforated metal, or expanded metal. The current collector should preferably have a thickness of 5 μm to 30 μm.
[0323] [Negative electrode] The negative electrode comprises a negative electrode active material layer and a negative electrode current collector. The negative electrode active material layer may also contain a negative electrode active material, a conductive material, and a binder.
[0324] <Negative electrode active material> For example, alloy materials or carbon materials can be used as the negative electrode active material.
[0325] Furthermore, the negative electrode active material can be an element capable of undergoing charge-discharge reactions through alloying and dealloying reactions with lithium. For example, a material containing at least one of silicon, tin, gallium, aluminum, germanium, lead, antimony, bismuth, silver, zinc, cadmium, indium, etc., can be used. Such elements have a larger capacity than carbon, and silicon in particular has a high theoretical capacity of 4200 mAh / g. For this reason, it is preferable to use silicon as the negative electrode active material. Compounds containing these elements may also be used. Examples include SiO, Mg2Si, Mg2Ge, SnO, SnO2, Mg2Sn, SnS2, V2Sn3, FeSn2, CoSn2, Ni3Sn2, Cu6Sn5, Ag3Sn, Ag3Sb, Ni2MnSb, CeSb3, LaSn3, La3Co2Sn7, CoSb3, InSb, SbSn, etc. In this context, elements capable of undergoing charge-discharge reactions through alloying and de-alloying reactions with lithium, and compounds containing such elements, are sometimes referred to as alloying materials.
[0326] In this specification, "SiO" refers to silicon monoxide, for example. Alternatively, SiO refers to SiO x It can also be expressed as follows. Here, x is preferably 1 or a value in its immediate vicinity. For example, x is preferably between 0.2 and 1.5, and more preferably between 0.3 and 1.2.
[0327] Carbon materials such as graphite, easily graphitizable carbon (soft carbon), difficult-to-graphitize carbon (hard carbon), carbon fibers (carbon nanotubes), graphene, and carbon black can be used.
[0328] Examples of graphite include artificial graphite and natural graphite. Examples of artificial graphite include mesocarbon microbeads (MCMB), coke-based artificial graphite, and pitch-based artificial graphite. Here, spheroidal graphite having a spherical shape can be used as artificial graphite. For example, MCMB may have a spherical shape and is therefore preferable. Furthermore, it is relatively easy to reduce the surface area of MCMB, which may also be preferable. Examples of natural graphite include flake graphite and spheroidized natural graphite.
[0329] When lithium ions are inserted into graphite (during the formation of lithium-graphite intercalation compounds), graphite exhibits a potential as low as that of lithium metal (0.05V to 0.3V vs. Li / Li). + This allows lithium-ion batteries using graphite to exhibit a high operating voltage. Furthermore, graphite is preferable because it has advantages such as a relatively high capacity per unit volume, relatively small volume expansion, low cost, and higher safety compared to lithium metal.
[0330] Furthermore, titanium dioxide (TiO2) and lithium titanium oxide (Li4Ti5O2) are used as negative electrode active materials. 12 ), lithium-graphite intercalation compound (Li x Oxides such as C6, niobium pentoxide (Nb2O5), tungsten dioxide (WO2), and molybdenum dioxide (MoO2) can be used.
[0331] The conductive material and binder that the negative electrode active material layer can have can be the same materials as the conductive material and binder that the positive electrode active material layer can have.
[0332] <Negative electrode current collector> In addition to the same materials as the positive electrode current collector, copper and other materials can also be used for the negative electrode current collector. It is preferable to use a material for the negative electrode current collector that does not alloy with carrier ions such as lithium.
[0333] [Electrolyte] A secondary battery has an electrolyte containing carrier ions. In this specification, the electrolyte is not limited to one containing an organic solvent that is liquid at room temperature, but also includes solid electrolytes, and electrolytes containing both an organic solvent that is liquid at room temperature and a solid electrolyte that is solid at room temperature (semi-solid electrolytes). A solution in which a lithium salt is dissolved in an organic solvent that is liquid at room temperature is sometimes called an electrolyte solution.
[0334] <Organic solvents that are liquid at room temperature> An example of an organic solvent that is liquid at room temperature is described below.
[0335] The organic solvent, which is liquid at room temperature, is preferably an aprotic organic solvent. For example, one or more of the following can be used: ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, chloroethylene carbonate, vinylene carbonate, γ-butyrolactone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate (EP), propyl propionate (PP), methyl butyrate, 1,3-dioxane, 1,4-dioxane, dimethoxyethane (DME), dimethyl sulfoxide, diethyl ether, methyl diglyme, acetonitrile, benzonitrile, tetrahydrofuran, sulfolane, sultone, etc.
[0336] By using one or more flame-retardant and non-volatile ionic liquids (room-temperature molten salts) as organic solvents that are liquid at room temperature, it is possible to prevent the battery cell from rupturing and igniting even if the internal temperature rises due to an internal short circuit or overcharging. Ionic liquids consist of cations and anions, and include organic cations and anions. Examples of organic cations used in organic solvents include aliphatic onium cations such as quaternary ammonium cations, tertiary sulfonium cations, and quaternary phosphonium cations, or aromatic cations such as imidazolium cations and pyridinium cations. Examples of anions used in organic solvents include monovalent amide anions, monovalent methide anions, fluorosulfonic acid anions, perfluoroalkyl sulfonate anions, tetrafluoroborate anions, perfluoroalkyl borate anions, hexafluorophosphate anions, or perfluoroalkyl phosphate anions.
[0337] Examples of lithium salts to be dissolved in the above organic solvent include LiPF6, LiClO4, LiAsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO4, and Li2B. 10 Cl 10 Li2B 12 Cl 12 One or more selected from LiCF3SO3, LiC4F9SO3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2)2, LiN(C4F9SO2)(CF3SO2), and LiN(C2F5SO2)2 can be used.
[0338] <Additives> The above organic solvent may contain additives. These additives can suppress the reaction and decomposition of the electrolyte that may occur on the positive or negative electrode surface when the secondary battery is operated at high voltage and / or high temperature. Examples of additives include vinylene carbonate (VC), propane sultone (PS), tert-butylbenzene (TBB), fluoroethylene carbonate (FEC), and lithium bis(oxalate) borate (LiBOB). LiBOB is particularly preferred because it readily forms a good film. VC or FEC are preferred because they can form a good film on the negative electrode during aging or initial charging of the secondary battery, improving its cycle characteristics.
[0339] Dinitrile compounds can be used as additives. Specific examples of dinitrile compounds include succinonitrile, glutalonitrile, adiponitrile (ADN), or ethylene glycol bis(propionitrile) ether (EGBE). One or more of these dinitrile compounds can be used as additives.
[0340] Furthermore, fluorobenzene may be added to the above organic solvent. The concentration of the additive can be, for example, 0.1 wt% to 5 wt% relative to the total electrolyte. PS or EGBE is preferred because it can form a good film on the positive electrode during charging and discharging, improving cycle characteristics. FB is preferred because it improves the wettability of the organic solvent to the positive and negative electrodes.
[0341] The electrolyte does not need to be liquid at room temperature; a semi-solid material called a polymer gel electrolyte may be used as the organic solvent. Using a polymer gel electrolyte enhances safety against leakage and other issues. It also allows for thinner and lighter battery cells.
[0342] As the polymer to be gelled, silicone gels, acrylic gels, acrylonitrile gels, polyethylene oxide-based gels, polypropylene oxide-based gels, fluorine-based polymer gels, and the like can be used.
[0343] Examples of polymers that can be used include polymers having a polyalkylene oxide structure such as polyethylene oxide (PEO), PVDF, polyacrylonitrile, and copolymers containing these. For example, PVDF-HFP, a copolymer of PVDF and hexafluoropropylene (HFP), can be used. The resulting polymer may also have a porous structure.
[0344] [Separator] When the electrolyte contains an electrolyte solution, a separator is placed between the positive and negative electrodes. The separator can be made from materials such as paper or other cellulose fibers, nonwoven fabrics, glass fibers, ceramics, or porous films made of nylon (polyamide), vinylon (polyvinyl alcohol-based fiber), polyester, acrylic, polyolefin, polyimide, or polyurethane. It is preferable that the separator be processed into a bag shape and positioned to enclose either the positive or negative electrode.
[0345] The separator may have a multilayer structure. For example, an organic material film such as polypropylene or polyethylene can be coated with a ceramic material, hydroxide material, fluorine material, polyamide material, or a mixture thereof. Examples of ceramic materials include aluminum oxide particles, silicon oxide particles, and magnesium oxide. Examples of hydroxide materials include magnesium hydroxide and aluminum hydroxide. Examples of fluorine materials include PVDF and polytetrafluoroethylene. Examples of polyamide materials include nylon and aramid (meta-aramid and para-aramid).
[0346] Coating with ceramic materials improves oxidation resistance, suppressing separator degradation during high-voltage charging and improving the reliability of secondary batteries. Coating with fluorine-based materials facilitates better adhesion between the separator and electrodes, improving output characteristics. Coating with polyamide materials, particularly aramid, improves heat resistance, thereby enhancing the safety of secondary batteries.
[0347] For example, a polypropylene film may be coated on both sides with a mixture of aluminum oxide and aramid. Alternatively, the side of the polypropylene film in contact with the positive electrode may be coated with a mixture of aluminum oxide and aramid, and the side in contact with the negative electrode may be coated with a fluorine-based material.
[0348] By using a multi-layered separator, the safety of the secondary battery can be maintained even if the overall thickness of the separator is thin, thus increasing the capacity per unit volume of the secondary battery.
[0349] [Exterior] The battery's outer casing can be made of metal materials such as aluminum, stainless steel, or titanium, or of resin material. A film-like outer casing can also be used. For example, a three-layer film can be used, consisting of a film made of polyethylene, polypropylene, polycarbonate, ionomer, or polyamide, on which a highly flexible metal thin film or metal foil made of aluminum, stainless steel, titanium, copper, or nickel is placed. Furthermore, an insulating synthetic resin film, such as a polyamide resin or polyester resin, is applied to the metal thin film as the outer surface of the casing. Such a multilayer film can be called a laminate film. In this case, the laminate film may be referred to by the name of the metal layer, such as aluminum laminate film, stainless steel laminate film, titanium laminate film, copper laminate film, or nickel laminate film.
[0350] The contents of this embodiment can be freely combined with the contents of other embodiments.
[0351] (Embodiment 4) In this embodiment, we will describe an example of the shape of a secondary battery having a positive electrode manufactured by the manufacturing method described in the previous embodiment.
[0352] [Coin-type rechargeable battery] An example of a coin-type rechargeable battery is described below. Figure 13(A) is an exploded perspective view of a coin-type (single-layer flat type) rechargeable battery, Figure 13(B) is an external view, and Figure 13(C) is a cross-sectional view thereof. Coin-type rechargeable batteries are mainly used in small electronic devices.
[0353] Note that Figure 13(A) is a schematic diagram to show the overlapping of components (up / down relationship and positional relationship) for clarity. Therefore, Figures 13(A) and 13(B) are not perfectly identical corresponding diagrams.
[0354] In Figure 13(A), the positive electrode 304, separator 310, negative electrode 307, spacer 322, and washer 312 are stacked. These are sealed with a gasket between the negative electrode can 302 and the positive electrode can 301. Note that the gasket for sealing is not shown in Figure 13(A). The spacer 322 and washer 312 are used to protect the inside or fix the position within the can when the positive electrode can 301 and the negative electrode can 302 are crimped together. The spacer 322 and washer 312 are made of stainless steel or insulating material.
[0355] The positive electrode 304 is a laminated structure in which a positive electrode active material layer 306 is formed on a positive electrode current collector 305.
[0356] Figure 13(B) is a perspective view of the completed coin-type rechargeable battery.
[0357] The coin-type secondary battery 300 has a positive electrode casing 301, which also serves as the positive electrode terminal, and a negative electrode casing 302, which also serves as the negative electrode terminal, insulated and sealed by a gasket 303 made of polypropylene or the like. The positive electrode 304 is formed by a positive electrode current collector 305 and a positive electrode active material layer 306 provided in contact with it. The negative electrode 307 is formed by a negative electrode current collector 308 and a negative electrode active material layer 309 provided in contact with it. Furthermore, the negative electrode 307 is not limited to a laminated structure, and lithium metal foil or a lithium-aluminum alloy foil may be used.
[0358] Furthermore, the positive electrode 304 and negative electrode 307 used in the coin-type secondary battery 300 may each have the active material layer formed on only one side.
[0359] The positive electrode can 301 and the negative electrode can 302 can be made of metals such as nickel, aluminum, or titanium, or alloys thereof, or alloys of these with other metals (e.g., stainless steel), which are corrosion-resistant to the electrolyte. Furthermore, it is preferable to coat them with nickel or aluminum to prevent corrosion caused by the electrolyte. The positive electrode can 301 is electrically connected to the positive electrode 304, and the negative electrode can 302 is electrically connected to the negative electrode 307.
[0360] The negative electrode 307, positive electrode 304, and separator 310 are immersed in an electrolyte solution, and as shown in Figure 13(C), the positive electrode can 301 is placed at the bottom, and the positive electrode 304, separator 310, negative electrode 307, and negative electrode can 302 are stacked in this order. The positive electrode can 301 and negative electrode can 302 are then crimped together via a gasket 303 to manufacture a coin-type secondary battery 300.
[0361] By having the above configuration, a coin-type secondary battery 300 with high discharge capacity and excellent cycle characteristics can be obtained.
[0362] [Cylindrical rechargeable battery] An example of a cylindrical secondary battery will be explained with reference to Figure 14(A). As shown in Figure 14(A), the cylindrical secondary battery 616 has a positive electrode cap (battery cover) 601 on the top surface and a battery casing (outer casing) 602 on the sides and bottom. The positive electrode cap 601 and the battery casing (outer casing) 602 are insulated from each other by a gasket (insulating packing) 610.
[0363] Figure 14(B) is a schematic diagram showing a cross-section of a cylindrical secondary battery. The cylindrical secondary battery shown in Figure 14(B) has a positive electrode cap (battery cover) 601 on the top surface and a battery casing (outer casing) 602 on the sides and bottom. The positive electrode cap and the battery casing (outer casing) 602 are insulated from each other by a gasket (insulating packing) 610.
[0364] Inside the hollow cylindrical battery can 602, a battery element is provided, in which a strip-shaped positive electrode 604 and a negative electrode 606 are wound with a separator 605 in between. Although not shown, the battery element is wound around a central axis. The battery can 602 is closed at one end and open at the other. The battery can 602 can be made of metals such as nickel, aluminum, or titanium, or alloys thereof, or alloys of these with other metals (e.g., stainless steel), which are corrosion resistant to the electrolyte. Furthermore, it is preferable to coat the battery can 602 with nickel and aluminum, etc., to prevent corrosion by the electrolyte. Inside the battery can 602, the battery element in which the positive electrode, negative electrode, and separator are wound is sandwiched between a pair of opposing insulating plates 608 and insulating plate 609. In addition, a non-aqueous electrolyte (not shown) is injected into the inside of the battery can 602 in which the battery element is provided. The non-aqueous electrolyte can be the same as that used in coin-type secondary batteries.
[0365] Since the positive and negative electrodes used in cylindrical storage batteries are wound, it is preferable to form the active material on both sides of the current collector.
[0366] By using the positive electrode active material particles 100 described in Embodiments 1 and 2 as the positive electrode 604, a cylindrical secondary battery 616 with high capacity, high discharge capacity, and excellent cycle characteristics can be obtained.
[0367] A positive electrode terminal (positive electrode current collector lead) 603 is connected to the positive electrode 604, and a negative electrode terminal (negative electrode current collector lead) 607 is connected to the negative electrode 606. Aluminum can be used for the positive electrode terminal 603, and copper or other metal materials can be used for the negative electrode terminal 607. The positive electrode terminal 603 is resistance-welded to the safety valve mechanism 613, and the negative electrode terminal 607 is resistance-welded to the bottom of the battery can 602. The safety valve mechanism 613 is electrically connected to the positive electrode cap 601 via a PTC (Positive Temperature Coefficient) element 611. The safety valve mechanism 613 disconnects the electrical connection between the positive electrode cap 601 and the positive electrode 604 when the internal pressure of the battery exceeds a predetermined threshold. The PTC element 611 is a thermal resistance element whose resistance increases when the temperature rises, limiting the current and preventing abnormal heat generation. Barium titanate (BaTiO3) based semiconductor ceramics can be used for the PTC element.
[0368] Figure 14(C) shows an example of an energy storage system 615. The energy storage system 615 has multiple secondary batteries 616. The positive electrode of each secondary battery is in contact with a conductor 624 separated by an insulator 625 and is electrically connected. The conductor 624 is electrically connected to a control circuit 620 via wiring 623. The negative electrode of each secondary battery is also electrically connected to the control circuit 620 via wiring 626. The control circuit 620 can be a charge / discharge control circuit that performs charging and discharging, or a protection circuit that prevents overcharging and / or over-discharging.
[0369] Figure 14(D) shows an example of an energy storage system 615. The energy storage system 615 has multiple secondary batteries 616, which are sandwiched between conductive plates 628 and 614. The multiple secondary batteries 616 are electrically connected to conductive plates 628 and 614 by wiring 627. The multiple secondary batteries 616 may be connected in parallel, in series, or connected in parallel and then in series. By configuring an energy storage system 615 with multiple secondary batteries 616, a large amount of power can be extracted.
[0370] Multiple secondary batteries 616 may be connected in parallel and then further connected in series.
[0371] Furthermore, a temperature control device may be provided between the multiple secondary batteries 616. When a secondary battery 616 overheats, it can be cooled by the temperature control device, and when a secondary battery 616 becomes too cold, it can be heated by the temperature control device. This makes the performance of the energy storage system 615 less susceptible to the influence of ambient temperature.
[0372] Furthermore, in Figure 14(D), the energy storage system 615 is electrically connected to the control circuit 620 via wiring 621 and wiring 622. Wiring 621 is electrically connected to the positive terminals of the multiple secondary batteries 616 via conductive plate 628, and wiring 622 is electrically connected to the negative terminals of the multiple secondary batteries 616 via conductive plate 614.
[0373] <Laminated rechargeable battery> Next, an example of an external view of a laminate-type secondary battery is shown in Figures 15(A) and 15(B). Figures 15(A) and 15(B) show a positive electrode 503, a negative electrode 506, a separator 507, an outer casing 509, a positive electrode lead electrode 510, and a negative electrode lead electrode 511.
[0374] Figure 16(A) shows the external view of the positive electrode 503 and the negative electrode 506. The positive electrode 503 has a positive electrode current collector 501, and the positive electrode active material layer 502 is formed on the surface of the positive electrode current collector 501. The positive electrode 503 also has a region where the positive electrode current collector 501 is partially exposed (hereinafter referred to as the tab region). The negative electrode 506 has a negative electrode current collector 504, and the negative electrode active material layer 505 is formed on the surface of the negative electrode current collector 504. The negative electrode 506 also has a region where the negative electrode current collector 504 is partially exposed, i.e., the tab region. Note that the area or shape of the tab regions of the positive and negative electrodes are not limited to the example shown in Figure 16(A).
[0375] <Method for manufacturing laminated rechargeable batteries> An example of a method for manufacturing a laminate-type secondary battery, whose external view is shown in Figure 15(A), will be explained using Figures 16(B) and 16(C).
[0376] First, the negative electrode 506, separator 507, and positive electrode 503 are stacked. Figure 16(B) shows the stacked negative electrode 506, separator 507, and positive electrode 503. Here, an example using 5 sets of negative electrodes and 4 sets of positive electrodes is shown. This can also be called a laminate consisting of negative electrodes, separators, and positive electrodes. Next, the tab regions of the positive electrode 503 are joined together, and the positive electrode lead electrode 510 is joined to the tab region of the outermost positive electrode. For joining, ultrasonic welding, for example, can be used. Similarly, the tab regions of the negative electrode 506 are joined together, and the negative electrode lead electrode 511 is joined to the tab region of the outermost negative electrode.
[0377] Next, the negative electrode 506, separator 507, and positive electrode 503 are placed on the outer casing 509.
[0378] Next, as shown in Figure 16(C), the outer casing 509 is bent at the portion indicated by the dashed line. Then, the outer periphery of the outer casing 509 is joined. For joining, for example, heat compression bonding may be used. At this time, a region that is not joined (hereinafter referred to as the inlet) is provided on a part (or one side) of the outer casing 509 so that the electrolyte can be added later.
[0379] Next, the electrolyte is introduced into the inside of the outer casing 509 through an inlet provided in the outer casing 509. It is preferable to introduce the electrolyte under a reduced pressure atmosphere or an inert atmosphere. Finally, the inlet is sealed. In this way, a laminate-type secondary battery 500 can be manufactured.
[0380] By using the positive electrode active material particles 100 described in Embodiments 1 and 2 as the positive electrode 503, a secondary battery 500 with high capacity, high discharge capacity, and excellent cycle characteristics can be obtained.
[0381] The contents of this embodiment can be freely combined with the contents of other embodiments.
[0382] (Embodiment 5) In this embodiment, as an example of mounting a secondary battery in a vehicle, an example is shown in which a lithium-ion battery according to one aspect of the present invention is mounted in a motorcycle or a bicycle.
[0383] Figure 17(A) shows an example of an electric bicycle using a power storage device according to one aspect of the present invention. The power storage device according to one aspect of the present invention can be applied to the electric bicycle 8700 shown in Figure 17(A). The power storage device according to one aspect of the present invention includes, for example, a plurality of batteries and a protection circuit.
[0384] The electric bicycle 8700 is equipped with a power storage device 8702. The power storage device 8702 can supply electricity to a motor that assists the rider. The power storage device 8702 is also portable, and Figure 17(B) shows it detached from the bicycle. The power storage device 8702 also incorporates multiple storage batteries 8701, which are part of a power storage device according to one embodiment of the present invention, and the remaining battery level and other information can be displayed on a display unit 8703. The power storage device 8702 also has a control circuit 8704 that can control the charging of the secondary battery or detect abnormalities. The control circuit 8704 is electrically connected to the positive and negative electrodes of the storage battery 8701. Furthermore, by combining it with a secondary battery that uses the positive electrode active material particles 100 described in Embodiments 1 and 2 as the positive electrode, a synergistic effect on safety can be obtained. The secondary battery and control circuit 8704 using the positive electrode active material particles 100 described in Embodiments 1 and 2 as the positive electrode can greatly contribute to eliminating accidents such as fires caused by secondary batteries.
[0385] Figure 17(C) shows an example of a motorcycle using a power storage device according to one embodiment of the present invention. The scooter 8600 shown in Figure 17(C) is equipped with a power storage device 8602, side mirrors 8601, and turn signals 8603. The power storage device 8602 can supply electricity to the turn signals 8603. Furthermore, the power storage device 8602, which houses multiple secondary batteries using the positive electrode active material particles 100 described in Embodiments 1 and 2 as the positive electrode, can have a high capacity and contribute to miniaturization.
[0386] Furthermore, the scooter 8600 shown in Figure 17(C) can accommodate the power storage device 8602 in the under-seat storage compartment 8604. The power storage device 8602 can be stored in the under-seat storage compartment 8604 even if the under-seat storage compartment 8604 is small.
[0387] The contents of this embodiment can be freely combined with the contents of other embodiments.
[0388] (Embodiment 6) This embodiment describes an example of mounting a secondary battery, which is one aspect of the present invention, in an electronic device. Examples of electronic devices on which a secondary battery is mounted include television equipment (also called televisions or television receivers), monitors for computers, digital cameras, digital video cameras, digital photo frames, mobile phones (also called mobile phones or mobile phone devices), portable game consoles, personal information terminals, sound playback devices, and large game machines such as pachinko machines. Personal information terminals include notebook personal computers, tablet terminals, e-book readers, and mobile phones.
[0389] Figure 18(A) shows an example of a mobile phone. The mobile phone 2100 includes a display unit 2102 built into the housing 2101, as well as operation buttons 2103, an external connection port 2104, a speaker 2105, a microphone 2106, and the like. The mobile phone 2100 also has a secondary battery 2107. By providing a secondary battery 2107 that uses the positive electrode active material particles 100 described in Embodiments 1 and 2 as the positive electrode, a high capacity can be achieved, and a configuration that can accommodate space saving due to the miniaturization of the housing can be realized.
[0390] The mobile phone 2100 can run various applications such as making phone calls, sending emails, reading and creating documents, playing music, communicating on the internet, and playing computer games.
[0391] The operation button 2103 can be assigned various functions, including time setting, power on / off operation, wireless communication on / off operation, silent mode activation / deactivation, and power saving mode activation / deactivation. For example, the function of the operation button 2103 can be freely configured by the operating system built into the mobile phone 2100.
[0392] Furthermore, the 2100 mobile phone is capable of performing standardized short-range wireless communication. For example, it can communicate with a wireless headset to enable hands-free calling.
[0393] Furthermore, the mobile phone 2100 is equipped with an external connection port 2104, which allows it to directly exchange data with other information terminals via a connector. It can also be charged via the external connection port 2104. However, charging may be performed wirelessly without using the external connection port 2104.
[0394] Furthermore, it is preferable that the mobile phone 2100 has sensors. Preferably, the sensors include, for example, human body sensors such as fingerprint sensors, pulse sensors, and body temperature sensors, as well as touch sensors, pressure sensors, or acceleration sensors.
[0395] Figure 18(B) shows an unmanned aerial vehicle 2300 having multiple rotors 2302. The unmanned aerial vehicle 2300 is sometimes called a drone. The unmanned aerial vehicle 2300 has a secondary battery 2301, a camera 2303, and an antenna (not shown), which are embodiments of the present invention. The unmanned aerial vehicle 2300 can be remotely controlled via the antenna. The secondary battery using the positive electrode active material particles 100 described in Embodiments 1 and 2 as the positive electrode has a high energy density and high safety, so it can be used safely for a long period of time over a long period of time and is suitable as a secondary battery to be mounted on the unmanned aerial vehicle 2300.
[0396] Figure 18(C) shows an example of a robot. The robot 6400 shown in Figure 18(C) is equipped with a secondary battery 6409, an illuminance sensor 6401, a microphone 6402, an upper camera 6403, a speaker 6404, a display unit 6405, a lower camera 6406, an obstacle sensor 6407, a movement mechanism 6408, a computing device, and the like.
[0397] Microphone 6402 has the function of detecting the user's voice and ambient sounds. Speaker 6404 has the function of emitting sound. Robot 6400 can communicate with the user using microphone 6402 and speaker 6404.
[0398] The display unit 6405 has the function of displaying various types of information. The robot 6400 can display the user's desired information on the display unit 6405. The display unit 6405 may be equipped with a touch panel. The display unit 6405 may also be a detachable information terminal, and by installing it in a fixed position on the robot 6400, charging and data transfer can be enabled.
[0399] The upper camera 6403 and the lower camera 6406 have the function of imaging the area around the robot 6400. In addition, the obstacle sensor 6407 can detect the presence or absence of obstacles in the direction of travel when the robot 6400 moves forward using the movement mechanism 6408. The robot 6400 can recognize its surrounding environment and move safely using the upper camera 6403, the lower camera 6406 and the obstacle sensor 6407.
[0400] The robot 6400 is equipped with a secondary battery 6409 according to one aspect of the present invention and a semiconductor device or electronic components in its internal region. The secondary battery using the positive electrode active material particles 100 described in Embodiments 1 and 2 as the positive electrode has a high energy density and high safety, so it can be used safely for a long period of time, and is suitable as the secondary battery 6409 to be mounted on the robot 6400.
[0401] The robot 6500 shown in Figure 18(D) is equipped with a lithium-ion battery 6505, a computing unit 6510, an illuminance sensor 6501, a microphone 6502, an upper camera 6503, a speaker 6504, a lower camera 6506, and an obstacle sensor 6507. Note that a humanoid robot is shown here as an example.
[0402] In the robot 6500, the above-mentioned semiconductor devices and / or electronic components can be used in the computing device 6510, the illuminance sensor 6501, the upper camera 6503, the lower camera 6506, and the obstacle sensor 6507, etc.
[0403] Microphone 6502 has the function of detecting the user's voice and ambient sounds. Speaker 6504 has the function of emitting sound. Robot 6500 can communicate with the user using microphone 6502 and speaker 6504.
[0404] The upper camera 6503 and lower camera 6506 have the function of imaging the area around the robot 6500. In addition, the obstacle sensor 6507 can detect the presence or absence of obstacles in the direction of travel when the robot 6500 moves forward on two legs. Using the upper camera 6503, lower camera 6506 and obstacle sensor 6507, the robot 6500 can perceive its surrounding environment and move safely.
[0405] Figure 18(E) shows an example of a cleaning robot. The cleaning robot 6300 has a display unit 6302 located on the top surface of the housing 6301, multiple cameras 6303 located on the sides, a brush 6304, operation buttons 6305, a secondary battery 6306, and various sensors. Although not shown, the cleaning robot 6300 is equipped with wheels, a suction port, etc. The cleaning robot 6300 is self-propelled, can detect dirt 6310, and can suck up the dirt from a suction port located on the bottom surface.
[0406] The cleaning robot 6300 can analyze images captured by the camera 6303 to determine the presence or absence of obstacles such as walls, furniture, or steps. Furthermore, if the image analysis detects an object that may become entangled in the brush 6304, such as wiring, the rotation of the brush 6304 can be stopped. The cleaning robot 6300 is equipped with a secondary battery 6306 according to one embodiment of the present invention and a semiconductor device or electronic component in its internal region. The secondary battery using the positive electrode active material particles 100 described in Embodiments 1 and 2 as the positive electrode has a high energy density and high safety, so it can be used safely for a long period of time over a long period of time and is suitable as the secondary battery 6306 to be installed in the cleaning robot 6300.
[0407] Figure 19(A) shows an example of a wearable device. Wearable devices use rechargeable batteries as a power source. Furthermore, in order to enhance splash resistance, water resistance, or dust resistance when used by users in daily life or outdoors, there is a demand for wearable devices that can be charged wirelessly in addition to wired charging with exposed connectors.
[0408] For example, a secondary battery according to one embodiment of the present invention can be mounted in a spectacle-type device 4000 as shown in Figure 19(A). The spectacle-type device 4000 has a frame 4000a and a display unit 4000b. By mounting the secondary battery in the temple portion of the curved frame 4000a, a lightweight spectacle-type device 4000 can be made with good weight balance and a long continuous usage time. The secondary battery using the positive electrode active material particles 100 described in Embodiments 1 and 2 as the positive electrode has a high energy density and can realize a configuration that can accommodate space saving due to the miniaturization of the housing.
[0409] Furthermore, a secondary battery according to one aspect of the present invention can be mounted in the headset-type device 4001. The headset-type device 4001 has at least a microphone section 4001a, a flexible pipe 4001b, and an earphone section 4001c. The secondary battery can be provided in the flexible pipe 4001b or in the earphone section 4001c. The secondary battery using the positive electrode active material particles 100 described in Embodiments 1 and 2 as the positive electrode has a high energy density and can realize a configuration that can accommodate space saving due to the miniaturization of the housing.
[0410] Furthermore, a secondary battery according to one embodiment of the present invention can be mounted on a device 4002 that can be directly attached to the body. The secondary battery 4002b can be provided inside the thin housing 4002a of the device 4002. The secondary battery using the positive electrode active material particles 100 described in Embodiments 1 and 2 as the positive electrode has a high energy density and can realize a configuration that can accommodate space saving due to the miniaturization of the housing.
[0411] Furthermore, a secondary battery according to one embodiment of the present invention can be mounted on a device 4003 that can be attached to clothing. A secondary battery 4003b can be provided inside the thin housing 4003a of the device 4003. A secondary battery using the positive electrode active material particles 100 described in Embodiments 1 and 2 as the positive electrode has a high energy density and can realize a configuration that can accommodate space saving due to the miniaturization of the housing.
[0412] Furthermore, a secondary battery according to one aspect of the present invention can be mounted on the belt-type device 4006. The belt-type device 4006 has a belt portion 4006a and a wireless power supply and receiving portion 4006b, and a secondary battery can be mounted in the internal region of the belt portion 4006a. The secondary battery using the positive electrode active material particles 100 described in Embodiments 1 and 2 as the positive electrode has a high energy density and can realize a configuration that can accommodate space saving due to the miniaturization of the housing.
[0413] Furthermore, a secondary battery according to one embodiment of the present invention can be mounted in the wristwatch-type device 4005. The wristwatch-type device 4005 has a display unit 4005a and a belt unit 4005b, and the secondary battery can be provided in either the display unit 4005a or the belt unit 4005b. The secondary battery using the positive electrode active material particles 100 described in Embodiments 1 and 2 as the positive electrode has a high energy density and can realize a configuration that can accommodate space saving due to the miniaturization of the housing.
[0414] The display unit 4005a can display not only the time, but also various other information such as incoming emails or phone calls.
[0415] Furthermore, since the wristwatch-type device 4005 is a wearable device that is worn directly on the wrist, it may be equipped with sensors to measure the user's pulse, blood pressure, etc. It can accumulate data on the user's exercise level and health, and manage their health.
[0416] Figure 19(B) shows a perspective view of the wristwatch-type device 4005 after it has been removed from the arm.
[0417] A side view is also shown in Figure 19(C). Figure 19(C) shows how the secondary battery 913 is built into the internal region. The secondary battery 913 is the secondary battery shown in Embodiment 4. The secondary battery 913 is located in a position that overlaps with the display unit 4005a, allowing for high density and high capacity, as well as being small and lightweight.
[0418] Since the wristwatch-type device 4005 is required to be small and lightweight, by using the positive electrode active material particles 100 described in Embodiments 1 and 2, etc., as the positive electrode of the secondary battery 913, a secondary battery 913 with high energy density and small size can be made.
[0419] The contents of this embodiment can be freely combined with the contents of other embodiments. [Examples]
[0420] In this embodiment, lithium cobalt oxide that has undergone initial heating was mixed with magnesium, nickel, and aluminum to produce positive electrode active material particles, which were prepared in accordance with Embodiment 2, and their properties were evaluated.
[0421] <Fabrication of positive electrode active material particles> The preparation of the positive electrode active material particles in this embodiment will be explained with reference to the preparation method shown in Figures 11(A) to 12(B).
[0422] <Sample 1> In step S10 of Figure 11(A), commercially available lithium cobalt oxide (Cellseed C-10N, manufactured by Nippon Chemical Industrial Co., Ltd.) was prepared as the LiCoO2 (starting material) having cobalt as the transition metal M and no particular additive element A. In step S15, lithium fluoride was prepared as the second lithium source (Li source 2). In step S16, the lithium cobalt oxide and lithium fluoride were mixed, and then in step S17, as initial heating, the mixture was placed in a crucible, covered, and heated in a muffle furnace at 850°C for 2 hours. The muffle furnace was then subjected to an oxygen atmosphere and no flow occurred (O2 purging). In the mixing in step S16, the lithium fluoride was weighed and mixed so that the number of moles of lithium cobalt oxide in step S10 was 0.33 (0.33 mol%) when the number of moles of lithium cobalt oxide in step S10 was 100. A ball mill was used for mixing, and zirconium oxide balls were used as the media. After mixing, the mixture was sieved using a sieve with a mesh size of 300 μm.
[0423] According to steps S21 to S23 shown in Figure 12(A) and steps S41 to S43 shown in Figure 12(B), element A was added separately as Mg and F, and Ni and Al.
[0424] Following step S21 shown in Figure 12(A), lithium fluoride (LiF) was prepared as the F source and magnesium fluoride (MgF2) was prepared as the Mg source. LiF and MgF2 were weighed in a molar ratio of 1:3. Next, lithium fluoride and magnesium fluoride were mixed in dehydrated acetone (step S22) and stirred at a rotational speed of 400 rpm for 12 hours to prepare the additive element source (A1 source). A ball mill was used for mixing, and zirconium oxide balls were used as the grinding medium. After mixing, the mixture was sieved through a sieve with a mesh size of 300 μm to obtain the A1 source (step S23).
[0425] Next, in step S31, when the number of moles of lithium cobalt oxide is set to 100, the amount of magnesium fluoride contained in source A1 is weighed so that the number of moles is 1 (1 mol%), and it is mixed dry with the lithium cobalt oxide after initial heating. At this time, it is stirred at a rotational speed of 150 rpm for 1 hour. This is a condition in which less force is applied to the powder than when stirring to obtain source A1. Finally, it is sieved with a sieve having a mesh size of 300 μm to obtain a mixture 903 with uniform particle size (step S32).
[0426] Next, in step S33, the mixture 903 was heated. The heating conditions were 900°C for 20 hours. During heating, the crucible containing the mixture 903 was covered. The crucible was kept in an oxygen atmosphere, and the entry and exit of oxygen was blocked (purged). By heating, a composite oxide containing Mg and F was obtained (step S34a).
[0427] Next, in step S51, the composite oxide and the additive element source (A2 source) were mixed. Nickel hydroxide was prepared as the Ni source and aluminum hydroxide as the Al source according to step S41 shown in Figure 12(B). When the number of moles of lithium cobaltate is set to 100, the number of moles of nickel hydroxide contained in the A2 source was 0.5 (0.5 mol%), and the number of moles of aluminum hydroxide was 0.5 (0.5 mol%). These were weighed and mixed dry with the composite oxide. At this time, the mixture was stirred at a rotational speed of 150 rpm for 1 hour. A ball mill was used for mixing, and zirconium oxide balls were used as the media. After mixing, the mixture was sieved through a sieve with a mesh size of 300 μm to obtain a mixture 904 with uniform particle size (step S52).
[0428] Next, in step S53, the mixture 904 was heated. The heating conditions were 850°C for 10 hours. During heating, the crucible containing the mixture 904 was covered. The crucible was kept in an oxygen-containing atmosphere, and the entry and exit of this oxygen was blocked (purged). By heating, lithium cobaltate containing Mg, F, Ni, and Al was obtained (step S54). The positive electrode active material particles (composite oxide) obtained in this way were designated as Sample 1.
[0429] <Sample 2> Sample 2 was prepared in the same manner as Sample 1, except that the heating temperature was changed to 875°C in step S17.
[0430] <Sample 3> Sample 3 was prepared in the same manner as Sample 1, except that the heating temperature was changed to 900°C in step S17.
[0431] <Sample 4> Sample 4 was prepared in the same manner as Sample 1, except that the heating temperature was changed to 925°C in step S17.
[0432] <Sample 5> Sample 5 was prepared in the same manner as Sample 1, except that the heating temperature was changed to 950°C in step S17.
[0433] <STEM-EDX Analysis> Cross-sectional STEM-EDX analysis was performed on the edge region of the surface layer portion of Sample 3. The above cross-sectional STEM-EDX analysis is a line analysis in the depth direction from the outside toward the inside of the sample.
[0434] As a pretreatment before being subjected to analysis, Sample 3 was thinned by the FIB method (μ-sampling method).
[0435] The following apparatus and conditions were used for STEM and EDX. ≪STEM Observation≫ Scanning Transmission Electron Microscope: JEM-ARM200F NEOARM manufactured by JEOL Ltd. Observation conditions Acceleration voltage: 200 kV Magnification accuracy: ±3% ≪EDX≫ Analysis method: Energy dispersive X-ray spectroscopy (EDX) Scanning Transmission Electron Microscope: JEM-ARM200F NEOARM manufactured by JEOL Ltd. Acceleration voltage: 200 kV Measurement mode: STEM mode Elemental analyzer: Dual SDD detector JED-2300T manufactured by JEOL Ltd. X-ray detection element area: 158 mm 2 ×2 Measurement conditions Dell time: 50 μsec Number of frames: 400 Number of captured pixels: 256×256
[0436] The cross-sectional STEM-EDX analysis location of Sample 3 is shown in Figure 20. Figure 20 is an enlarged HAADF-STEM image of the edge region of Sample 3, and the surface of the edge region is presumed to be the (10-2) plane.
[0437] The results of the cross-sectional STEM-EDX analysis of Sample 3 are shown in Figure 21(A) to Figure 22(B).
[0438] <Edge Region> Figure 21(A) is a graph showing the results of cross-sectional STEM-EDX radiation analysis in the edge region of sample 3, with the vertical axis representing the amount of characteristic X-rays detected (counts), and Figure 21(B) is a graph of the same data as in Figure 21(A), but with the vertical axis representing the quantitative value of concentration (atomic%). In the horizontal axis of both Figure 21(A) and Figure 21(B), the reference point on the particle surface is estimated to be at a position of 10 nm. The position of the reference point was determined by the method described in the previous embodiment (using 50% of the count of characteristic X-rays for oxygen).
[0439] Furthermore, Figure 22(A) is a graph with the vertical axis of Figure 21(A) magnified, and Figure 22(B) is a graph with the vertical axis of Figure 21(B) magnified.
[0440] Table 1 shows the peak value (also called the maximum value) and its position of the concentration of additive element A, based on the STEM-EDX analysis results shown in Figure 22(B).
[0441] Note that the quantitative values of concentrations (atomic %) in the above figure and Table 1 were calculated by setting the sum of the concentrations of carbon, oxygen, fluorine, magnesium, aluminum, silicon, phosphorus, sulfur, calcium, titanium, iron, cobalt, nickel, and gallium to 100%. Since fluorine was below the detection limit of 1.5 atomic percent, the maximum concentration and its position at that point are not indicated.
[0442] [Table 1]
[0443] As shown in Figures 21(A) to 22(B) and Table 1, the edge region of Sample 3 was confirmed to contain magnesium, nickel, and aluminum. Furthermore, the concentration and detection peaks of magnesium had a steep peak shape, with most of its convex shape confined within a 10 nm range, indicating that a large amount of magnesium is present on the surface side of the surface layer of the particles in Sample 3. Similarly, the concentration and detection peaks of nickel also had a steep peak shape, with most of its convex shape confined within a 10 nm range, indicating that a large amount of nickel is present on the surface side of the surface layer of the particles in Sample 3. On the other hand, the concentration and detection peaks of aluminum were asymmetrical and had a gentler shape towards the interior of the particles, compared to those of magnesium and nickel. Specifically, the slope from the peak top towards the interior was gentler compared to the slope from the peak top towards the surface. In other words, it was confirmed that the detection amount and concentration of aluminum decreased gently from the surface layer towards the interior of the particles in Sample 3.
[0444] In other words, magnesium and nickel were found to have steep peaks within 10 nm from the reference point of the Sample 3 particles toward the interior of the particles. Furthermore, aluminum was found to have asymmetrical, gently sloping peaks toward the interior of the particles beyond 10 nm from the reference point of the Sample 3 particles toward the interior of the particles.
[0445] Furthermore, the nickel distribution in the edge region of sample 3 largely overlapped with the magnesium distribution, and the difference in depth between the peak of nickel concentration or detected amount and the peak of magnesium concentration or detected amount was within 1 nm, specifically within 0.5 nm.
[0446] Furthermore, the magnesium concentration peak and the magnesium concentration peak in the edge region of Sample 3 were present within a depth of 3 nm from the reference point toward the center. More specifically, the magnesium concentration peak in the edge region of Sample 3 was present within a depth of 1 nm from the reference point toward the center. Furthermore, the nickel concentration peak in the edge region of Sample 3 was present within a depth of 1 nm from the reference point toward the center.
[0447] Furthermore, the aluminum concentration peak in the edge region of Sample 3 was located on the inner side of the particles of Sample 3, compared with those of magnesium and nickel.
[0448] <XPS Analysis> XPS analysis was performed on each of the surfaces of the particles of Sample 1 to Sample 5 prepared above as the analysis of the particle surfaces. The XPS measurement apparatus and conditions were as follows. Measurement apparatus: Quantera II manufactured by ULVAC-PHI, Inc. X-ray: Monochromatic Al Kα (1486.6 eV) Energy resolution: Full width at half maximum of Ag3d5 / 2 peak is 1.0 eV ± 0.1 eV or less Detection region: 100 μmφ Detector angle: 45° Measurement spectra: Wide scan, narrow scan of each detected element
[0449] The results of the XPS analysis are shown in Table 2.
[0450] [Table 2]
[0451] Table 2 shows the concentrations of each element (at%: atomic concentration) when the total concentration of lithium (Li), cobalt (Co), titanium (Ti), oxygen (O), carbon (C), fluorine (F), sulfur (S), calcium (Ca), magnesium (Mg), sodium (Na), zirconium (Zr), nickel (Ni), silicon (Si), and aluminum (Al) is set to 100 at%. Note that in this example, the analysis results are rounded, so the total may not always equal 100%.
[0452] Table 2 also shows the concentrations of magnesium (Mg / Co), nickel (Ni / Co), and aluminum (Al / Co) when the cobalt concentration is set to 1. Additionally, it shows the concentration of fluorine (F / Mg) when the magnesium concentration is set to 1.
[0453] Figure 23(A) is a graph showing the above-mentioned Mg / Co and F / Mg values for Samples 1 to 5. Figure 23(B) is a graph showing the above-mentioned Ni / Co and Al / Co values for Samples 1 to 5. The horizontal axis of the graphs in Figures 23(A) and 23(B) represents the heating temperature conditions in step S17 for each sample, and the horizontal axis of the graphs represents the respective concentration ratios.
[0454] As shown in Figure 23(A), compared to the samples where the heating temperature in step S17 was less than 900°C (Sample 1 and Sample 2), the samples where the heating temperature was 900°C or higher (Sample 3, Sample 4, and Sample 5) tended to have lower Mg / Co and F / Mg values. Furthermore, in the samples where the heating temperature in step S17 was 900°C or higher, the Mg / Co value was between 0.50 and 0.70, and the F / Mg value was between 0.10 and 0.20.
[0455] As shown in Figure 23(B), the Ni / Co and Al / Co values tended to decrease as the heating temperature in step S17 increased. Furthermore, the significant changes observed in the Ni / Co and Al / Co values between the 875°C and 900°C conditions, as seen in the Mg / Co and F / Mg values, were not observed in the Ni / Co and Al / Co values.
[0456] Next, we focused on the Mg1s peak in the XPS spectrum obtained from XPS analysis and performed an analysis. In the analysis of the Mg1s peak, the peak component derived from the O-Mg-O bond was designated as Fit Peak 1, the peak component derived from the O-Mg-F bond as Fit Peak 2, and the peak component derived from the F-Mg-F bond as Fit Peak 3. These three fit peaks were synthesized, and the ratio of the synthesized peak that minimized the difference with the Mg1s peak in the XPS spectrum obtained from the XPS analysis was calculated. The analysis results obtained by assuming that the area ratios of Fit Peak 1, Fit Peak 2, and Fit Peak 3 represent the relative abundances of the O-Mg-O bond, O-Mg-F bond, and F-Mg-F bond are shown in Table 3.
[0457] In the XPS spectrum analysis method described above, the energy value at the maximum value of Fit Peak 1 (also called the peak top) (Ep1) was referenced from the energy value at the maximum value of the Mg1s peak when MgO-coated LiCoO2 was measured separately as a standard sample. Similarly, the energy value at the maximum value of Fit Peak 3 (Ep3) was referenced from the energy value at the maximum value of the Mg1s peak when magnesium fluoride (MgF2, High Purity Chemical Laboratory MGH18XB, purity 99.9% (3N) up) was measured separately as a standard sample. Furthermore, the energy value at the maximum value of Fit Peak 2 (Ep2) was set to an intermediate value between Ep1 and Ep3. The energy value at the maximum value of a peak is also referred to as the peak position.
[0458] Furthermore, the XPS spectrum used in the XPS analysis was corrected for the energy axis so that the maximum value of the C1s peak was 284.8 eV.
[0459] [Table 3]
[0460] Table 3 shows the heating temperature conditions for step S17 for samples 1 to 5, the Mg1s analysis results in XPS analysis, the peak position of the Mg1s peak for each sample, and the full width at half maximum of the peak.
[0461] As shown in Table 3, analysis of the XPS spectra of Samples 1 to 5 revealed that samples heated at temperatures below 900°C in step S17 (Sample 1 and Sample 2) had peak components originating from O-Mg-O bonds and O-Mg-F bonds, while samples heated at 900°C or higher (Sample 3, Sample 4, and Sample 5) had peak components originating from O-Mg-O bonds. It should be noted that even when the above analysis results indicate 0.0%, this does not mean that the corresponding bond is completely absent. In other words, the bond indicated as 0.0% may be present below the detection limit.
[0462] Furthermore, as shown in Table 3, in the XPS spectra of Samples 1 to 5, the full width at half maximum of the Mg1s peak was between 2.9 eV and 3.0 eV for samples heated at less than 900°C in step S17 (Sample 1 and Sample 2), while it was between 2.5 eV and 2.6 eV for samples heated at 900°C or higher (Sample 3, Sample 4, and Sample 5).
[0463] In other words, the XPS analysis results showed that, compared to the samples heated at a temperature of less than 900°C in step S17 (Sample 1 and Sample 2), the samples heated at 900°C or higher (Sample 3, Sample 4, and Sample 5) had 100% of the peak components derived from O-Mg-O bonds, O-Mg-F bonds, and F-Mg-F bonds, when the sum of these components is set to 100. Furthermore, compared to the samples heated at a temperature of less than 900°C in step S17 (Sample 1 and Sample 2), the samples heated at 900°C or higher (Sample 3, Sample 4, and Sample 5) had a narrower full width at half maximum (FMAX) of the Mg1s peak, ranging from 2.5 eV to 2.6 eV.
[0464] From the above, it was revealed that the samples in step S17 with a heating temperature of 900°C or higher (Sample 3, Sample 4, and Sample 5) fall within the preferred range described in Embodiment 1 (100% of the peak components originating from the O-Mg-O bond, and the full width at half maximum of the Mg1s peak is within the range of 1.0 eV to 2.6 eV). [Examples]
[0465] In Example 2, discharge rate tests and charge-discharge cycle tests were performed using samples 1 to 5 prepared in Example 1.
[0466] <Fabrication of the positive electrode> Each of the above samples 1 to 5 was prepared as positive electrode active material particles, acetylene black (AB) as the conductive material, and polyvinylidene fluoride (PVDF) as the binder. The PVDF was prepared by dissolving it in N-methyl-2-pyrrolidone (NMP) at a weight ratio of 5%. Next, a slurry was prepared by mixing each of the positive electrode active material particles in a weight ratio of positive electrode active material particles:AB:PVDF = 95:3:2, and this slurry was coated onto an aluminum positive electrode current collector. NMP was used as the solvent for the slurry. After coating the positive electrode current collector with the slurry, the solvent was evaporated.
[0467] Subsequently, to increase the density of the positive electrode active material layer on the positive electrode current collector, a press treatment was performed using a roll press machine. The press treatment conditions were as follows: a first press (linear pressure 210 kN / m) followed by a second press (linear pressure 1467 kN / m). The upper and lower rolls of the roll press machine were both set to 120°C.
[0468] The positive electrode was obtained through the above process. The amount of positive electrode active material particles supported per unit area of the positive electrode was 14 mg / cm². 2 More than 15mg / cm 2 The following was observed. Using this manufacturing method, cathodes having sample 1 through sample 5 were produced.
[0469] <Half-cell fabrication> A coin-shaped half-cell was fabricated using the above-mentioned positive electrode, lithium metal foil, separator, electrolyte, coin cell positive electrode container, and coin cell negative electrode container. The shape of the coin-shaped half-cell was that of a CR2032 type (20 mm in diameter and 3.2 mm in height).
[0470] As the electrolyte, a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of EC:DEC = 3:7 was used, with 1 mol / L lithium hexafluoride phosphate (LiPF6) added, and 2 wt% vinylene carbonate (VC) added as an additive.
[0471] A porous polypropylene film was used as the separator.
[0472] In this way, half-cells using the cathode containing Sample 1 to half-cells using the cathode containing Sample 5 were fabricated.
[0473] <Discharge Rate Test> Using the half-cells prepared as described above, a discharge rate test was conducted in a 25°C environment.
[0474] The conditions for the discharge rate test are described below. In the first charge-discharge cycle, charging was performed at a constant current of 0.2C up to 4.60V, then at a constant voltage until the current value reached 0.05C, and then at a constant current of 0.2C down to 3.0V. In the second charge-discharge cycle, charging was performed at a constant current of 0.5C up to 4.60V, then at a constant voltage until the current value reached 0.05C, and then at a constant current of 0.1C down to 3.0V. In the third charge-discharge cycle, charging was performed at a constant current of 0.5C up to 4.60V, then at a constant voltage until the current value reached 0.05C, and then at a constant current of 1.0C down to 3.0V. In the fourth charge-discharge cycle, charging was performed at a constant current of 0.5C up to 4.60V, then at a constant voltage until the current value reached 0.05C, and then at a constant current of 2.0C down to 3.0V. Here, 1.0C was defined as 200 mA / g per unit weight of positive electrode active material. The measurement environment temperature was set to 25°C. The post-charge pause time from the completion of charging to the start of discharging, and the post-discharge pause time from the completion of discharging to the start of charging, were both set to 10 minutes. In addition, the charging and discharging cycles were each terminated for 20 hours, in conjunction with the termination conditions described above.
[0475] The results of the discharge rate test are shown in Figures 24(A) and 24(B). In the graphs, the horizontal axis shows the "charge rate / discharge rate" of the measurement conditions, and the vertical axis shows the discharge capacity under each measurement condition. The discharge capacity values shown above are obtained by dividing the discharge capacity value of each half cell by the weight of the positive electrode active material particles contained in each half cell. The results of the discharge rate test shown in Figures 24(A) and 24(B) are shown in Table 4.
[0476] [Table 4]
[0477] The discharge rate test results showed that at a discharge rate of 1.0C (charging 0.5C / discharging 1.0C), samples 3, 4, and 5 exhibited superior characteristics compared to samples 1 and 2. Specifically, samples 3, 4, and 5 showed discharge capacities of 200mAh / g or more even at a discharge rate of 1.0C, indicating good discharge rate characteristics. Among them, sample 3 had particularly excellent discharge rate characteristics, showing a discharge capacity of over 160mAh / g at a discharge rate of 2.0C. This is more than 75% of the discharge capacity at a discharge rate of 0.1C, and approximately 80% of the discharge capacity, indicating particularly excellent discharge rate characteristics. [Examples]
[0478] <XRD analysis of high-voltage charging state> Experiments were conducted to investigate the crystal structure of sample 3 under a high-voltage charging state.
[0479] <Fabrication of the positive electrode> Sample 3 was prepared as the positive electrode active material, acetylene black (AB) as the conductive material, and polyvinylidene fluoride (PVDF) as the binder. The PVDF was prepared by dissolving it in N-methyl-2-pyrrolidone (NMP) at a weight ratio of 5%. Next, a slurry was prepared by mixing each positive electrode active material in a ratio of positive electrode active material:AB:PVDF = 95:3:2 (by weight), and this slurry was coated onto an aluminum positive electrode current collector. NMP was used as the solvent for the slurry. After coating the positive electrode current collector with the slurry, the solvent was evaporated. In the preparation of the positive electrode, no pressing treatment was performed after the slurry dried.
[0480] <Half-cell fabrication> Next, a half-cell was prepared using the cathode containing Sample 3. The half-cell was prepared using the same method as in Example 2. The amount of cathode active material loaded in the cathode containing Sample 3 was 7 mg / cm³. 2 That was the case.
[0481] Next, the fabricated half-cells were used for charging, discharging, disassembly, and XRD measurement.
[0482] <Charging and discharging before measurement> Charging was performed by constant current charging at 0.2C up to 4.50V, and then constant voltage charging until the current value reached 0.05C. Discharging was performed by constant current discharge at 0.2C up to 3.0V. As with other tests, 1.0C was defined as 200mA / g per weight of positive electrode active material.
[0483] Next, charging was performed in a high-voltage charged state prior to XRD analysis. Charging was carried out at a constant current of 0.2C up to 4.60V, and then at a constant voltage until the current value reached 0.02C. The charging capacity at this stage was 212.9mAh / g.
[0484] <Disassembly of half-cells and XRD measurement> Subsequently, after charging to 4.60V was completed, the half-cell was disassembled within one hour. During disassembly, in order to remove the positive electrode while it was still charged at high voltage, insulating tools were used and the disassembly was carried out carefully to avoid short circuits. Disassembly was performed using a glove box filled with argon gas with controlled dew point and oxygen concentration. Preferably, the dew point inside the glove box is -70°C or lower, and the oxygen concentration is 5 ppm or lower. Furthermore, since the crystal structure of the positive electrode active material may change due to self-discharge if a long time has passed since the above charging, it is preferable to disassemble and analyze the cell as soon as possible.
[0485] The positive electrode obtained by disassembling the half-cell was placed in a sealed sample holder inside the glove box.
[0486] Subsequently, XRD measurements were initiated within 15 minutes. The XRD equipment and conditions are as follows: XRD system: Bruker D8 ADVANCE X-ray:CuKα1 ray Output: 40kV, 40mA Divergence angle: 0.6 mm Detector: LYNXEYE XE-T Scanning method: 2θ / θ continuous scan Measurement range (2θ): 15° to 75° Step width (2θ): 0.01° setting Counting time: 1 second / step Sample stage rotation: 15 rpm
[0487] The XRD measurement data of the positive electrode (Sample 3) in the high-voltage charged state measured above is shown in Figures 25(A) and 25(B). Figures 25(A) and 25(B) show the reference pattern of the O3' structure (O3') and the reference pattern of the H1-3 structure (H1-3) together.
[0488] Figure 25(A) shows the range where 2θ is between 18° and 21° in the XRD measurement. Figure 25(B) shows the range where 2θ is between 42° and 48°. In addition, representative peak positions were extracted from the XRD measurement data of sample 3 and the reference pattern of the O3' structure, and are shown in Table 5. Furthermore, when the XRD measurement data showing some ranges in Figures 25(A) and 25(B) was analyzed using the crystal structure analysis software DIFFRAC.TOPAS, the lattice constant of the unit cell was found to be 2.81540 (10) for the a-axis. -1 (nm), and the c-axis is 13.7677 (10 -1 It was (nm).
[0489] [Table 5]
[0490] As shown in FIG. 25(A), FIG. 25(B) and Table 5, the peak positions of Sample 3 in the high-voltage charged state in XRD measurement roughly match the peak positions of the reference pattern (Ref) of the O3' structure. That is, it can be said that Sample 3 in the high-voltage charged state has the O3' structure. Further, in Sample 3 in the high-voltage charged state, no peak matching the reference pattern (Ref) of the H1-3 structure was confirmed. That is, in Sample 3 in the high-voltage charged state, the region with the O3' structure is larger than the region with the H1-3 structure, the region with the O3' structure is much larger than the region with the H1-3 structure, there is almost no region with the H1-3 structure, 50% or more of the regions have the O3' structure, 60 wt% or more of the regions have the O3' structure, 70 wt% or more of the regions have the O3' structure, 80 wt% or more of the regions have the O3' structure, or 90 wt% or more of the regions have the O3' structure.
Example
[0491] In Example 4, cross-sectional HAADF-STEM analysis and cross-sectional STEM-EELS analysis were performed on Sample 3 produced in Example 1, and the existing positions of magnesium and nickel in the surface layer portion were investigated.
[0492] <STEM-EELS Analysis> Cross-sectional HAADF-STEM analysis was performed on the edge region of the surface layer portion of Sample 3.
[0493] As pretreatment before being subjected to analysis, Sample 3 was thinned by the FIB method (μ-sampling method), respectively.
[0494] HAADF-STEM analysis and STEM-EELS analysis were performed using the following apparatus and conditions. ≪STEM Observation≫ Scanning transmission electron microscope: JEM-ARM200F NEOARM manufactured by JEOL Ltd. Observation conditions Accelerating voltage: 200 kV ≪EELS Analysis≫ Analysis method: Electron energy loss spectroscopy (EELS) Scanning transmission electron microscope: JEOL JEM-ARM200F NEOARM Acceleration voltage: 200kV Measurement mode: Cs-STEM mode Measurement pitch: 0.04nm Thickness of measurement sample: approximately 25 nm EELS detector: Gatan ContinuumK3 Dwell Time: approx. 0.003sec Number of frames: 1
[0495] Figure 26(A) shows the HAADF-STEM image of the edge region of Sample 3. In Figure 26(A), the numbers 1 through 10 indicate the 1st through 10th columns. Figure 26(B) is a black-and-white inverted version of Figure 26(A) for improved visibility. In other words, in Figure 26(A), areas where atoms are present are shown with high brightness (white), while in Figure 26(B), areas where atoms are present are shown with low brightness (black). Also, in Figure 26(A), areas with a higher abundance of atoms with larger atomic numbers are shown with higher brightness, while the opposite trend is observed in Figure 26(B).
[0496] As shown in Figures 26(A) and 26(B), in the first to third columns, there was no difference in brightness between the locations of atoms in each column (vertical arrangement in the figure), exhibiting the characteristics of a rock salt crystal structure. Furthermore, from the tenth column onward, layers with high brightness (horizontal arrangement in the figure) and layers with low brightness were observed alternately in the vertical direction of the figure, exhibiting the characteristics of a layered rock salt crystal structure.
[0497] In Figure 26(A), the high-luminosity layers from the 10th column onward can be considered layers of layered rock salt-type cobaltsite, while the low-luminosity layers can be considered layers of layered rock salt-type lithiumsite. Similarly, in Figure 26(B), the low-luminosity layers from the 10th column onward can be considered layers of layered rock salt-type cobaltsite, while the high-luminosity layers can be considered layers of layered rock salt-type lithiumsite.
[0498] Furthermore, as shown in Figure 26(A), in the range from the 4th to the 9th column, the layer of lithium site in the layered rock salt type showed alternating arrangements of bright spots (5th, 7th, and 9th columns) and bright spots (4th, 6th, and 8th columns) in the depth direction, exhibiting the characteristics of a spinel-type crystal structure.
[0499] Figures 27(A) to 28 show mapping images of STEM-EELS analysis in the same region as Figure 26(A). Figure 27(A) is a mapping image in which the brightness of cobalt locations is shown as low (black), Figure 27(B) is a mapping image in which the brightness of magnesium locations is shown as low (black), and Figure 28 is a mapping image in which the brightness of nickel locations is shown as low (black).
[0500] Furthermore, in Figures 26(B) to 28, the rectangles enclosed by solid lines represent regions a, b, c, and d, and the dashed lines indicate the respective positions of columns 1 through 10.
[0501] Table 6 shows the results of the STEM-EELS analysis for regions a, b, c, and d. In Table 6, "Detected (Low)", "Detected (Medium)", and "Detected (High)" indicate detection, while "-" indicates that the detection limit was not reached. The notation in parentheses when an element is detected indicates the height of the EELS detection peak in three stages for each element; for example, "Detected (Medium)" for magnesium and "Detected (Medium)" for nickel do not necessarily indicate the same concentration.
[0502] [Table 6]
[0503] As shown in Table 6, the presence of magnesium was confirmed in regions a, b, and c. Nickel was also confirmed in regions a, b, c, and d. Furthermore, cobalt was confirmed in regions a, b, c, and d; however, in region a, considering the spatial resolution of the EELS analysis, it is possible that the detection was misinterpreted due to the influence of surrounding cobalt sites.
[0504] As described above, STEM-EELS analysis of the edge region of the positive electrode active material particles revealed a region between the rock salt structure region and the layered rock salt structure region, containing lithium sites (regions a and c) where magnesium and nickel are detected, cobalt sites (region b) where magnesium and nickel are detected, and cobalt sites (region d) where nickel is detected.
[0505] From the results in Figures 26(B) to 28 and Table 6, it can be inferred that a crystal structure of space group Fd-3m, as shown in Figures 5(A) to 6(F), exists between the rock salt structure region and the layered rock salt structure region. The schematic diagram of the crystal structure in Figure 5(A) shows LiCoO2 of space group Fd-3m with lithium at position 16c, cobalt at position 16d, and oxygen at position 32e in Wyckoff notation. Since this crystal structure is considered to be the same as the crystal structure described in Non-Patent Documents 13 and 14, it was confirmed that the region shown in Figure 26(A), etc., as having the characteristics of a spinel-type crystal structure, has a LiTiO2 structure (spinel' structure) of space group Fd-3m.
[0506] In the structure shown in Figure 5(A), if magnesium and nickel are substituted for a portion of the lithium position at 16c, and nickel is substituted for a portion of the cobalt position at 16d, the results in Figures 26(B) to 28 and Table 6 can be explained without contradiction. Specifically, regions A, B, C, and D enclosed by dashed lines in Figure 5(A) correspond to regions a, b, c, and d in Figures 26(B) to 28, respectively, and the presence of lithium, magnesium, and nickel at the 16c position of the space group Fd-3m, and cobalt and nickel at the 16d position can explain the results in Figures 26(B) to 28 and Table 6.
[0507] For example, in region A, only the Wyckoff position 16c of the space group Fd-3m is present. <110> In the region a of STEM-EELS analysis, which is located in a position that overlaps in the direction, magnesium and nickel were detected in the 4th to 9th columns of positive electrode active material particles corresponding to region A. Although lithium was not included in the detection target for this analysis, it is speculated that lithium is present in region a. Furthermore, for example, regions B and C are located at Wyckoff positions 16c and 16d of space group Fd-3m, respectively. <110> In regions b and c of the STEM-EELS analysis, which show overlapping positions in the direction, magnesium and nickel were detected in the 4th to 9th columns of the positive electrode active material particles corresponding to regions C and D. Furthermore, for example, in region D, only the Wyckoff position 16d of space group Fd-3m was detected. <110> In region d of the STEM-EELS analysis, which is located in a position overlapping in the direction and corresponds to region D, nickel is detected while magnesium is below the detection limit.
[0508] Furthermore, it can be assumed that the cobalt present in region b of the STEM-EELS analysis includes not only trivalent cobalt but also divalent cobalt. Conversely, it can be assumed that the cobalt present in region d of the STEM-EELS analysis is predominantly trivalent cobalt.
[0509] From the above, it has become clear that a positive electrode active material according to one aspect of the present invention has a region of space group Fd-3m between a region of rock salt structure and a region of layered rock salt structure in the edge region, and in this region, lithium, magnesium, and nickel are present at position 16c, and cobalt and nickel are present at position 16d.
[0510] In the case of the structure described above, compared to the case where the rock salt structure region and the layered rock salt structure region are in direct contact at the edge region, the internal stress is smaller, the surrounding crystal structure can be stabilized, and oxygen desorption can be suppressed. As a result, it can be used as a positive electrode active material with little capacity degradation even when repeatedly charged and discharged at high voltage. Furthermore, in the crystal structure shown in Figure 5(A), lithium is arranged in region A, allowing for smooth movement of lithium during charging and discharging, and similar lithium pathways exist in three dimensions, so it can be used as a positive electrode active material that enables rapid charging and rapid discharging. [Examples]
[0511] In Example 5, cross-sectional STEM-EELS analysis was performed on the edge region of Sample 3 prepared in Example 1 to investigate the valence of cobalt in the surface layer.
[0512] As a pretreatment before analysis, each of the three samples was sectioned using the FIB method (μ-sampling method).
[0513] HAADF-STEM analysis, STEM-EELS analysis, and STEM-EDX analysis were performed using the following instruments and conditions. <<STEM Observation>> Scanning transmission electron microscope: JEOL JEM-ARM200F NEOARM Observation conditions: Acceleration voltage: 200kV ≪EELS analysis≫ Analytical method: Electron energy loss spectroscopy (EELS) Scanning transmission electron microscope: JEOL JEM-ARM200F NEOARM Acceleration voltage: 200kV Measurement mode: Cs-STEM mode Measurement pitch: Approximately 0.15 nm Thickness of measurement sample: approximately 30 nm EELS detector: Gatan ContinuumK3 Dwell Time: Approx. 0.05sec Number of frames: 1
[0514] Figure 29(A) shows a HAADF-STEM image of the edge region of sample 3, with cross-sectional STEM-EELS analysis performed at the same location. In Figure 29(A), the left side of the figure represents the exterior of the sample 3 particle, and the right side represents the interior of the sample 3 particle.
[0515] Figure 29(B) shows the results of STEM-EELS analysis in the same region as Figure 29(A). Figure 29(B) is a valence mapping image of cobalt. Figure 30 shows the results of the 2D data cobalt valence mapping image shown in Figure 29(B) as a 1D line analysis. Figure 31(A) shows the standard spectra of divalent cobalt and trivalent cobalt used to calculate the valence of cobalt. In Figure 31(A), the vertical axis represents the count number of the STEM-EELS analysis, and the horizontal axis represents the value of the energy loss.
[0516] This section describes the method for creating a cobalt valence mapping image. First, energy spectra were acquired using STEM-EELS analysis at a pitch of approximately 0.15 nm in the same region as shown in Figure 29(A). Next, the energy spectra acquired at each location were calibrated using the zeroloss peak (peak with zero energy loss). Next, background removal was performed on the energy spectra, using the counts in the energy region lower than the Co L3 edge as the background region. Next, a process was performed to remove the effects of multiple scattering. Then, peak fitting was performed using the standard spectra of divalent cobalt and trivalent cobalt shown in Figure 31(A). Next, the valence was converted from the ratio of the fit coefficients of divalent and trivalent cobalt obtained by peak fitting. All of the above processing on the energy spectra was performed on the data corresponding to each location to obtain matrix data on the valence of cobalt. Next, the matrix data on the valence of cobalt was processed using a median filter. Next, the matrix data regarding the valency of cobalt was imaged using a grayscale palette, with a valency of 2.4 represented as black and a valency of 2.9 as white, to obtain the cobalt valency mapping image shown in Figure 29(B). In this analysis, regions where the STEM-EELS intensity was low and the cobalt spectrum was not clear (left side of Figure 29(B)) were judged to be outside the particle and were displayed in black.
[0517] Note that the standard spectrum of divalent cobalt in Figure 31(A) was obtained using cobalt(II) oxide (product code: 035-05651) manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., and the standard spectrum of trivalent cobalt was obtained using lithium cobalt(III) oxide (product code: 442704) manufactured by Sigma-Aldrich.
[0518] To create Figure 30, first, the average, maximum, and minimum values of cobalt valences were calculated from the data (column data) corresponding to pixels arranged in a direction perpendicular to the direction of arrow A (depth direction) on the paper (column direction) as shown in Figure 29(B). Each pixel has a pitch of approximately 0.15 nm. Next, the graph in Figure 30 was created using the average, maximum, and minimum values for each column data as the values on the vertical axis and the position in the direction of arrow A as the value on the horizontal axis.
[0519] As shown in Figures 29(A) to 30, in the region with a LiTiO2-type crystal structure of space group Fd-3m and the region with a rock salt-type crystal structure, there were regions with lower cobalt valencies compared to the region with a layered rock salt-type crystal structure. Using Figure 31(A), the method for calculating the cobalt valency in creating a cobalt valency mapping image will be explained.
[0520] Furthermore, when we extracted and examined cobalt valency data from two rows of particles close to the outside (dashed lines in Figure 31(B)) corresponding to the region with a rock salt-type crystal structure, we calculated that the highest valency in the region with a rock salt-type crystal structure was 2.75, and the lowest valency was 2.46. The average valency in the region with a rock salt-type crystal structure was calculated to be 2.62. In addition, the frequency distribution of the valency data in this region as the population showed that the valency (V10) at which 10% of the population was below this value was 2.54, the valency (V50, median) at which 50% of the population was below this value was 2.61, and the valency (V90) at which 90% of the population was below this value was 2.69. Figure 31(B) is a cobalt valency mapping image from Figure 29(B) with dashed lines indicating the locations of the extracted regions.
[0521] Thus, in a positive electrode active material particle 100 having a structure in which, from the interior 100b toward the exterior of the positive electrode active material particle 100, a region with a layered rock salt type crystal structure, a region with a LiTiO2 type crystal structure of space group Fd-3m, and a region with a rock salt type crystal structure are arranged in that order, the average valence of cobalt in the region with the rock salt type crystal structure was in the range of 2.54 to 2.69. Therefore, it is considered that stability during high-voltage charging can be enhanced and lithium ions can enter and exit the positive electrode active material particle 100 sufficiently.
[0522] In other words, the positive electrode active material particles 100 in one aspect of the present invention have a region in contact with the electrolyte that has a highly stable rock salt-type crystal structure, and a region with a LiTiO2-type crystal structure of space group Fd-3m where lithium pathways exist in three dimensions. This allows the positive electrode active material to exhibit both minimal capacity degradation even after repeated high-voltage charging and discharging, and to be capable of rapid charging and rapid discharging. [Explanation of symbols]
[0523] 10 Lithium-ion batteries 11 Positive electrode 12 Negative electrode 13 Separator 21 Positive electrode current collector 22 Cathode active material layer 31 Negative electrode current collector 32 Negative electrode active material layer 41 Conductive material 51 Electrolytes 100 Positive electrode active material particles 100a Surface layer 100b internal 200 Second positive electrode active material particles< / edx> < / xps> < / xrd>
Claims
1. It has a positive electrode and a negative electrode, The positive electrode has positive electrode active material particles, The positive electrode active material particles contain lithium, cobalt, oxygen, magnesium, fluorine, nickel, and aluminum. The interior of the positive electrode active material particles has a layered rock salt type crystal structure with space group R-3m. The positive electrode active material particles have a layered rock salt-type crystalline structure, with LiTiO2 having a space group Fd-3m, extending from the inside outwards. 2 It has edge regions arranged in the order of a region having a type of crystal structure and a region having a rock salt type crystal structure. In the STEM-EELS analysis of the region having the aforementioned rock salt-type crystal structure, a region with a cobalt valency of 2.54 or more and 2.69 or less is observed. Lithium-ion rechargeable battery.
2. In claim 1, When the arrangement of bright spots on the surface of the positive electrode active material particles observed in the cross-sectional HAADF-STEM image of the edge region is defined as the first row, at least a portion of the fourth to ninth rows located in the interior direction of the positive electrode active material particles contains the LiTiO 2 It has a region of the type of crystal structure, The LiTo 2 The region of the crystal structure of this type has lithium sites in which magnesium and nickel are detected in STEM-EELS analysis, cobalt sites in which magnesium and nickel are detected, and cobalt sites in which nickel is detected. Lithium-ion rechargeable battery.
3. In either claim 1 or claim 2, Lithium metal is used as the negative electrode, and the electrolyte is a mixture of lithium hexafluoride phosphate, ethylene carbonate, diethyl carbonate, and 2 wt% vinylene carbonate. At 25°C, the battery is charged with a constant current of 0.5C (while satisfying 1.0C = 200mA / g) until the voltage reaches 4.60V, and then charged with a constant voltage until the current reaches 0.05C. When the positive electrode was analyzed by XRD using CuKα1 in an argon atmosphere, the XRD pattern had diffraction peaks at least at 2θ = 19.25 ± 0.12° and 2θ = 45.47 ± 0.10°. Lithium-ion rechargeable battery.
Citation Information
Patent Citations
Positive electrode active material, method for manufacturing positive electrode active material, and secondary battery
JP2018206747A
Secondary battery and electronic apparatus
JP2022070247A